Physicochemical, flavor, and metabolic characteristics of fermented goat, mare, and camel milk beverages - Jiayang Li; Xingxing Deng; Junnan Hu; Hui Li; Rulan Xiao; Zixin Dai; Lianchao Zhang; Songyi Lin; Zhiqiang Lu (International Dairy Journal, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Multifunctional carboxymethyl chitosan/gelatin bilayer film loaded with phage capsules, anthocyanins, and titanium dioxide-loaded cyclodextrin-metal organic frameworks for pork preservation and freshness monitoring - Huili Wang; Jisi Deng; Alberto Danielli; András Székács; Hui Shi (Food Control, 2026)

Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Molten salt-templated synthesis of Fe-N5 sites on ramie-derived porous biochar for enhancing singlet oxygen generation and antibiotic degradation - Chenxi Huang; Dong Li; Yutong Zhang; Meifang Li; Xinjiang Hu; Chao Huang; Xiaofei Tan; Jiaqin Deng; Xi Hu; Hui Wang (Bioresource Technology, 2026)

Stathmin-mediated autophagy drives the differentiation of dermal fibroblast into myofibroblast under TGFβ1 stimulation - Hui Tang; Luqi Yang; Yanhai Feng; Jianxin Wu; Yi Liang; Zhenglin Li; Lingbo Li; Wan Zhao; Xiaolin Deng; Dan Luo; Xia Lei; Lingfei Li (Molecular Biology Reports, 2026)

Knockout of kdm4aa inhibits early embryonic development in zebrafish via downregulating cyp26a1 - Rui Deng; Xinqing Cai; Hui Jiang; Yuting Luo; Weiran Chai; Bingshe Han; Junfang Zhang (Molecular Genetics and Genomics, 2026)

Creation of new varieties of tetraploid willow (Salix suchowensis) and their evaluation for salt tolerance - Mingchao Deng; Mengru Li; Chaonan Qian; Siwei Kan; Yandong Mei; Hui Wei; Guoyuan Liu; Yanhong Chen; Jian Zhang (Molecular Genetics and Genomics, 2026)

An integrated molecular classification system identifies distinct prognostic clusters of non-muscle-invasive bladder cancer - Kezhi Liu; Zhenhua Chen; Xiaohan Jin; Hui Liang; Haihua Liu; Jinwei Chen; Chengpeng Gui; Yuhang Chen; Ziran Dai; Hao Zhou; Zheyu Ai; Zhu Wang; et al. (Functional & Integrative Genomics, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Defining optimal elevation thresholds for mangrove restoration through dynamic tidal simulation: Evidence from morphological and physiological assessment of five species in Zhanjiang Bay, China - Jianjian Huang; Bing Yang; Xin Zhou; Jie Chen; Suqing Liu; Kangyi Deng; Xiuxuan Lin; Yiting Chen; Ruixuan Wang; Yuzhong Zheng; Qinghan Wu; Hui Zhu; et al. (Ecological Engineering, 2026)

An integrated gene annotation and body-wide single-cell atlas of the Pacific White shrimp, Litopenaeus vannamei - Xi Xiong; Zehua Zeng; Yuanyan Xiong; Weiwen Huang; Dandan Huang; Zhaojie Deng; Wen Li; Huiling Zhang; Zhiye Zeng; Hui Ren; Tianhong Chen; Lian Gan (Aquaculture, 2026)

Seismic resilience assessment of underground subway stations - Jia Yang; Peng Deng; Hanlin Wei; Zhicheng Liu; Hui Wang; Xingzhong Nong; Chao Zhang; Qihang Huang; Renpeng Chen (Tunnelling and Underground Space Technology, 2026)

Simultaneous remediation of arsenic and cadmium co-contaminated paddy soil via an electrode-potential-controlled sediment bioelectrochemical system - Xiaoting Zhang; Can Jiang; Luo Peng; Ying Chen; Hui Jiang; Meihui Tian; Huajian Deng; Shiqiang Wei (Journal of Environmental Chemical Engineering, 2026)

Hierarchical porous carbons derived from coal/heavy oil hydrogenation co-refining residue for supercapacitor applications - Yu Xin; Zhixing Huang; Xiliang Tong; Hui Luo; Feng Du; Wenan Deng; Qingshan Zhao; Chuan Li (Fuel, 2026)

Global regulation, application categories, toxicological safety, and analytical methodologies of selenium nutritional fortifiers: a critical review - Hongan Li; Hui Liu; Danni Wang; Zeyuan Deng; Hongyan Li (Food Research International, 2026)

Structure-function relationships of pectic Fibers from pitaya Peel in astaxanthin-loaded emulsion systems - Jingteng Deng; Chong Chen; Hui Teng; Yuli Liao; Bei Liu; Zilin Chen; Huifan Liu; Xi Xie; Lei Chen; Chao Ai (Food Chemistry, 2026)

Designing microstructure for improved quality: Texture and stability optimization in galangin-loaded bigels - Yitong Wang; Lei Chen; Ruoxin Liu; Liya Wen; Zhixian Deng; Ximin Huang; Qifu Tan; Hui Teng; Yanan Zhao (Food Chemistry, 2026)

Evaluation of load-carrying capacity of horizontal joints in concrete wind turbine towers - Ji-Ke Tan; Yun-Hui Zhang; Qiang Li; Wan-Lang Zheng; Mei-Ni Su; Fei Deng (Engineering Structures, 2026)

Mercury isotopes trace (meta-)sedimentary melting in pegmatite lithium mineralization in the Eastern Songpan-Ganzi Belt, China - Weipeng Liu; Hui Zhang; Yong Tang; Zhenghang Lv; Shukuan Wu; Wei Mao; Changzhou Deng (Chemical Geology, 2026)

Field measurement and numerical simulation of turbulent dispersion effect of wind-driven rain on a building in an urban street canyon - Hui Wang; Haoran Pang; Xiaobo Xie; Yangchen Deng (Building and Environment, 2026)

A Study on the Effects of Modified Coal Gangue Ceramsite on Soil Water Retention and Maize Growth under Drought Stress Based on Pot Experiment - Kun Zhang; Xin Yan; Jiazhang Han; Yubin Li; Hui Deng (Water, Air, & Soil Pollution, 2026)

MiR-424 induce buffalo (Bubalus bubalis) follicular atresia via targeting and inhibiting SERPINB2 - Guofeng Bai; Qiao Lv; Yuying Wu; Lingxiu Zou; Hui Li; Yongmei Wu; Yanyan Yang; Ruimeng Zhang; Sufang Yang; Deshun Shi; Yu Pan; Yanfei Deng (Animal Reproduction Science, 2026)

Microplastisphere as a crowded and inclusive micro-ecosystem in seagrass meadow: Cross-kingdom connections and microbial food web - Qiqi Wu; Yu Xia; Yiwei Tao; Chengjun Ge; Yuanyuan Zhao; Dan Feng; Hui Deng (Marine Pollution Bulletin, 2026)

Constructing a High-Spatiotemporal-Resolution NO2 Dataset for China: Bias Correction of GEMS Data Using TROPOMI as a Benchmark - jiarong Yao; Hui Chen; Ziwei Chai; Zongyao Wang; Ruimin Deng; Jiantao Dong; Mengjie Zhang; Jingxuan Zhao; pfei Ma (Remote Sensing Applications: Society and Environment, 2026)

Effects of an endophyte Aspergillus niger in controlling internal browning of pineapple and its biosafety assessment - Qiuping Deng; Miaomiao Peng; Fei shen; Bin Wang; Hui Gu; Shijiang Zhu; Guang Wang (Postharvest Biology and Technology, 2026)

Dissolution mechanism of gold in a high-valent Cu(III)-assisted iodide system: towards eco-friendly and fast gold oxidative leaching from ore and e-waste - Lei Hou; Aurora Robledo Cabrera; Hui Guo; Zhenshuai Wang; Huihui Zeng; Jiushuai Deng; Baolin Xing (Minerals Engineering, 2026)

Seasonally varied cross-shelf transport of sedimentary particles in the river-dominated margin sea elucidated by radionuclides - Jinlong Wang; Mark Baskaran; Sheng Zeng; Hui Wu; Silu Zhou; Jinzhou Du; Bing Deng (Marine Geology, 2026)

Rapid quantitative detection of aflatoxin B1 in soybeans using a natural anthocyanin-based colorimetric sensor array - Hui Jiang; Ziyue Chen; Jingwen Zhu; Fanzhen Meng; Jihong Deng; Yuhan Ding; Congli Mei (Journal of Stored Products Research, 2026)

Black carp DDX3b suppresses antiviral immunity by inhibiting IRF7 modifications and promoting its lysosomal degradation - Liang Chen; Ziting Zhao; Zhihao Du; Xinyi Liang; Shuhao Deng; Sitong Wu; Jun Yan; Hui Wu; Ji Liu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2026)

Deploying multifunctional forward bases in gastric firmly adherent mucus via micron-scale interlock of adaptive disulfide-braked micromotors - Zhen Ren; Hui Deng; Yi Zhang; Junwei Lu; Xiaoxu Cao; Yiting Xu; Zhuo Chen (Chemical Engineering Journal, 2026)

Moisture transfer-driven quality enhancement in solid-state fermented Daqu: Synergistic effects of microbial community adaptation and functional enzyme metabolism - Mengyao Wu; Hui Liao; Yi Luo; Yongqi Yao; Deng Yang; Ziyuan Hu; Ling Gao; Xiaole Xia (Bioresource Technology, 2026)

Historical grazing intensity determines the response patterns of plant community and soil nutrient stocks to grazing exclusion in a temperate meadow steppe - Haonan Guo; Xiaoping Xin; Jiquan Chen; Phil J. Murray; Maira Kussainova; Wei Fang; Zhigang Zhao; Hui Li; Cuixia Jiang; Yufan Si; Amarjargal Amartuvshin; Alim Pulatov; et al. (Agriculture, Ecosystems & Environment, 2026)

Characterization of a Novel Endolysin Sb1-LysAEJ as a Biocide and Food-contact Surface Disinfectant for the Control of Staphylococcus aureus - Hui Yin; JingJing Deng; WanEr Li; ZhanPeng Li; YiXi Yang; Jian Li (Probiotics and Antimicrobial Proteins, 2026)

Triphenyltin-induced hepatotoxicity in zebrafish larvae: A multi-omics insight into lipid metabolism disruption and inflammation - Yu Zhang; Mengjiao Li; Wenyi Li; Xiyue Liu; Hongru Liu; Xinxin Deng; Tingting Qian; Hui Liu; Li Wang (Pesticide Biochemistry and Physiology, 2026)

Improvement of surface hydrophilicity by nanometer oxides to promote aluminum-water reaction to generate hydrogen - Gen-Wang Ma; Xiao-Han Guo; Wei-Zhuo Gai; Yang Yang; Jie Zhang; Zheng-hui Pan; Zhen-Yan Deng (Fuel, 2026)

Citric acid-induced aqueous phase separation method in the fabrication of chitosan/nisin films for the preservation of chilled pork - Yi Deng; Jiahui Li; Zhiao Du; Baohua Kong; Qian Chen; Zhihong Pan; Hui Wang (Food Hydrocolloids, 2026)

Click-crosslinked nano-hydrogel enables metabolic immune reprogramming for diabetic foot ulcers - Heng Gong; Tingjiang Gan; Xikun Ma; Ye Wu; Yaxing Li; Shijiu Yin; Biao Cao; Xiangtian Deng; Cheng Zheng; Yunbing Wang; Hui Zhang (Science China Life Sciences, 2026)

Lagged hydrological responses and wavelet-guided displacement prediction of reservoir landslides in the xiluodu reservoir area - Kun Tian; Hui Deng; Jianhui Deng; Zhenghuan Ye; Wenjiang Zhang; Siyuan Zhao; Hua Li (Bulletin of Engineering Geology and the Environment, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Impact and evaluation of different temporal compositing strategies on the accuracy of tea plantation remote sensing mapping - Deng Zhi-Yong; Wu Guo-Hui; Liu Xiao-Jing; Yang Ya-Jie; Luo Jian; Zhang Hai-Yao; Du Xin-Lu; Li Ting; Wang Shan (International Journal of Remote Sensing, 2026)

Simulation study of exoskeleton–musculoskeletal coupling for exoskeleton assistance via multi-agent reinforcement learning - Lei Sun; Hui Li; Aofei Deng; Wei Wang (Medical & Biological Engineering & Computing, 2026)

EasyAphid: a comprehensive method for aphid infestation quantification in wheat using EVC-YOLO-Seg model and RGB images - Haotian Deng; Hui Deng; Jiawei Chen; Xin Liu; Zijun Pei; Chenzhao Gao; Qi Sun; Xin Zhang; Shijie Zhai; Xueli Hu; Shuming Fan; Xiao Wang; et al. (Computers and Electronics in Agriculture, 2026)

BmAHR regulates antennal development and olfactory gene expression to control mating behavior in Bombyx mori - Yuping Deng; Zhiping Xing; Tao Lu; Hui Dong; Zhipeng Li; Bo Hu (Insect Biochemistry and Molecular Biology, 2026)

Functional characterization of a previously unknown gene governing metamorphosis in Bombyx mori - Tao Lu; Zhiping Xing; Hui Dong; Yuping Deng; Zhipeng Li; Han Gao; Xiaojing Liu; Bo Hu; Anjiang Tan (Insect Biochemistry and Molecular Biology, 2026)

Characteristic aroma, antioxidant properties, and extraction mechanism of Hemerocallis hydrosol extracted by deep eutectic solvent - Wanlin Ye; Fucheng Wei; Weijun Deng; Mengyun Tang; Hui Guo; Jing Hu (Food Chemistry, 2026)

Multi-marker UPLC-MS/MS detection of sesame, soybean, and peanut oil adulteration in camellia and olive oils: a high-sensitivity approach for food authenticity - Nan Deng; Hui Wang; Fangping Yin; Xiaobo Hu; Jijun Qin; Feifei Zhong; Ben Li; Wenting Cao; Peng Zhou (Food Chemistry, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

High efficiency biosynthesis of 1α,25-Dihydroxyvitamin D3 via engineered dihydroxylase and deep eutectic solvent based resting cell bioprocess - Fan He; Qiaoqiao Ma; Huahua Zhang; Junheng Gou; Qingbo Deng; Jinsong Gong; Jinsong Shi; Zhenghong Xu; Hui Li (Bioresource Technology, 2026)

Pilot EnKF assimilation of FY-4A AGRI All-sky upper-tropospheric water vapor radiances for a warm-sector heavy rainfall case in South China - Jie He; Weiyu Ding; Hong Wang; Hui Xiao; Siqi Chen; Honglei Zhang; Hua Deng; Xulin Ma (Atmospheric Research, 2026)

Study on the macro-microscopic damage deterioration mechanism of weathered dacite under freeze–thaw cycles - Junqi Yu; Hui Deng; Chenglong Yang (Bulletin of Engineering Geology and the Environment, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Dark side of biodegradable microplastics in mangrove ecosystem: Plastisphere as an overlooked hotspot of sulfate-reducing metabolism - Yiqiao Zheng; Qiqi Wu; Yu Xia; Hui Deng; Yuanyuan Zhao; Jiwei Luo; Dan Feng; Chengjun Ge (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

14-3-3σ alleviates UVB-induced epidermal oxidative stress through the pentose phosphate pathway promotion - Xuyi Deng; Zhengzheng Fu; Xinli Niu; Peiqi Lian; Hui Liu; Yinghui Wang; Fangming Li; Meijuan Zhou (Journal of Photochemistry and Photobiology B: Biology, 2026)

Removing Pb2+ ions from aqueous solution with freshwater cyanobacteria: Combined adsorption and intracellular precipitation - Xiaofei Zhu; Hui Bai; Xiangyang Bi; Haipeng Deng; Neha Mehta; Liyuan Ma; Zhaoyi Dai; Hongmei Wang; Deng Liu (Journal of Hazardous Materials, 2026)

Mechanistic insights into the role of nitrogen configurations driving efficient activation of low-dose ferrate (VI) for sulfonamides elimination - Zhikang Deng; Jinyao Zhu; Xi Chen; Minghui Xiang; Hui Lin; Junwei Ma; Song Cui; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Development and comparative study of rapid detection methods for Salmonella based on multiple molecular and immunological techniques - Jifu Ma; Wei Zhang; Xingmei Deng; Qian Zhang; Feifan Liu; Changan Chen; Yue Yang; Xia Zhou; Zhihua Sun; Jia Guo; Tianyi Zhao; Zhen Wang; et al. (International Dairy Journal, 2026)

Microplastics drive the reconfiguration of microbial sulfur cycling pathways in seagrass bed sediments - Mingguang Luo; Jinluo Fan; Xiujun Wang; Yibing Ge; Dan Feng; Shengkai Cao; Jun Wang; Hui Deng; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge; Honglin Bu (Environmental Pollution, 2026)

Coplanar analysis and rapid window mapping based on the automatic identification of rock mass discontinuities from 3D point clouds in underground excavations - Bo Deng; Qiang Xu; Xiujun Dong; Wei Xiao; Hui Chen; Junheng Cao; Yue Zhao (Engineering Geology, 2026)

CryoClean technology: A novel closed vitrification system combining high efficiency and sterility for embryo cryopreservation - Rongxiang Wang; Hui Yang; Hongjuan Ye; Laiqing Yan; Liya Shi; Jiwen Zhou; Caixia Zhang; Yu Liu; Kejie Yao; Lihua Sun; Shoulong Deng; Jing Xie; et al. (Cryobiology, 2026)

GAN-MT1DInv: A physics-informed generative adversarial network for magnetotelluric inversion - Tuanfu Gui; Juzhi Deng; Hui Chen; Hui Yu; Xianxiang Wang; Xianyang Huang; Chongwei Yuan (Computers & Geosciences, 2026)

An ultra-stretchable, tough yet resilient hydrogel with high fatigue fracture threshold - Changpeng Wang; Hongyao Ding; Yuming Deng; Libo Zhang; Runjie Zhai; Hui Li; Si Yu Zheng (Chemical Engineering Journal, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Advances in the use of Aspen for lignocellulosic biomass gasification - Hong Chen; Yinjie Liu; JiaChen Zuo; Yiqiang Deng; Hui Wang; Qinzhen Fan; Libo Zhang (Bioresource Technology Reports, 2026)

Elevation and vertical gradient changes of microbe-mediated carbon cycling function in Poyang Lake wetland - Yajun Liu; Jingwei Liu; Jichao Zuo; Hui Zhong; Hailin You; Mi Deng; Rongfu Li; Yongming Wu (Plant and Soil, 2026)

Land Subsidence Simulation and Prediction in Typical Urban Lake-infilled Area Using Polynomial and ConvLSTM Models: A Case Study of Shahu Lake, Wuhan, China - Yang Zhang; Kai Lan; Siyu Liu; ChenYang Huang; Hui Deng (Journal of Geovisualization and Spatial Analysis, 2026)

Characteristics and impacts of coastal sea ice disasters in China over the past 60 years - Lijing Deng; Mengyuan Quan; Jianghua Lyu; Wei Guo; Aimei Wang; Bowen Jin; Hui Wang (Journal of Coastal Conservation, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Ecological engineering projects significantly enhanced vegetation recovery: A case study from the Jinsha River Basin (Yunnan section), China - An Chen; Suling He; Yuyin Cheng; Jun Ma; Jinliang Wang; Yuncheng Deng; Haichao Xu; Hui Wang (Land Use Policy, 2026)

Indoor human exposure to dioxins via central air-conditioning systems: Contamination characteristics and health risks from filter dust around a waste-to-energy plant in East China - Jun Yu; Weihong Lai; Xinting Li; Sihan Deng; Chen Wang; Hui Li (Journal of Hazardous Materials, 2026)

Arsenic recovery by UV/sulfite/iodide system: Dual roles of carbonate/bicarbonate - Xilong Zhou; Haoxiang Zhong; Jianing Han; Qiaozhi Li; Ziqi Zheng; Meifang Li; Hui Wang; Ying Fang; Jiaqin Deng; Xinjiang Hu (Journal of Cleaner Production, 2026)

Quantifying infectious murine norovirus 1 in heat-processed seaweed - Shijue Gao; Hui Li; Qingwei Deng; Gloria Sánchez; Xuejun Ma; Hong Yao; Xiyang Wu (Food Research International, 2026)

The structural characteristics, physicochemical properties, rheological behavior and anti-obesity effects of polysaccharides from Pueraria lobata: In-depth study focusing on the gut microbiota-hepatic FGF21 signaling - Hui Niu; Qiong Deng; Baishun Hu; Yuhao Dong; Yan Long; Xiaoqin Zeng; Wenyang Zhang; Qingfei Duan; Qiang Huang; Bin Zhang; Zuman Dou; Shanshui Zeng (Food Research International, 2026)

Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

Different starch-mediated modulation of digestibility disparities between whey and casein proteins: Multiscale structural and interaction mechanism investigations - Ninghua Deng; Hui Yang; Yue Li; Song Zhu; Dejian Huang (Food Hydrocolloids, 2026)

Temperature effects on bonding performance of near-surface-mounted CFRP concrete interfaces: Experimental and finite element studies - Shuang Gong; Miao Su; Xudong Deng; Zegang Song; Isamu Yoshitake; Hui Peng (Engineering Structures, 2026)

Enhanced heterogeneous catalytic removal of 2-methylisoborneol by ozone micronano-bubbles using Mn-FeCO3@IF: Synergistic effect between catalytic activity and microchannel - Zhifeng Lu; Qiujin Deng; Ben Chen; Yanyan Jia; Zongqiang Zhu; Qiujian Yang; Dasen Yang; Sa Chen; Qifeng Liang; Chuqi Song; Hui Lu (Chemical Engineering Journal, 2026)

Antimicrobial Proteins from Limosilactobacillus fermentum GR-9 Inhibit Pathogens and Alleviate Salmonella Paratyphi B Infection in Mice - Jiefang Deng; Jing Ji; Aman Khan; Zemin Wang; Wei Xiang; Hui Qiao; El-Sayed Salama; Jidong Gu; Chunlan Mao; Pu Liu; Xiangkai Li (Probiotics and Antimicrobial Proteins, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Comparative transcriptomic profiling reveals metabolic and regulatory features of Drosophila melanogaster S2 cells relative to newly hatched larval tissues - Deng Chao; Yang Hui (Genes & Genomics, 2026)

Diversified livestock management and urban adaptation in the early Shang capital of Zhengzhou: sequential evidence from cattle and sheep tooth enamel at the Zijingshanlu site, China - Tianyang Gu; Hui Deng; Xiaomin Zeng; Guoding Song; Yanfeng Hou; Guowen Zhang (Archaeological and Anthropological Sciences, 2026)

Circular economy of Castanea henryi : high-value utilization and processing technologies advances - Zhi-hui Deng; Bin Yuan; Yuan-yuan Lu; Xiao-ming Tian; De-fang Niu; Feng Zou; Xiao-ming Fan; De-yi Yuan; Fu-liang Hu (Critical Reviews in Food Science and Nutrition, 2026)

The E3 ubiquitin ligase MIEL1 promotes thermo-responsive growth by blocking auto-ubiquitination and self-degradation of XBAT31 - Lin-Lin Zhang; Qiang-Hua Zhou; Zhi-Ping Deng; Juan Gao; Hui-Dan Luo; Ying-Ying Tian; Jian-Xiang Liu (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Improvement of the treatment of swine wastewater by rational allocation of readily degradable organic matter - Hui Wang; Hongnan Yang; Yingying Cai; Wenkai Han; Lan Wang; Wenguo Wang; Xiong Wei; Liangwei Deng (Journal of Water Process Engineering, 2026)

Buffering failure of the ratio of secondary to primary phases: Risk overestimation of soil heavy metals under alkaline conditions - Yingdong Wu; Zixin Zeng; Rong Teng; Junwei Yang; Jiang Yu; Hui Sun; Siwei Deng; Pengxinyue Huang; Jie Luo; Yi Wu; Xuetao Zhao (Journal of Hazardous Materials, 2026)

Efficient uranium extraction by a bifunctional MXene: Performance and mechanism in weakly acidic uranium mining wastewater - Liangbing Sheng; Dexin Ding; Hui Zhang; Jianhong Ma; Feng Li; Nan Hu; Weiwen Deng; Yang Chen; Zhengji Yi; Rongying Zeng (Journal of Environmental Chemical Engineering, 2026)

Redox coupling induced by nitrite in the UV/sulfite system: Mechanisms and pathways of metformin degradation - Wenyao Liang; Ziqi Zheng; Jiazhen Zheng; Xinjiang Hu; Haoxiang Zhong; Chao Zhang; Changlan Hou; Ying Fang; Hui Wang; Meifang Li; Xi Hu; Jiaqin Deng; et al. (Journal of Environmental Chemical Engineering, 2026)

Poly(deep eutectic solvent)@MOF-801 for technical surveillance of carbaryl: Pesticide residue safety control strategy - Xicheng He; Yumin Yang; Ying Cao; Ziming Wang; Haixiang Li; Zhiliu Liu; Yan Wang; Fengyun Li; Qian Zhang; Abdulla Yusuf; Feiran Li; Mi Hu; et al. (Journal of Environmental Management, 2026)

Red phosphorus triggers endogenous iron activation of sludge biochar for peroxymonosulfate activation: Unravelling superoxide radical and non-radical degradation mechanisms - Minghui Xiang; Zhikang Deng; Yongfei Ma; Yifan Liu; Xiaoyu Xiang; Han Ding; Ranran Zhang; Hui Lin; Junwei Ma; Yongzhen Ding; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

The role of vegetation in the formation of regolith-hosted REE deposits from granitic rocks: The mercury isotope perspective - Yuzhou Feng; Runsheng Yin; Yuanming Pan; Bernd Lehmann; Changzhou Deng; Di Chen; Bing Xiao; Hui Zheng; Huayong Chen (Gondwana Research, 2026)

Dietary L-Se-methylselenocysteine suppresses liver tumor progression via integrated antioxidant, immune, and apoptotic modulation in mice - Hongan Li; Zhengyan Guo; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Research International, 2026)

Fluorescent molecularly imprinted sensor for rapid detection of gentamicin in Milk - Hui Guo; Jing Ding; Jiaxin Li; Shenglan Zhao; Yiting Deng; Peilong Ma; Longteng Wang (Food Chemistry, 2026)

Preparation and characterization of the complex of resveratrol and crab shell derived carbon dots with improved solubility, photostability, antioxidant, and antibacterial properties - Meihui Wang; Zhiao Du; Fei Li; Yi Deng; Jiahui Li; Baohua Kong; Qian Liu; Hui Wang (Food Bioscience, 2026)

Innovative integrated management achieves high productivity and profitability of sugarcane in China with low environmental costs - Huayang Wang; Yinghe Yao; Hui Wang; Jiaxing Chen; Xiao Tang; Prakash Lakshmanan; Xinping Chen; Yan Deng; Fusuo Zhang (European Journal of Agronomy, 2026)

Exploring global sustainable development pathways based on the spatial spillover effects of ecological wellbeing performance - Jing Shi; Dawei Zhang; Hui Xu; Huai Deng; Jiayi He; Xinpu Wang; Yang Wu; Shulin Yan (Environmental Impact Assessment Review, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Global Phosphorus Enrichment Reshapes Terrestrial Phosphorus Cycling - Zixin Chen; Kai Dong; Julian Helfenstein; Dafeng Hui; Constantin M. Zohner; Frank Hagedorn; Manuel Delgado‐Baquerizo; Adam R. Martin; Jiguang Feng; Nan Yang; Xinli Chen; Laurent Augusto; et al. (Global Change Biology, 2026)
Anthropogenic phosphorus (P) inputs are rapidly altering terrestrial P cycling through plant – soil – microbial interactions; however, global patterns and underlying mechanisms driving these changes remain poorly understood. By performing a global meta‐analysis of 1315 observations from 176 studies across diverse natural terrestrial ecosystems, we found that P addition increased P concentrations in foliage, stems, roots, and litter by 62%, 114%, 100% and 63%, respectively. Soil total P, plant‐available P, and microbial P concentrations rose by 43%, 221%, and 70%, while leaf P‐resorption efficiency and soil phosphatase activity declined by 23% and 15%, respectively. Stem P and soil phosphatase activity exhibited consistent trends across tropical, temperate, and boreal zones, suggesting climate‐specific P acquisition strategies. In addition, foliar P responses diverged among ecosystem and plant functional types. These responses were primarily regulated by background soil total P concentration, precipitation, soil pH, and P addition duration and rate. Our findings provide critical insights into the potential consequences of increasing anthropogenic P inputs in natural terrestrial ecosystems, improving our understanding of nutrient cycling and informing future ecosystem management under ongoing global change.

High-fidelity removal of strawberry leaf occlusion via outline-texture improvement network - Ling Zheng; Huiwen Yang; Yudi Chen; Shenao Sun; Hui Zhang; Rui Deng; Nina Zhu; Jialing Chen; Shizhuang Weng (Computers and Electronics in Agriculture, 2026)

Effects of live prey on growth performance, immune and digestive enzyme activities, and intestinal health in juvenile lined seahorse (Hippocampus erectus) - Yaowen Meng; Zhaoji Pan; Jinzhao He; Shengping Zhong; Xinming Liu; Shunli Mi; Hui Wang; Guoqing Deng; Langduorijie Cai; Guoqiang Huang; Chenghai Gao; Lianghua Huang (Aquaculture, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Revisiting the role of small ponds in regulating river water quality in agricultural landscapes: A focus on pond use types and sediment nutrients - Hui Xie; Jiancai Deng; Zhaoshi Wu; Jianwei Dong; Nengsheng Wan; Zhuyang Xiong; Zhenya Li; Yunliang Li; Lei Chen; Xijun Lai (Journal of Environmental Management, 2026)

Analysis of deep structures and key factors for oil and gas accumulation in the Erjiacun Depression of South Poyang Basin based on magnetotelluric sounding imaging - Ronghua Xu; Juzhi Deng; Fasheng Lou; Yang Gao; Zequn Wen; Hui Yu (Journal of Applied Geophysics, 2026)

Fe-Cu bimetal/N-doped carbon nanotubes with oxygen vacancies and multivalent redox cycling for ultrasensitive electrochemical detection of benomyl in fruit samples - Lili Chen; Xiaotong Peng; Jing Zhou; Linbo Deng; Yiming Qiao; Jiapeng Li; Yansha Gao; Xuemin Duan; Hui Chen; Limin Lu (Food Chemistry, 2026)

Novel eco-friendly extraction of oat bran protein: A multifaceted analysis of structure, physicochemical, and functional properties - Hui Peng; Qian Wang; Yanli Zhang; Yaqi Zhao; Wenyuan Zhang; Yunlong Li; Jianjun Deng; Haixia Yang (Food Hydrocolloids, 2026)

Deacetylation-regulated binding mechanism between chitosan and Pb2+ from nano to macroscale - Song Zhang; Yang Shen; Peng Qiu; Mengjia Fang; Peichuang Li; Xiangning Du; Zhengying Deng; Wanhao Cai; Hui-Li Wang (Food Hydrocolloids, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Enhanced substrate tolerance of l-amino acid deaminase by reshaping substrate binding pocket for phenylpyruvic acid production - Kai Chu; Yingjia Tong; Qingbo Deng; Xiaomei Zhang; Jinsong Shi; Zhenghong Xu; Hui Li (Systems Microbiology and Biomanufacturing, 2026)

An improved GA-BP model based on self-organizing map mode unsupervised clustering ability promoting and its application in landslide susceptibility mapping - Penghui Liu; Hui Deng; Anrun Li; Linyi Lv; Tian Yongqing; Zheyi Wu (Natural Hazards, 2026)

Magmatic control on the formation of the Diaoquan Ag-(Cu-Au) skarn deposit in the eastern North China Craton as revealed by zircon, apatite and sulfides - Gao-Hua Fan; Jian-Wei Li; Paul T. Robinson; Kai-Xuan Hui; Xiao-Dong Deng; Wen-Sheng Gao; Jin-Hao Liu; Hang-Jin Jiang (Mineralium Deposita, 2026)

Recent advances in zearalenone degradation: integrating physical, chemical, biological, and innovative methods - Mukhtar Ahmad; Deng Kun; Wang Hui; Jiang Wei (Reviews in Environmental Science and Bio/Technology, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

Optimizing environmental surveillance for early detection of zoonotic pathogens via fecal shedding modeling - Xin Du; Zhiqiang Deng; Yuqing Long; Fenglan He; Chunlong Zhu; Chun Han; Hui Li; Songzhe Fu (Water Research, 2026)

ASSR-mediated sludge yield reduction couples deterministic enrichment of Nitrospira with metabolic resource partitioning - Huanzhong Deng; Junling Yang; Ruohong Li; Kewen Li; Hui Lu; Bing Lin; Xingquan Xu; Jiajun Liao; Congrong Ye; Jie Deng; Bo Wu; Lianpeng Sun (Water Research, 2026)

The emplacement of an intraplate volcanic system in the Xiangshan Basin, Southeast China, implied from resistivity constrained 3D gravity and magnetic joint inversion - Min Feng; Juzhi Deng; Hui Yu; Hui Chen; Yunong Wei; Yanguo Wang; Xiao Chen (Tectonophysics, 2026)

Spatial pattern of spring dissolved organic matter and microbial communities under dual anthropogenic-natural forcing in a tropical semi-enclosed bay - Yuechu Zheng; Xin Zhou; Siyi Deng; Hui Zhao (Marine Environmental Research, 2026)

Trade-offs of leaf structural adaptive traits of desert steppe plants under precipitation variation - Si-Yu Guan; Ke-Chen Song; Hai-Ying Hu; Hao Zhang; Jia-Yi Yong; Wen-Hui Deng; Xiao-Na Zhao (Journal of Arid Environments, 2026)

Pipeline sediments and secondary water supply tanks as dominant reservoirs of microbiological risk in drinking water distribution systems - Dong Hu; Hui Yang; Kun Chen; Fang Hu; Cun Zhang; Mingquan Wang; Wenhai Gao; Hongyi Cao; Yang Deng; Ruibao Jia (Environmental Research, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Characterization and bifidogenic effects of a low-molecular weight polysaccharide isolated from a Chinese herb, Polygonatum kingianum Coll. et Hemsl (Huangjing) rhizome - Xiao-Hui Yuan; Ting-Ting Tu; Yu-Heng Mao; Yan-Chun Wang; Meng-Qi Huang; Lei- Wang; You Luo; Chun-Xiao Wang; Shu-Yi Qiu; Bin- Deng; Ang-Xin Song (Carbohydrate Polymers, 2026)

Retraction notice to “Construction of functional curdlan hydrogels with bio-inspired polydopamine for synergistic periodontal antibacterial therapeutics” [Carbohydrate Polymers 245 (2020) 116585] - Xianqin Tong; Xiaoliang Qi; Ruiting Mao; Wenhao Pan; Mengying Zhang; Xuan Wu; Gang Chen; Jianliang Shen; Hui Deng; Rongdang Hu (Carbohydrate Polymers, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Discovery and optimization of AAK1 inhibitors based on 1H-indazole scaffold for the potential treatment of SARS-CoV-2 infection - Zi Hui; Haowen Deng; Yueying Xu; Yuan Gao; Chenfeng Zhai; Nian-Dong Mao; Hao Che; Zhen Li; Yuting Zhang; Hang Zhang; Tian Xie; Xiang-Yang Ye (Molecular Diversity, 2026)

β-Caryophyllene Induces PPARγ-Mediated Apoptosis and Enhances the Radiosensitivity in Colorectal Cancer Cells - Hui-Wen Chan; Deng-Yu Kuo; Yu-Chieh Jill Kao; Yun-Xuan Tang; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2026)
Purpose This study aimed to investigate the radiosensitizing potential of β-caryophyllene (BCP), a natural CB2 receptor agonist, in colorectal cancer (CRC) cells and to elucidate the underlying molecular mechanisms. Methods Murine CT26 and human HCT116 CRC cells were treated with BCP alone or in combination with radiotherapy (RT). Cell viability was evaluated using the MTT assay, and combination index (CI) values were calculated to assess synergy. Flow cytometry and immunofluorescence were used to analyze cell cycle distribution and DNA damage. Protein expression levels of PPARγ, phosphorylated AKT (pAKT), cyclin D1, Bax, Bcl-2, and cleaved caspase-3 were examined by western blot. Results BCP synergistically enhanced RT-induced cytotoxicity in both CRC cell lines, with CI values ranging from 0.92 to 0.70 in CT26 cells and from 0.78 to 0.68 in HCT116 cells at 4 and 8 Gy irradiation. The combination treatment resulted in significant G2/M arrest and sustained γH2AX expression at both 24 and 48 h, indicating persistent DNA double-strand breaks. BCP suppressed pAKT and cyclin D1 levels while upregulated PPARγ expression. Activated apoptosis was verified by increased Bax/Bcl-2 ratios and elevated cleaved caspase-3 levels. Conclusion BCP enhances the radiosensitivity of CRC cells by promoting RT-induced DNA damage and triggering PPARγ-mediated apoptotic pathways. These findings support its potential as a natural radiosensitizer in CRC treatment.

Woody peat application enriches beneficial soil microorganisms to enhance aromatic compound accumulation in tobacco leaves - Tantan Zhou; Jisheng Xu; Jun Tan; Hui Pan; Yunpeng Zhou; Di Wu; Wei Guo; Qingxia Wang; Jiawen Deng; Jiabao Zhang; Bingzi Zhao (Applied Soil Ecology, 2026)

Flow and heat transfer characteristics in molten salt reactor core channels under the coupled influence of wall heat flux and volumetric internal heat generation - Hui Deng; Chong Zhou; Shanwu Wang; Shuaiyu Xue; Pinyan Huang; Hongxiang Yu (Annals of Nuclear Energy, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Synergies and trade-offs in the food-energy-water nexus of rural households: A case study in the North China Plain - Mengrong Wu; Gengyuan Liu; Richard Morris; Pablo Gregorini; Bojie Liu; Nan Zhang; Qipeng Deng; Duo Xu; Mingwan Wu; Hui Li (Journal of Rural Studies, 2026)

Polystyrene and polyvinyl chloride microplastics exposure induces ocular surface inflammation by causing mitochondrial damage and lipid metabolic disruption - Binyu Wen; Bosheng Ma; Hui Tao; Shen Chen; Jing Zhang; Mengdi Shi; Wenbing Liu; Zhihong Deng (Journal of Hazardous Materials, 2026)

Regulating mineral ions to enhance uranium phytoremediation by Macleaya cordata under synergistic effects of oxalic acid and Fusarium sp. A-2 - Meichen Li; Huang Yu; Tao Lang; Qinwen Deng; Weichao Zhao; Hui Zhang; Yuan Xue; Yongdong Wang; Dexin Ding; Nan Hu (Journal of Environmental Radioactivity, 2026)

Numerical modeling of CO2 storage and gas recovery enhancement in low-permeability carbonate reservoirs via acid-fractured horizontal wells - Jiangtao Hu; Shenglai Yang; Lufei Bi; Xinyuan Gao; Hui Deng; Ermeng Zhao (Fuel, 2026)

Profiling and risk assessment of biogenic amines in Chinese wines: Content variations driven by multifactorial influences - Haiyue Liu; Qiaoyun Deng; Yiding Xie; Hui Zhou; Ju Shen; Weidong Huang; Jicheng Zhan; Yilin You (Food Chemistry, 2026)

Atomically dispersed Zn–N4 catalytic sites on ZIF-8 derived carbon enabling reversible sulfur conversion in a high-voltage acid-alkaline hybrid battery - Haoliang Chen; Wenjie Huang; Hui Wang; Yida Deng; Liuzhang Ouyang; Lichun Yang; Min Zhu (Chemical Engineering Journal, 2026)

Enhancement of microalgal carbon fixation via synergistic interactions with a facultative autotrophic bacterium Cytobacillus KQ-2 - Dandan Yao; Yunhui Li; Zhiqian Han; Ding Tan; Meng Wang; Huan Deng; Hui Wang; Yun Liu (Bioresource Technology, 2026)

A sound-driven digital twin for reducing passengers’ exposure to exhaled bioaerosols in an aircraft cabin - Yue Pan; Hui Liu; Chengzhong Deng; Zhu Li; Chun Chen (Building and Environment, 2026)

Synergistic Nano-antimicrobial Platform: ZIF-8/Ganoderic Acid A Composite with Dual Bactericidal Mechanisms for Infected Wound Healing - Fan Liu; Yan Wang; Haohao Wang; Dong Liu; Hui Deng; Xiaoyuan Ding (Current Microbiology, 2026)

Improvement and validation of a thermal resistance network model for wick-type heat pipe - Xiang Chai; Jiaolong Deng; Xing Xia; Ziyu Song; Xiaojing Liu; Jinbiao Xiong; Tengfei Zhang; Hui He (Annals of Nuclear Energy, 2026)

CL-20 biodegradation and gene analyses of Sphingobium sp. CzL-01 isolated from activated sludge - Cunzhi Li; Xinying Peng; Xiaoqiang Lv; Hui Deng; Bin Zhao; Ting Gao; Huan Li; Yongchao Gao; Wenzhi Gao; Jiacheng Shen; Lifang Hu; Junhong Gao; et al. (Archives of Microbiology, 2026)

Methane emission intensifies the warming effect of carbon dioxide efflux from a subtropical coastal macroalgae aquaculture ecosystem - Yueting Deng; Xianghui Guo; Dengjin Hu; Hui Luo; Yougan Chen; Xudong Zhu (Limnology and Oceanography, 2026)
Macroalgae aquaculture ecosystems have been increasingly recognized as coastal biogeochemical hotspots of air–sea net ecosystem carbon dioxide (CO 2 ) exchange; however, their roles in regulating the temporal variability of net ecosystem methane (CH 4 ) exchange (NME) receive little attention mainly due to very limited data availability. Here, we applied the eddy covariance (EC) technique to acquire 1‐yr (June 2023 to May 2024) NME measurements, over a subtropical macroalgae aquaculture ecosystem in southeast China, to examine the temporal variability of NME across time scales and its contribution to net radiative forcing. The results indicated that (a) this ecosystem acted as a CH 4 source in most months with the summer accounting for about two‐thirds of annual NME of 0.40 g C m −2 yr −1 ; (b) the inclusion of annual NME increased the sustained‐flux global warming potentials (SGWPs) by 11.0% from 219.3 (CO 2 only) to 243.4 g CO 2 ‐eq. m −2 yr −1 for a 100‐yr time horizon; (c) NME and its radiative contribution varied across seasons, farming periods, and growth stages, with the temporal fluctuations mainly controlled by temperature and tidal activities; (d) bimodal varying patterns across tidal levels were identified with larger fluxes occurring when tidal level changed most rapidly. This is the first EC study to confirm that CH 4 emission intensifies the warming effect of CO 2 efflux from macroalgae aquaculture ecosystems. The observed strong temporal variability of CH 4 and CO 2 fluxes and their asynchrony highlight the importance of high‐frequency and continuous flux measurements in accurately assessing their net radiative forcing at both short‐ and long‐term scales.

Cytotoxic effect of a cyclic nonapeptide from Agrostemma githago L. against non-small cell lung carcinoma H460 cells - Chong Yu; Yun-Xi Yang; Jia-Hang Deng; Yi Yang; Jun Yin; Zhi-Hui Liu (Natural Product Research, 2025)

Pore Structure Evolution in Marine Sands Under Laterally Constrained Axial Loading - Xia-Tao Zhang; Cheng-Liang Ji; Le-Le Liu; Hui-Long Ma; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Installation in sand is sensitive to its evolving pore structure, yet design models rarely update permeability for real-time fabric changes. This study tracks the stress-dependent pore size distribution of coarse sand under laterally constrained compression using high-resolution X-ray nano-CT. Scans taken at six axial stress levels show that the distribution shifts toward smaller radii while keeping its log-normal shape. A single shifting factor, defined as the current median radius normalized by the initial value, captures this translation. The factor decays with axial stress according to a power law, and the exponent as well as the reference pressure are calibrated from void ratio data. The resulting closed-form expression links mean effective stress to pore radius statistics without extra fitting once the compressibility constants are known. This quantitative relation between effective stress and pore size distribution has great potential to be embedded into coupled hydro-mechanical solvers, enabling engineers to refresh hydraulic permeability at every computation step, improving predictions of excess pore pressure and soil resistance during suction anchor penetration for floating wind foundations.

Deep banding of controlled-release potassium chloride increases soybean productivity by regulating microbial communities and improving potassium uptake - Zhaoming Qu; Qin Wang; Hao Deng; Qianhui Chen; Hui Dong; Shuihong Yao; Chengliang Li (Soil and Tillage Research, 2025)

Tropical tree-mycorrhizal types show divergent phosphorus adaptive strategies after 12-year simulated acid rain - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying-Ping Wang; Xiaolin Huang; Minghui Hu; Yiren Zhu; Yonghui Li; Jianling Li; Deqiang Zhang; Qi Deng (Soil Biology and Biochemistry, 2025)

Tree-mycorrhizal types differ in their biomass response to nitrogen addition - Guoyin Chen; Yuanliu Hu; Jianping Wu; Richard P. Phillips; Jianyang Xia; Ying-Ping Wang; Dafeng Hui; Jianling Li; Xianyu Yao; Qi Deng (Soil Biology and Biochemistry, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Metallogenic process of the metasedimentary rock-hosted HREE deposit at Guangshui (Hubei Province, Central China) - Cheng-Lai Deng; Shao-Yong Jiang; Xue-Wen Yuan; Hui-Min Su; Wei Wang (Journal of Geochemical Exploration, 2025)

Pilot scale study on treatment of landfill leachate by short-cut nitrification and denitrification coupling sulfur autotrophic denitrification: Performance, cost and carbon emissions - Jinghai Luo; Huiyu Liang; Liao Meng; Haibo Cui; Qiujin Deng; Hui Lu; Ben Chen (Journal of Environmental Chemical Engineering, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Flavor formation and microbial community dynamics in Dong ethnic fermented Anyu - Fenghong Li; Kelang Kang; Qun Huang; Xin li; Shaoping Deng; Yingjuan Wei; Hui Yang; Meijuan Yu (Food Research International, 2025)

Large-ring cyclodextrins for efficient encapsulation of diverse aroma molecules: Exploring mechanism of inclusion complex formation and stabilization - Changyue Deng; Tao Sheng; Hui Zhu; Yujie Wu; Sanxu Shi; Yibin Zhou (Food Chemistry, 2025)

Systematic profiling and bioactivity evaluation of Jiuzao from light flavor baijiu: A by-product rich in bioactive compounds - Siqi Hu; Yuting Zeng; Hongqin Liu; Mingquan Huang; Hui Li; Wen wen Deng; Jihong Wu; Hehe Li; Xiaotao Sun (Food Chemistry, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Enhancing the performance of natural pigment sensor arrays for the detection of Procymidone residues in Allium tuberosum using outcome-corrected decision-making method - Jingwen Zhu; Hengke Chen; Fanzhen Meng; Jihong Deng; Yiran Li; Enze Tian; Hui Jiang (Food Control, 2025)

Insights into the prediction and driving factors of perfluorinated and polyfluoroalkyl substances in sediments from Taihu Lake of China using machine learning models - Hui Xiao; Kai Liu; Ligang Deng; Wanru Yang; Lijian Sun; An Yi; Yuanhang Zhang; Xin Qian; Tong Liu; Huiming Li (Environmental Pollution, 2025)

Liquid metal-doped tough hydrogel with ultralow hysteresis and anti-freezing property for wearable electronics - Bingyao Wang; Yuming Deng; Hui Li; Xiaodong Shen; Hongyao Ding; Xuewen Li; Si Yu Zheng (Chemical Engineering Journal, 2025)

Gut microbiome and postbiotics: bridging the dietary nutrition and feed efficiency in food-producing animals - Zhang-Chao Deng; Meng Liu; Ke-Xin Cao; Mahmoud Mohamed Khalil; Le Luo Guan; Lv-Hui Sun (Science China Life Sciences, 2025)

Botany, traditional uses, phytochemistry, pharmacological activities, and toxicity of the mangrove plant Avicennia marina: a comprehensive review - Pan Zhou; Huihui Hu; Xia Wu; Zhenhui Feng; Xingyan Li; Samad Tavakoli; Kefeng Wu; Luming Deng; Hui Luo (Phytochemistry Reviews, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

Molecular cloning, expression, and bioinformatics analysis of the CueO laccase gene from Escherichia coli SDB2 - Hui Deng; Sicong Li; Yanling Huang; Jiangling Li; Qingsong Ni; Yang Zhao; Jin Chen; Xiurong Peng; Bin Li; Dan Yu (Molecular Biology Reports, 2025)

Spatiotemporal transcriptomic dynamics of rice defense under bacterial blight challenge - Xiuli Liu; Hui Deng; Weijun Cui; Rumeng Xu; Zaozao Zhu; Shaomin Wang; Jie Zhou; Hongjia Liu; Haiyan He; Chengqi Yan; Wona Ding; Yin Lu; et al. (Journal of Plant Diseases and Protection, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Regnase-1 regulates inflammation in T cells of ankylosing spondylitis through the TRAF6 - Yuxin Ren; Yujie Deng; Ziqi Li; Yanyu Zhao; Hanqing Wu; Longbao Xu; Guoqing Li; Hui Zhao; Mengmeng Wang; Guoqi Cai; Faming Pan (Immunologic Research, 2025)

The CMA Global Atmospheric Reanalysis Version 1.5 (CRA1.5) - Tao Zhang; Zijiang Zhou; Zhiquan Liu; Chunxiang Shi; Shuang Yao; Lipeng Jiang; Yan Yao; Zhisen Zhang; Xiao Liang; Zhiqiang Zhang; Junxia Gu; Jie Liao; et al. (Journal of Meteorological Research, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

A novel papillomavirus identified through viromic analysis of stranded Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Huiwei Deng; Hao Zhou; Mengqi Jiao; Qian Ling; Qianjin Fan; Haoyue Huangfu; Ji Pu; Hui Kang; Yujiang Hao; Songhai Li; Xuelian Luo; Jinsong Zheng; et al. (Archives of Virology, 2025)

Water quality monitoring optimization based on human activity intensity: a case study of the Ganjiang River Basin - Yuan Ying; Bao Ning; Li Lanhui; Deng Fuliang; Li Hui (Environmental Monitoring and Assessment, 2025)

Experimental studies on the dynamic behaviors of Kunming highly decomposed peat soils - Lei Hang; Wei Xiao; Peng Xia; Wei-Juan Geng; Deng-Hui Dai; Di Wang; Mao Ye (Soil Dynamics and Earthquake Engineering, 2025)

Ten undescribed sesquiterpenoids isolated from the tuber of Alisma orientale - Deng-Hui Zhu; Jing-Ke Zhang; Peng-Li Guo; Si-Qi Tao; Meng-Nan Zeng; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2025)

Late Triassic ultrahigh-temperature mafic granulite from the North Dabie terrane, Central China - Heng-Cong Lei; Hai-Jin Xu; Hui Zhang; Fei Xia; Cong-Jun Yu; Wang-Chao Li; Liang-Peng Deng; Ling Wang; Jian-Bing Duan (Lithos, 2025)

New perspective on postmortem meat quality changes of Esox Lucius: The role of mitophagy-mediated ferroptosis pathway - Wenbo Yan; Hui Li; Xinyao Yu; Xin Chen; Lingzhen Ma; Xiaorong Deng; Jian Zhang (Food Chemistry, 2025)

Qualitative and quantitative pesticide residue analysis in Allium tuberosum using an electronic nose with multivariate analysis - Fanzhen Meng; Jingwen Zhu; Jihong Deng; Tianqi Wu; Aocheng Qi; Wencheng Zhu; Hui Jiang (Food Chemistry, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

Multi-task detection of pesticide residues in Allium tuberosum using a colorimetric sensor array based on anthocyanin dyes combined with a pattern recognition algorithm - Jingwen Zhu; Fanzhen Meng; Jihong Deng; Chunyu Zhang; Hengke Chen; Huazhi Wang; Hui Jiang (Food Chemistry, 2025)

Integrative omics analysis: Effects of stir-frying with clamshell powder on the physicochemical properties of fish maw - Hui Yu; Yier Li; Yuzhen Zhu; Samad Tavakoli; Xingyan Li; Qianqian Ouyang; Luming Deng; Saiyi Zhong; Chunyu Xiao; Yumeng Wang; Hui Hong; Kefeng Wu; et al. (Food Chemistry, 2025)

Axial compressive performance of RC columns strengthened with textile-reinforced high-strength highly ductile concrete - Ding Wei; Mingke Deng; Ruizhe Li; Wei Zhang; Tong Li; Hui Chen (Engineering Structures, 2025)

Pure hybridized local and charge-transfer materials based white organic light-emitting diodes - Xu Zhang; Hui Dai; Zhiwei Ma; Huangjun Deng; Zhiyong Yang; Juan Zhao; Zhenguo Chi (Chemical Engineering Journal, 2025)

Proton exchange membranes with oriented ion channels for enhanced conductivity - Bingru Lu; Hongyang Ma; Zhanfeng Deng; Jun Lin; Zhongrui Lu; Tianxu Jin; Shaoxiong Zhai; Jiahua Li; Peng Sheng; Qing Ye; Hui Jin (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Surface engineering of MOF-derived hierarchical porous carbons for ultrasensitive detection and discrimination of anticancer and antibacterial drugs - Junlin He; Jun Wang; Zhonghui Luo; Jiaheng Zhang; Yongrong Deng; Bo Liu; Hui Zhao; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Machine learning-based identification of high-gradient gullies using UAV imagery and topography - Fengjie Fan; Fuhuan Zhang; Hui Liu; Ziquan Zuo; Haiqing Yang; Jun Luo; Lei Wang; Qingchun Deng; Bin Zhang (CATENA, 2025)

In situ generation of peracetic acid using phosphotungstic acid: A one-pot strategy for selective delignification of corn stover - Xueyan Liang; Zhen Hao; Xiwen Jia; Kaili Ding; Hui Zhang; Aihua Deng; Haitao Yu; Lujia Han; Weihua Xiao (Bioresource Technology, 2025)

Investigation on co-combustion characteristics of sewage sludge char with biomass: Thermal behavior, synergistic effect, ash melting characteristics and kinetic analysis - Shuanghui Deng; Kuan Xu; Baoan Hui; Zhifeng Li; Zhong Xia; Shilin Yu; Xuebin Wang; Houzhang Tan; Xiangyu Zhang; Zhihua Du (Biomass and Bioenergy, 2025)

The palynoflora from the Lower Cretaceous of Jiuquan Basin, Gansu Province, NW China, and its paleoclimate implication - Yuan-zheng Lu; Sheng-hui Deng (Cretaceous Research, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Effect of DOM transformation on As enrichment from an Alpine river basin in the Western Tibetan Plateau - Yue Jiang; Tianliang Zheng; Hui Li; Hongying Jiang; Yang Deng; Jianfei Yuan; Xingguo Du; Xiangjun Pei (Journal of Environmental Sciences, 2025)

Alloy effects of oil-soluble bimetallic Fe-Ni-S catalysts in the coprocessing of coal and petroleum residue - Hui Luo; Cheng Ding; Zhiqing Wang; Ruming Yan; Wenan Deng; Chuan Li (Fuel, 2025)

Prediction model of spontaneous combustion “three zones” in goaf - Hui Ma; Wanxing Ren; Yaochuang Wang; Haowen Deng; Depeng Zhang (Fuel, 2025)

Physiological responses of Illicium difengpi to simulated persistent and intermittent droughts - Baoyu Liu; Huiling Liang; Xiujiao Zhang; Hai Ren; Manlian Wang; Hui Tang; Xue Zhao; Dafeng Hui; Chenghua Deng (Flora, 2025)

Source-pathway-sink analysis and health risk zoning of heavy metal groundwater pollution in karst chemical park - Jiayi Deng; Jingyang Yu; Baoyue Zhang; Hui Zhao; Zhiliang Zhao; Yi Chen; Shengyan Pu (Environmental Pollution, 2025)

A safe single-anion ionic liquid electrolyte for high-performance sodium metal batteries - Long Wang; Zhibin Li; Guokai Shi; Miaoran Deng; Xusheng Wang; Hui Ying Yang; Wenjie Mai; Jinliang Li (Chemical Engineering Journal, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Soil aggregate stability in karst peak-cluster depressions: How do organic–inorganic cements work together? - Fang Wang; Juan Huang; Yuanfeng Yang; Qiuyue Tang; Hui Wei; Gairen Yang; Xiaoqian Duan; Yusong Deng (CATENA, 2025)

Cigarette smoke-induced glycerophospholipid DLPC promotes macrophage ferroptosis through the USP7/GPX4 regulatory axis in chronic obstructive pulmonary disease - Weibin Ruan; Zhimin Peng; Mingsi Huang; Hui Zhang; Xiaohua Li; Tingting Ma; Jiehua Deng; Mianluan Pan; Ziqing Mai; Xia Meng; Jianquan Zhang (Chemico-Biological Interactions, 2025)

The vascular preferentially expressed OsCOPT7 mediates the long-distance transport of copper in rice - Hui Zhou; Haiyang Tang; Beibei Hu; Jin Zhang; Yuan Qin; Fanrong Zeng; Guang Chen; Zhong-Hua Chen; Fenglin Deng (Plant and Soil, 2025)

Chalcone derivatives containing 1,2,4-triazole and pyridine moiety: design, synthesis, and antiviral activity - Hui Xin; Jiao Tian; Tianyu Deng; Qing Zhou; Yuhong Wang; Hong Fu; Haotao Pu; Wei Xue (Molecular Diversity, 2025)

Bone marrow mesenchymal stem cells promote the recovery of stroke in rats with type 2 diabetes mellitus by inhibiting the activation of TLR4/NF-κB signaling pathway - Fan Peng; Yanping Long; Taolin Zheng; Minghui Leng; Hui Deng (Molecular and Cellular Biochemistry, 2025)

Sediment redox state threshold for N2O emissions and indirect regulatory impact of organic carbon in shallow lakes - Hui Li; Huatang Deng; Yingying Cai; Jianfen Li; Zhenhua Qin; Fangyuan Chen; Xiuyun Cao; Chunlei Song; XinBin Duan (Journal of Soils and Sediments, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Fisetin Augments OEC Neuroprotection Through Modulating Neurotrophin/Cytokine Signaling and Activating PI3K/Akt/CREB Pathway in an In Vitro Neurodegenerative Injury - Yizhen Jiang; Jianbin Guo; Yan Yang; Lin Li; Peng Deng; Shihao Yuan; Jinchao Wang; Hao Hui; Hao Yang (NeuroMolecular Medicine, 2025)

Watershed runoff as a dominant pathway for mercury loading into a karst lake as unraveled by a novel mercury isotope and flux balance model - Hui Zhang; Xuewu Fu; Xian Wu; Qianwen Deng; Kaihui Tang; Leiming Zhang; Jonas Olof Sommar; Xinbin Feng (Water Research, 2025)

Liquid biopsy-based multi-cancer early detection: an exploration road from evidence to implementation - Yongjie Xu; Sibo Zhu; Changfa Xia; Hui Yu; Si Shi; Kezhong Chen; Yue He; Chuxia Deng; Haoxuan Jin; Jing Liu; Rebecca Fitzgerald; Partha Basu; et al. (Science Bulletin, 2025)

Transcriptional factors AcNAC1/2 synergistically orchestrate kiwifruit chlorophyll degradation - Ying-ying Wu; Shi Wu; Xin-yi Li; Jia-hui Deng; Pu Liu; Wen-qiu Wang; Xue-ren Yin; Xiao-fen Liu (Postharvest Biology and Technology, 2025)

Geospatial environmental sources of inhaled microplastics: A case in Zhuhai, China - Chenghui Zhong; Meiqi Lan; Chunzhao Chen; Lieyang Fan; Hongjie Shen; Mengnan He; Jiajing Wang; Jingwen Fang; Wenfeng Lu; Xiaole Xu; Liqiu Qiu; Shaojuan Wang; et al. (Journal of Hazardous Materials, 2025)

Arsenite-oxidizing chemolithooautotrophic prokaryotes underpin inorganic carbon fixation and arsenic detoxification in deep underground uranium mining layers - Huang Yu; Wenpan Lv; Dexin Ding; Nan Hu; Hui Zhang; Mingfei Chen; Cheng Wang; Qingyun Yan; Ye Deng; Zhili He; Hans K. Carlson; Ruiwen Hu (Journal of Hazardous Materials, 2025)

Myricetin and 2-amino-3-methyl-3H-imidazole [4, 5-F] quinoline triggers liver injury by regulating gut microbiota and liver metabolism - Hongting Deng; Yanan Zhao; Ran Cao; Leyao Chen; Chang Zhang; Hui Teng; Lei Chen (Journal of Hazardous Materials, 2025)

Sodium lignosulfonate alkylates based-biosurfactants for efficient remediation of oily sludge - Yun Ma; Shengqian Wu; Hui Liu; Chuanqi Ren; Yi Xie; Gang Deng; Shuangquan Yao; Xiaocheng Wang; Chengrong Qin (Journal of Environmental Management, 2025)

Quantification of aflatoxin B1 in wheat using a natural pigment sensing array - Hui Jiang; Dengmin Li; Jihong Deng; Quansheng Chen (Food Control, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

Source apportionment and health risks of heavy metals in agricultural soils near mining areas: APCS-MLR and Monte Carlo approaches - Yangfan Zhao; Yinggang Wang; Hao Wu; Hui Wang; Jingpeng Yue; Ziyang Gao; Jinliang Deng; Xiaojun Li (Environmental Geochemistry and Health, 2025)

The gym effect: Unveiling the role of microbial adaptation in organic carbon redistribution and metabolic optimization in anaerobic side-stream reactors - Huanzhong Deng; Chuanhan Chen; Lianpeng Sun; Hui Lu; Miao Wang; Xinzhe Zhu; Chao Yang; Ruo-hong Li (Water Research, 2025)

Hepatoprotective effects of dandelion against AFB1-induced liver injury are associated with activation of bile acid-FXR signaling in chicks - Zhe Peng; Jiang Deng; Ze-Jing Xu; Qin-Jian Niu; Lamesgen Dessalegn; Alainaa Refaie; Lv-Hui Sun; Yan-Ping Feng; Meng Liu (Toxicon, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Synergistic TA/(NH4)2SO4 conditioning for sludge dewatering: Mechanisms of EPS redistribution and hydrophobic enhancement - Jing Deng; Hui Wang; Jiahui Huang; Jie Hu; Zhuoyi Pan; Ruhao Gao; Lei Wang; Dong Xu (Journal of Environmental Management, 2025)

Barium isotope variation during granitic magma differentiation: implications for the discrimination of crystal fractionation and fluid-magma interaction - Nian-Qin Zhang; Kun Zhou; Yi-Xiang Chen; Fang Huang; Xiao-Feng Gu; Lin-Hui Dong; Gengxin Deng; Peng Gao (Geochimica et Cosmochimica Acta, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

A quantitative study on the influencing pathways of aerosol acidity: the non-neglectable role of non-ideality - Hanze Cui; Yaxing Du; Hui Zhang; Mingqi Deng; Qi Zhang; Weihua Chen; Shuzhen Su; Xihua Li; Sayantan Sarkar; Liming Yang; Xuemei Wang; Shiguo Jia (Atmospheric Environment, 2025)

The influence of aerosols on lightning activity in the Pearl River Delta of China - Zebiao Zhang; Tao Deng; Xue Zhang; Hanjie Huang; Guowen He; Chenguang Tang; Lüwen Chen; Jeremy Cheuk-Hin Leung; Hui Xiao; Shanshan Ouyang; Qing Wang; Gongke Rao; et al. (Atmospheric Research, 2025)

Probiotics: A New Approach for the Prevention and Treatment of Cervical Cancer - Hui Li; Zhen Xu; Chaoqi Liu; Jinfang Deng; Ziqin Li; Yongqin Zhou; Zhiying Li (Probiotics and Antimicrobial Proteins, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Pharmaceuticals in drinking water in suburban communities in Chengdu, China: potential risks on the human health - Chong Tang; Shuhong Fang; Hongling Yin; Hui Zhang; Xin Xin; Binqi Yu; Zhuo Zeng; Kangcheng Deng; Yuanhang Zhang; Zhangzhen Wu; Chenchen Zhao; Juan Chen; et al. (Environmental Monitoring and Assessment, 2025)

Diversity, influential factor, and communication network construction of quorum sensing bacteria in global wastewater treatment plants - Yong-Chao Wang; Sen Wang; Ya-Hui Lv; Jia-Yi Wang; Wen-Xuan Yang; Ye Deng; Feng Ju; Can Wang (Water Research, 2025)

Valorization of marine crustacean shells waste via fermentation technology: A comprehensive review on derived value-added compounds and enhancing their industrial applications - Samad Tavakoli; Qing Li; Wenyu Han; Huijuan Zhang; Ma Hui; Luming Deng; Armin Mirzapour Kouhdasht; Yuqing Tan; Yongkang Luo; Hui Hong; Kefeng Wu (Waste Management, 2025)

The efficient separation of apatite and dolomite using sodium dextran sulphate as an eco-friendly depressant: Flotation performances and atom-scale interaction mechanism - Rui Ma; Bingqiao Yang; Bing Deng; Hui Shao; Yimei Xiao; Huihua Luo (Minerals Engineering, 2025)

Soil particles and elevation shape the distribution of prokaryotic communities in Poyang Lake - Yajun Liu; Hui Zhong; Mi Deng; Zeyong Chi; Xiangmin Liu; Rongfu Li; Yongming Wu (Limnologica, 2025)

Colonization time of plastisphere drives the dynamics of organic carbon stability and microbial communities in seagrass bed sediments - Shuailing Hou; Jun Wang; Dan Feng; Dongming Wu; Shiquan Chen; Jinluo Fan; Mingguang Luo; Hui Deng; Xing Yang; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge (Journal of Hazardous Materials, 2025)

Unraveling stress responses of microalgal-bacterial granular sludge when treating ciprofloxacin-laden wastewater - Lan Tang; Chuanyan Zhuang; Peng Qi; Xiaojing Yang; Meng Yan; Fan Li; Qiujin Deng; Lianpeng Sun; Hui Lu (Journal of Hazardous Materials, 2025)

Enhancing the application of near-infrared spectroscopy in grain mycotoxin detection: An exploration of a transfer learning approach across contaminants and grains - Jihong Deng; Congli Mei; Hui Jiang (Food Chemistry, 2025)

Characterization, grass carp (Ctenopharyngodon idella) freshness monitoring and preservation effects of active films incorporated with Solanum nigrum L. anthocyanins - Jianhui Wang; Miao Liu; Disheng Xiao; Lanlan Ouyang; Xiaoyi Hou; Bo Zhang; Na Deng; Hui Li (Food Chemistry, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Operational influence line identification of bridge cable forces using stochastic vehicle-induced responses - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Yi Xia; Ya-Yue Deng (Engineering Structures, 2025)

Unlocking the potential of lignin-activated in-situ char formation for fire-resistant foams - Baojuan Deng; Hui Liu; Yi Xie; Fei Wang; Baojie Liu; Shuangfei Wang; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Chemical Engineering Journal, 2025)

Enhanced lithium-ion diffusion kinetics of silicon anode via in-situ forming high ion conductive Li3N-rich carbon interface derived from g-C3N4 coating - Haoqin Feng; Jiaguo Deng; Yu Liu; Shixiong Mei; Ben Xiang; Xinbo Guo; Jianguo Sun; Hui Zhang; Tao Li; Biao Gao; Kaifu Huo (Chemical Engineering Journal, 2025)

Effects of Wet–Dry Cycles and Acidic Environments on the Mechanical Properties and Microstructure of Silty Mudstone - Junqi Yu; Hui Deng; Songbo He; Linyi Lv (Rock Mechanics and Rock Engineering, 2025)

A new Alternaria (Pleosporales, Pleosporaceae) species in section Infectoriae associated with marigold (Tagetes erecta) from Northern China - Sein Lai Lai Aung; Ya-Nan Gou; Qian Deng; Jia-Hui Huang; Jian-Xin Deng; Yi Zhou (Mycological Progress, 2025)

Influence of sedimentary environment on rock physical properties of saline lacustrine shale: A case study from the upper member of the Lower Ganchaigou Formation - Hui Xia; Ji-xin Deng; Lian-teng Song; Jian-gong Wang; Ping Zhang; Zhong-hua Liu; Hong-liang Wu; Jia-qing Wang; Yan Long-long (Applied Geophysics, 2025)

Conservation implications of mismatched diversity between mangrove plants and benthic mollusks - Lin Zhang; Yamian Zhang; Wei Ma; Hui Zhang; Yijuan Deng; Mao Wang; Wenqing Wang (Journal of Environmental Management, 2025)

Hydroxyapatite combined with phosphate-solubilizing bacteria immobilized of Cd and inhibited the absorption of Cd by lettuce - Ke Wang; Junqing Zhang; Weilin Li; Zhongyan Deng; Randa S. Makar; Lunguang Yao; Hui Han (Journal of Environmental Chemical Engineering, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

Effect of adding Pickering emulsion containing oregano essential oil on the storage quality of Harbin red sausage - Lingyu Yin; Yuhang Cao; Meihui Wang; Yi Deng; Fei Li; Baohua Kong; Qian Liu; Hui Wang (Food Bioscience, 2025)

Insights into mantle metasomatism during oceanic subduction from late Paleozoic (∼260 Ma) high-Mg diorites in the northeastern Tibetan Plateau - Feng-Hui Zou; Jian-Ping Zheng; Cai-Lai Wu; Chang-Qian Ma; Li-Huan Deng (Chemical Geology, 2025)

Do aerosols induce the differences in low cloud frequency between eastern China and eastern United States? - Hui Xu; Jianping Guo; Tianmeng Chen; Yinjun Wang; Jianbo Deng; Bing Tong (Atmospheric Research, 2025)

High-Altitude CO2 Flux in Cropland and Grassland of Eastern Qilian Mountains, China: Variation and Driving Factors - Weiyi Zeng; Hui Hu; Yuan Deng; Huating Jiang; Mi Zhang; Pan Wang; Hao Huang (Water, Air, & Soil Pollution, 2025)

Effect of rhizosphere soil microbial communities and environmental factors on growth and the active ingredients of Angelica sinensis in Gansu Province, China - Zuhua Yan; Hui Jin; Xiaoyan Yang; Deng Min; Xinxin Xu; Cuiping Hua; Bo Qin (Folia Microbiologica, 2025)

Travel Behaviors of Hand-Foot-and-Mouth Disease Patients Across Hospital Service Areas in Nanchang City, China - Zeliu Zheng; Wentao Song; Hui Li; Zhiqiang Deng; Bisong Hu; Yuxia Wang; Fahui Wang (Chinese Geographical Science, 2025)

Genome-wide identification of CYP450 in Ganoderma lucidum and expression analysis of genes related to ganoderic acid synthesis - Xiaolu Li; Dong Liu; Bangxing Han; Shiping Huang; Hui Deng (Archives of Microbiology, 2025)

Application of scattering image wavelet transform in cave recognition: A case study on a bedrock buried hill reservoir in Bongor Basin, Chad - Yu-Jiang Xiao; Tao Song; Li-Deng Gan; Yan Zhang; Wen-Hui Du; Xing-Yan Fan; Xiao-Feng Dai (Applied Geophysics, 2025)

Alkaloids and lignans isolated from Alisma orientale exhibit anti-pulmonary fibrosis activities by modulating an apoptotic signaling pathway - Deng-Hui Zhu; Jing-Ke Zhang; Peng-Li Guo; Si-Qi Tao; Meng-Nan Zeng; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Deep learning-based inversion framework for fractured media characterization by assimilating hydraulic tomography and thermal tracer tomography data: Numerical and field study - Cihai Chen; Yaping Deng; Jiazhong Qian; Haichun Ma; Lei Ma; Jichun Wu; Hui Wu (Engineering Geology, 2025)

PdRh bimetallic-loaded α-Fe2O3 nanospindles with Ppb-limit of 3-hydroxy-2-butanone biomarker detection: Particle dimension regulation and oxygen spillover effect - Xing-Yu Wang; Ping-Ping Liu; Hai-Jie Cai; Miao-Miao Li; Chun-Hui Deng; Yong Zhao; Zhao-Huan Zhang; Yong-Heng Zhu (Chemical Engineering Journal, 2025)

Temperature-tuned dual-selective NO2/diisopropylamine sensor based on (NH4)0.33WO3 doped γ-WO3 nanosheets-assembled hollow microspheres via simple pyrolysis of commercial ammonium metatungstate - Guo-Li Chen; Hui-Ye Jiang; Yan Jiang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2025)

Investigation on fluorescence enhancement of DNA tetrahedral structures modified DNA-silver nanoclusters for biosensing - Boyuan Jia; Xuesong Li; Xinyu Wang; Yanyan Lu; Hui Meng; Xinshuo Zhang; Xiangyang Wu; Zhen Zhang; Yibin Deng (Chemical Engineering Journal, 2025)

The differential partition of copper in cell wall and symplastic space contributes to the natural variation of copper toxicity tolerance in rice - Jin Zhang; Yuan Qin; Xuan Chen; Nayun Xiao; Wei Jiang; Haiyang Tang; Hui Zhou; Xianjin Qiu; Jianlong Xu; Fanrong Zeng; Zhong-Hua Chen; Guang Chen; et al. (Plant and Soil, 2025)

Stability evaluation of columnar perilous rock in the Three Gorges Reservoir area based on UAV tilt photography - Linfeng Wang; Ning Tang; Hui Jiang; Huafeng Deng; Zhizhong Yang; Bo Cai (Bulletin of Engineering Geology and the Environment, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Failure Characteristics and Control Strategies of Overlying Remaining Coal Pillars in Close-Distance Coal Seam Mining - Wei-guang Ren; Hui Yuan; Zhi-gang Deng; Yun-peng Li; Wen-xin Li (Applied Geophysics, 2025)

Biostimulants accelerate lignin degradation in semi-aerobic landfills, assisting overall lifecycle management and sustainable development of landfills - Mingxing Li; Hui Jiang; Ruiding Li; Lifeng Liu; Wendong Liu; Yong Xie; Wenchan Wu; Xing Li; Yulan Chen; Quan Deng; Zhongping Qiu (Journal of Cleaner Production, 2025)

Solar steam generation system with photothermal-electrothermal synergistic evaporation and efficient salt-resistance concurrently - Di Wang; Shuai Wang; Hui Deng; Tianle Tan; Guangxv Liu; Zilong Liu (Journal of Environmental Chemical Engineering, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Duality of supercritical water pressure on phenol gasification studied by metadynamics simulation and experimental - Deng Zhao; Xuetong Li; Wei Luo; Qingxin Li; Wenming Han; Huashan Wang; Hua Liu; Hui Liu; Shuai Guo; Jiajing Kou (Fuel, 2025)

Optimized two-step flash chromatography method for large-scale isolation of linusorb and its antioxidant capacity evaluation - Jun-le Li; Jia-hui Yu; Wan-zen Li; Du-jian Deng; Yue Xin; Martin J.T. Reaney; Zi-zhe Cai; Yong Wang (Food Research International, 2025)

Enhanced stability of anthocyanins and phages by titanium dioxide-loaded cyclodextrin-metal organic frameworks: Application as a cherry tomato preservative - Jisi Deng; Hui Shi (Food Bioscience, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Controlled-release phosphate fertilizer improves soil fertility and soybean productivity by regulating soil microbial diversity and composition and increasing enzyme activities - Zhaoming Qu; Qi Chen; Hao Deng; Qin Wang; Shuihong Yao; Qianhui Chen; Hui Dong; Yanli Liu; Haojie Feng; Chengliang Li (Field Crops Research, 2025)

Ruthenium-doped carbon dots with “three-in-one” chemodynamic, photodynamic, and photothermal activity induce panoptosis for tumor therapy - Xiaokang Lu; Weijie Sun; Xingye Zheng; Lishen Yang; Tan Feng; Xiaoqin Deng; Fengqi Zhou; Hongmin Zhu; Ding Ma; Bilian Li; Guobao Ning; Hang Chen; et al. (Chemical Engineering Journal, 2025)

A glycogen synthase kinase-3 gene enhances grain yield heterosis in semi-dwarf rapeseed - Li Bao; Liu Xinhong; Yang Qian; Zhang Hui; Tan Wenqing; Yan Mingli; Deng Lichao; Li Mei; Qu Liang; Guo Yiming (Plant Molecular Biology, 2025)

Social cost of carbon under endogenous social adaptation - Huai Deng; Huan Wu; Hui Xu (Climatic Change, 2025)

Evaluating the Impact of an Organic Trace Mineral mix on the Redox Homeostasis, Immunity, and Performance of Sows and their Offspring - Shao-Qing Wang; Zhe Peng; Hua Sun; Yan-Ming Han; Bo Zhang; Lane Pineda; Gavin Boerboom; Lv-hui Sun; Ying Liu; Zhang-Chao Deng (Biological Trace Element Research, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Characterization of emulsion co-encapsulated with probiotics and quercetin and its effect on the storage quality of Harbin red sausage - Yuhang Cao; Lingyu Yin; Fei Li; Yi Deng; Baohua Kong; Qian Liu; Hao Wang; Hui Wang (Meat Science, 2025)

Novel production of ultrafine particles to meet environmental and energy sustainability - Yimin Deng; Hui Luo; Liju Bai; Xianfeng Fan; Jan Baeyens (Journal of Environmental Management, 2025)

A chemically enhanced primary treatment and anammox-based process for sustainable municipal wastewater treatment: The advantage and application prospects - Ruolan Wen; Jiayuan Deng; Huan Yang; Yu-You Li; Hui Cheng; Jianyong Liu (Journal of Environmental Management, 2025)

Qualitative and quantitative analysis of mineral oil pollution in peanut oil by Fourier transform near-infrared spectroscopy - Jihong Deng; Hui Jiang; Quansheng Chen (Food Chemistry, 2025)

Periodic straw-derived biochar improves crop yield, sequesters carbon, and mitigates emissions - Feng Chang; Shanchao Yue; Shuai Li; Hui Wang; Yafei Chen; Wenjia Yang; Bingyan Wu; Haini Sun; Shiwen Wang; Lina Yin; Xiping Deng (European Journal of Agronomy, 2025)

Macrophage-targeted, ROS-removing and H2S-releasing nanomicelle encapsulated in hydrogel microspheres for the treatment of osteoarthritis - Jun Tao; Hui Deng; Zhengnan Li; Liping Cao; Yanfei Rao; Zhanhai Yin (Chemical Engineering Journal, 2025)

Hijacking the hyaluronan assisted iron endocytosis to promote the ferroptosis in anticancer photodynamic therapy - Hong Deng; Jiayu Chen; Huimin Wang; Runmeng Liu; Yiyi Zhang; Hui Chang; Ching-Hsuan Tung; Weiqi Zhang (Carbohydrate Polymers, 2025)

Comprehensive cultivation of the broiler gut microbiota guides bacterial isolation from chickens - Zhang-Chao Deng; Ke-Xin Cao; Yu-Xuan Huang; Zhe Peng; Ling Zhao; Dan Yi; Meng Liu; Lv-Hui Sun (Science China Life Sciences, 2025)

Novel recycling strategy for distillers’ grains waste: prolonged biochar aging promotes cadmium immobilization and lettuce growth by regulating soil nutrient availability and bacterial composition - Jieming Li; Yu Zhao; Guoren Xu; Suyi Zhang; Bo Deng; Pan Song; Hui Qin (Plant and Soil, 2025)

Tracking the geographical distribution of the Asian citrus psyllid Diaphorina citri throughout China using mitogenomes and endosymbionts - Fengnian Wu; Zehan Dai; Min Shi; Jianjian Huang; Hui Zhu; Yuzhong Zheng; Zikai Chen; Xiuhong Li; Xiaoling Deng; Eduardo G. P. Fox (Journal of Pest Science, 2025)

Physiological, transcriptomic, and metabolomic analyses reveal the adaptation mechanism of Betaphycus gelatinus under different salinity conditions - Hui Tian; Yongqiu Deng; Kangtai Liao; Siqi Xu; Jihong Chen; Linwen He (Algal Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Degradation of ofloxacin by activation of persulfate with metal-N co-doped modified peanut shell biochar: The key role of cobalt doping - Wei Qian; Yi-Li Deng; Xiao-Long Liu; Hui Liu; Mao-You Ye; Ying-Ying Li; Yong-Zheng Zhang; Zeng-Hui Diao; Jia-Lin Liang (Journal of Water Process Engineering, 2025)

Preparation and characterization of pickering emulsions stabilized by zein/quercetin/quaternary ammonium chitosan composite nanoparticles with antibacterial effect - Lingyu Yin; Yuhang Cao; Yi Deng; Fei Li; Baohua Kong; Qian Liu; Hui Wang (Journal of Food Engineering, 2025)

Morphology effect on the photocatalytic performance of CeO2 and insights into the degradation mechanism of tetracycline - Saisai Deng; Hui Wang; Yanmei Dong; Wenjing Cheng; Xiangang Lin; Longxia Wu; Jun Hu; Yuanxu Liu; Yangyang Li (Journal of Environmental Chemical Engineering, 2025)

Genome and transcriptome analysis of the lignite-degrading Trichoderma cf. simile WF8 strain highlights potential degradation mechanisms - Jinghua Yao; Yajuan Chen; Deyu Zhuo; Siqiao Chen; Baichao Xu; Congwei Yan; Wanrong Li; Hui Feng; Sheng Deng; Feng M. Cai; Andrei S. Steindorff; Irina S. Druzhinina; et al. (International Biodeterioration & Biodegradation, 2025)

Nanofibrous perovskite La0.35Pr0.15Sr0.5Fe0.8Ti0.2O3-δ as cathode for solid oxide fuel cells - Yinzhuo Jia; Ke Deng; Zhe Zhang; Qi Wang; Hui Fan (Fuel, 2025)

The surface gradient doping of Sn enables CuO high selectivity for electro-reducing CO2 to HCOOH - Mengmeng Zhang; Xu Chen; Hui Xue; Zhijia Zhang; Yang Wang; Yifang Zhang; Yida Deng; Yong Jiang (Fuel, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Determination of aflatoxin B1 in peanuts based on millimetre wave - Leijun Xu; Zhenshuo Chen; Xue Bai; Jihong Deng; Xiang Zhao; Hui Jiang (Food Chemistry, 2025)

Physicochemical and digestive properties of curcumin stabilized by quaternized chitosan/sodium alginate nanoemulsion coatings - Ying-ao Zhu; Yi Deng; Pengyuan Sun; Yuhang Cao; Baohua Kong; Qian Liu; Hui Wang; Qian Chen (Food Chemistry, 2025)

Integrating knowledge-data-driven method to predict load-displacement curve on a trapdoor - Hui Zeng; Xing-Tao Lin; Deng Wang; Xiangsheng Chen; Dong Su; Ruidi Chen; Wei Liu (Computers and Geotechnics, 2025)

Integrating Ni2P crystalline-NiFeBP amorphous heterojunction nanosheets on hierarchical nickel foam for superior overall water splitting - Guang-Lan Li; Fei Deng; Tian-Ge Ma; Yu-Hui Shi; Junyan Liu; Yang Yan; Qing Mao; Junjiang Bao (Chemical Engineering Journal, 2025)

Dynamics of soil and foliar phosphorus fractions in a secondary tropical forest under altered seasonal precipitation patterns - Xiaofang He; Dafeng Hui; Faming Wang; Qi Deng; Zhanfeng Liu; Hongfang Lu; Kuncun Yao; Hai Ren; Jun Wang (Plant and Soil, 2025)

Publisher Correction: An automatic methodology for lithology identification in a tight sandstone reservoir using a bidirectional long short-term memory network combined with Borderline-SMOTE - Chong Hu; Rui Deng; Xueyi Hu; Mengcheng He; Hui Zhao; Xuemeng Jiang (Acta Geophysica, 2025)

Efficacy of radiotherapy in treating local recurrence concomitant with distant metastasis of nasopharyngeal carcinoma: a long-term retrospective multicenter study - Lu Li; Mingyou Deng; Jianlan Ren; Wenjun Liao; Liangjian Zheng; Hui Ma; Jinyi Lang; Mei Feng; Yangkun Luo (Clinical & Experimental Metastasis, 2025)

Modeling the Hydrodynamic Pressure Field and Wake Field Characteristics of an Underwater Vehicle and Studying Their Correlation - Peihao Li; Hui Deng; Bingrui Xu; Weixue Xia; Wenbin Yi (Journal of Marine Science and Engineering, 2025)
The hydrodynamic pressure field and wake field generated by an advancing underwater vehicle are used as key factors for its detection and identification. In this paper, a numerical method is established based on the Reynolds-averaged Navier–Stokes equation. Following grid convergence verification for seven kinds of grids, the differences between the hydrodynamic pressure field and wake field are investigated using the gridding method and turbulence model. Subsequently, on a validation basis, the characteristics and correlation of the hydrodynamic pressure field and wake field for an underwater vehicle at different water depths are studied, showing that the SST turbulence model is applicable to underwater vehicle hydrodynamic pressure fields with low grid requirements. A high grid density and the LES turbulence model are needed to accurately capture information about the wake field’s flow field. As the underwater vehicle approaches the bottom, the hydrodynamic pressure field characteristics change significantly, and the wake field characteristics do not significantly change. In the region behind the hull, the influence of the wake field on the hydrodynamic pressure field is complex, but it has a short acting distance. The correlation in the area behind the hull is crucial for identifying, detecting, and tracking targets.

Beneficial effects of Haematococcus pluvialis on growth and hepatopancreas health status in crayfish (Procambarus clarkii) via remodeling the gut microbial metabolic functions - Aimin Wang; Wenjie Hui; Xin Deng; Hongyan Tian; Wuxiao Zhang; Silei Xia; Fei Liu; Wenping Yang; Yebing Yu; Bo Liu; Peng Shao; Aimin Zhu (Aquaculture, 2025)

Spatial behaviors of HFMD hospital visits across regions of various urbanicity levels in Nanchang, China - Zeliu Zheng; Wentao Song; Hui Li; Zhiqiang Deng; Bisong Hu; Yuxia Wang; Fahui Wang (Travel Behaviour and Society, 2025)

Enhanced sludge solid-liquid separation based on Fe2+/periodate conditioning coupled with polyoxometalates: Cell destruction and protein adsorption - Jing Deng; Hui Wang; Ruhao Gao; Xin Ma; Minjie Chen; Dong Xu; Anhong Cai (Journal of Environmental Management, 2025)

Effect of active site size in dispersed MoS2 nanocatalysts on slurry-phase hydrocracking of residue - Hui Luo; Cheng Ding; Siqi Yin; Wenan Deng; Chuan Li; Wenlong Cui; Feng Du (Fuel, 2025)

Corrigendum to “Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums” [Food Chem. 458 (2024) 140093] - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2025)

Changes in meat quality of Esox Lucius during postmortem storage: Based on the lysosomal-mitochondrial apoptotic pathway - Hui Li; Xuemei Fan; Xin Guo; Wenbo Yan; Xinyao Yu; Xiaorong Deng; Jian Zhang (Food Chemistry, 2025)

Dietary sn-2 palmitate influences cognitive behavior by increasing the transport of liver-produced lysophosphatidylcholine VLCPUFAs to the brain - Teng Wei; Yangzheng He; Dengfeng Tan; Xiaoling Zeng; Yanmei Hou; Jiaqi Wang; Hui Jiang; Zeyuan Deng; Jing Li (Food Chemistry, 2025)

Experimental assessment of ozonated ice: Preparation, stability, and preservation effects on shrimp (Metapenaeus ensis) - Hui Li; Chenghao Yuan; Sixie Li; Yongjian Cai; Na Deng; Tianci Liao; Miao Liu; Jianhui Wang (Food Control, 2025)

High-precision detection of dibutyl hydroxytoluene in edible oil via convolutional autoencoder compressed Fourier-transform near-infrared spectroscopy - Jihong Deng; Zhenyu Chen; Hui Jiang; Quansheng Chen (Food Control, 2025)

Research on systematic analysis and optimization method for ice storage cooling system based on model predictive control: A case study - Wenbo Qiang; Ying Liao; Jiewen Deng; Chenwei Peng; Huier Long; Hecheng Yang; Jie Bai; Yangyang Su; Qingpeng Wei; Xinhua Xu; Xiaoliang Tang; Hui Zhang (Energy and Buildings, 2025)

Adoptive Treg therapy using chitosan conduits/self-assembled peptide hydrogels for enhanced immunomodulation and peripheral nerve regeneration - Yuan Feng; Xiaomin Yao; Yuyang Ma; Yuhui Jiang; Xueying Zhao; Hui Deng; Xiu Dai; Jing Jie; Weiwei Wang; Yumin Yang; Pengxiang Yang (Chemical Engineering Journal, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Dynamic transport of Zn2+ in ionic liquid intercalated V2O5 cathode for high-performance aqueous Zn-ion batteries - Wenzhe Su; Zanyu Chen; Xingkai Wang; Peng Cui; Minjie Yao; Hui Sun; Hong Zhang; Yida Deng; Xiaopeng Han; Wenbin Hu (Chemical Engineering Journal, 2025)

Temperature-controlled construction of honeycomb-ordered structure in layered Li2Ir0.6Ni0.4O3 to enhance the anionic redox activity and stability - Jianwen Wang; Long Gu; Chao Wang; Wencheng Su; Yuying Zhang; Huiyan Zeng; Liting Deng; Xueliang Li; Wenjing Li; Hui Ying Yang; Chunzhen Yang (Chemical Engineering Journal, 2025)

Structural characterization and antioxidant activity mechanism of the ferulic acid-rich subfraction from sugar beet pectin - Chunhong Xiang; Hui Teng; Zhili Sheng; Chao Zhao; Jingteng Deng; Chengang Zhao; Bo He; Lei Chen; Chao Ai (Carbohydrate Polymers, 2025)

Rice intercropping with water mimosa (Neptunia oleracea Lour.) could alleviate the negative effects of simulated nitrogen deposition on rice and soil - Yu-Hao Deng; Ji-Dong Liao; Ze-Wen Hei; Kai-Ming Liang; Hui Wei; Jia-En Zhang; Hui-Min Xiang (Plant and Soil, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

In-situ nucleic acid amplification induced by DNA self-assembly for rapid and ultrasensitive detection of miRNA - Hongfei He; Xuewen Zhang; Meng Deng; Yan Zhou; Hongwei Pang; Hui Yang; Jiazhen Lyu; Yuxin Feng; Xiangqin Geng; Xiaolan Guo; Guangcheng Luo; Bin Guo (Analytica Chimica Acta, 2025)

An automatic methodology for lithology identification in a tight sandstone reservoir using a bidirectional long short-term memory network combined with Borderline-SMOTE - Chong Hu; Rui Deng; Xueyi Hu; Mengcheng He; Hui Zhao; Xuemeng Jiang (Acta Geophysica, 2024)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Sedimentary antimony stable isotope record of anthropogenic contamination in a karst lake in southwestern China - Qianwen Deng; Xian Wu; Hui Zhang; Yunjie Wu; Kaihui Tang; Ye Sun; Guangyi Sun; Heng Yao; Jonas Olof Sommar; Xuewu Fu; Xinbin Feng (Science of The Total Environment, 2024)

Adverse effects of microplastics on the growth, photosynthesis, and astaxanthin synthesis of Haematococcus pluvialis - Weibin Zhao; Jiaye Deng; Jiamei Wang; Chengjun Ge; Hui Yang (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Numerical analysis of FPSO mooring dynamic tension and its fatigue damage under a simplified coupled method considering structural elastic deformation - Chunlei Liu; Hui Li; Ruixiang Liu; Jian Zou; Baoli Deng; Lin Lu (Ocean Engineering, 2024)

Arsenic mobilization and nitrous oxide emission modulation by different nitrogen management strategies in a flooded ammonia-enriched paddy soil - Feng WANG; Jing ZHANG; Yanqiong ZENG; Honghui WANG; Xiyu ZHAO; Yilin CHEN; Huanhuan DENG; Liyun GE; Randy A. DAHLGREN; Hui GAO; Zheng CHEN (Pedosphere, 2024)

Spatial distribution and migration characteristics of heavy metals at an abandoned industrial site in the Southwest of China - Jiayi Deng; Jingyang Yu; Xingtao Wang; Dong Yu; Hui Ma; You Wu; Chenglong Yu; Shengyan Pu (Journal of Hazardous Materials, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

Designing carbon-based catalysts for enhanced sulfite activation: Strategies for pollutant degradation - Xiaowen Jiang; Shuyan Guan; Linfeng Chen; Fengxia Deng; Hui Yan; Fengyang Liu; Xuedong Zhai; Carlos A. Martínez-Huitle; Jing Ding (Journal of Environmental Chemical Engineering, 2024)

Nutrient changes from Zhoushan coastal upwelling fluctuations since 1900 and its implications for fisheries - Meiqun Xiao; Bing Deng; Guosen Zhang; Hui Wu; Yuanyuan Chen; Lijun Hou (Global and Planetary Change, 2024)

Characterization, antibacterial and snakehead fish (Channa argus) preservation effects of active films infused with compounded cinnamon and thyme essential oils - Na Deng; Shaoqing Wang; Disheng Xiao; Hui Li; Changzhu Li; Zhihong Xiao; Fang Fang; Miao Liu; Jianhui Wang (Food Packaging and Shelf Life, 2024)

Thermal comfort and adaptation in the temperate zone and the effects of thermal history: A tracking survey field study - Hui Zhao; Wenjie Ji; Shihan Deng; Zhihao Wang; Shuli Liu (Energy and Buildings, 2024)

Formation of interior hollow nanocubes derived from cobalt-based metal-organic frameworks via one-step etching for efficient battery desalination - Chengbo Kou; Sareh Vafakhah; Tianchen Li; Guorui Deng; Lei Zhu; Wen Ji; Liping Yang; Chengding Gu; Meng Ding; Lu Guo; Hui Ying Yang (Desalination, 2024)

Rational design of hierarchical defect-rich NiSe2/Se-NiCuOx heterostructures: Modulating electronic structure for exceptional ammonia oxidation performance - Guang-Lan Li; Tian-Ge Ma; Yu-Hui Shi; Fei Deng; Ri-Yang Huang; Yang Yan; Qing Mao; Yushan Li; Yonghou Xiao (Chemical Engineering Journal, 2024)

Double-network conductive hydrogel for non-contact respiratory monitoring - Shuhang Deng; Xiaoran Ming; Guilong Yan; Li Wang; Zhenyu Li; Jingyu Chen; Jingjuan Lai; Dong Li; Dong Xiang; Chunxia Zhao; Hui Li; Xuezhong Zhang; et al. (Chemical Engineering Journal, 2024)

The mechanism of plasma affecting biomass pyrolysis to more H2, activated char and less CO2 - Deng Zhao; Yongxiang Liang; Lei Gou; Yalu Cui; Huashan Wang; Chunsheng Wang; Hui Liu; Shuai Guo; Suning Li (Chemical Engineering Journal, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Macrophage activation syndrome in Sepsis: from pathogenesis to clinical management - Shunyao Chen; Cong Zhang; Jialiu Luo; Zhiqiang Lin; Teding Chang; Liming Dong; Deng Chen; Zhao-Hui Tang (Inflammation Research, 2024)

Ensemble Machine Learning and Predicted Properties Promote Antimicrobial Peptide Identification - Guolun Zhong; Hui Liu; Lei Deng (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Metformin Protects Against Acute Kidney Injury Induced by Lipopolysaccharide via Up-Regulating the MCPIP1/SIRT1 Pathway - Wen-long Zhang; Long-jun Zhang; Piao Liang; Hui-long Fang; Xiao-li Wang; Yan-juan Liu; Hua-fei Deng (Biochemical Genetics, 2024)

Insights into the role of electrochemical stimulation on sulfur-driven biodegradation of antibiotics in wastewater treatment - Haoting Quan; Yanyan Jia; Huiqun Zhang; Fahui Ji; Yongsen Shi; Qiujin Deng; Tianwei Hao; Samir Kumar Khanal; Lianpeng Sun; Hui Lu (Water Research, 2024)

Soil aggregate size distribution mediates microbial responses to prolonged acid deposition in a subtropical forest in south China - Jianping Wu; Xin Xiong; Dafeng Hui; Huiling Zhang; Jianling Li; Zhongbing Chang; Shuo Zhang; Yongxian Su; Xueyan Li; Deqiang Zhang; Qi Deng (Soil Biology and Biochemistry, 2024)

Evaluation of groundwater quality with multi-source pollution based on source identification and health risks - Dong Yu; Jiayi Deng; Qing Jiang; Hanshuang Liu; Chenglong Yu; Hui Ma; Shengyan Pu (Science of The Total Environment, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Hierarchically porous and flexible chitin-fiber/melamine-sponge composite filter with high-loading of PdAu nanoparticles for effective hydrodechlorination of chlorophenols - De-Chang Li; Zhengbin Tian; Xianliang Huang; Wan Zhang; Wenquan Wang; Qian Zhang; Xiaohui Deng; Guang-Hui Wang (Journal of Hazardous Materials, 2024)

De-noising magnetotelluric data based on machine learning - Tuanfu Gui; Juzhi Deng; Guang Li; Hui Chen; Hui Yu; Min Feng (Journal of Applied Geophysics, 2024)

Chemometrics and sensomics-assisted identification of key odorants responsible for retort odor in shelf-stored green tea infusion: A case study of Biluochun - Jie-Qiong Wang; Ying Gao; Zhi-Hui Feng; Si-Han Deng; Jian-Xin Chen; Fang Wang; Yi-Fan Li; Ying-Bin Zhang; Jun-Feng Yin; Liang Zeng; Wei-Biao Zhou; Yong-Quan Xu (Food Research International, 2024)

Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2024)

Exploring the mechanism of alkali metal K-catalyzed biomass char gasification using in-situ DRIFTS and molecular simulation - Deng Zhao; Yu Wang; Guanwei Wang; Wenming Han; Hua Liu; Huashan Wang; Hui Liu; Shuai Guo (Chemical Engineering Journal, 2024)

Effects of labyrinth-like path designs on mitigating stress response to traffic noise - Li Deng; Hope Hui Rising; Chao Gu; Anju Bimal (Building and Environment, 2024)

Sialyl Lewis X decorated integrin α3 on small extracellular vesicles promotes metastasis of bladder cancer via enhancing vascular permeability - Hui Feng; Liang Liang; Wenli Deng; Jiaojiao Gao; Xiang Li; Feng Guan (Angiogenesis, 2024)

Nutrient regeneration patterns for initiating and maintaining algae blooms-a case study of in Lake Taihu - Hui Li; Yingying Cai; Huatang Deng; Zhenhua Qin; Jianfen Li; Xiuyun Cao; Yiyong Zhou; Chunlei Song; XinBin Duan (Chemosphere, 2024)

Corrigendum to ``Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions'' [Water Research 261 (2024) 122054] - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

Mycorrhizal association controls soil carbon-degrading enzyme activities and soil carbon dynamics under nitrogen addition: A systematic review - Yuanliu Hu; Ji Chen; Jørgen E. Olesen; Kees Jan van Groenigen; Dafeng Hui; Xinhua He; Guoyin Chen; Qi Deng (Science of The Total Environment, 2024)

Effect of plant roots on the radiocarbon age of loess deposits in arid central Asia - Leibin Wang; Huizhen Deng; Hui Zhao; Huan Xia; Aifeng Zhou; Qiang Wang; Fahu Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Highly efficient recovery of lithium from spent ternary NCM cathode materials via a selective chlorination method - Wan-Jing Yu; Yi Li; Bochuan Deng; Jing Wang; Gaoqiang Mao; Hui Tong; Hanbing He; Xueyi Guo (Journal of Environmental Chemical Engineering, 2024)

Simultaneous extraction of five heavy metal ions from root vegetables via dual-frequency ultrasound-assisted enzymatic digestion - Min Yuan; Xinyan Huan; Xiaojun Yang; Menghan Fan; Jiaqi Yin; YingQing Ma; Bo Deng; Hui Cao; Yiyi Han; Fei Xu (Food Chemistry, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

On-demand detachable and reuseable adhesives assembled by organic-silicon nanogels with wide applicability and excellent harsh-environment resistance - Hui Rong; Pengwei Zhao; Manhua Lu; Liandong Deng; Shuangyang Li; Xiaobin Fan; Zhanpeng Ye; Jianhua Zhang; Anjie Dong (Chemical Engineering Journal, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

An improved monitoring strategy for shallow rainfall-induced landslides under critical site-specific recognition - Fei Wang; Fei Chen; Hui Deng; Jianjun Zhao; Jibin Chen; Wei Xu; Qiangwei Zeng (Landslides, 2024)

Nomogram to predict central lymph node metastasis in papillary thyroid carcinoma - Dehui Qiao; Xian Deng; Ruichen Liang; Xu Li; Rongjia Zhang; Zhi Lei; Hui Yang; Xiangyu Zhou (Clinical & Experimental Metastasis, 2024)

A study of rock mass properties based on discrete fracture network modeling and compression damage process - Ming Li; Hui Deng; Guoxing Tu (Bulletin of Engineering Geology and the Environment, 2024)

Bioturbation coefficients and organic carbon degradation rates of deep-sea sediments in the central-eastern tropical Pacific - Feng Lin; Cai Lin; Xiuwu Sun; Hui Lin; Li Lin; Fangfang Deng; Kaiwen Tan; Peng Lin (Acta Oceanologica Sinica, 2024)

Effects of Dietary Supplementation of Zinc Oxide Quantum Dots on Growth Performance and Gut Health in Broilers - Lei Shi; Meng-Ling Ruan; Bing-Bing Zhang; Guo-Xin Gong; Xue-Wu Li; Alainaa Refaie; Lv-Hui Sun; Zhang-Chao Deng (Biological Trace Element Research, 2024)

Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

A comparison of preferential flow characteristics and influencing factors between two soils developed in the karst region of Southwest China - Hui Wei; Yuanfeng Yang; Jianyu Wang; Qingmei Meng; Yusong Deng (Soil and Tillage Research, 2024)

Impact of Apis cerana cerana (Hymenoptera: Apidae) body size on newly built cell size - Hui Li; Shangkao Deng; Qingxin Meng; Shunhua Yang; Wutao Jiang; Wenzheng Zhao; Yakai Tian; Kun Dong; Xueyang Gong (Journal of Asia-Pacific Entomology, 2024)

Preparation of amorphous coal-based activated coke via a two-step process of carbonization and steam activation - Xiaoling Jin; Hui Wang; Hong An; Xiaoming Huang; Wenyan Zhang; Lei Deng; Defu Che (Fuel, 2024)

A review of dynamic thermal comfort influenced by environmental parameters and human factors - Hui Zhao; Wenjie Ji; Shihan Deng; Zhihao Wang; Shuli Liu (Energy and Buildings, 2024)

Efficient removal of lead from polluted paddy soil by one-pot synthesized Nano-Fe3O4 incorporated stable lignin hydrogel - Deyun Li; Ziyao Li; Xiujiao Wei; Tian Hu; Jianbin Deng; Mingkai Zhang; Hui-juan Xu; Wenyan Li; Jinjin Wang; Yongtao Li; Yulong Zhang (Chemical Engineering Journal, 2024)

Design of robust fluorinated interpenetrating poly(thieno[3,2-b]thiophene) network for highly stable flexible electrochromic-supercapacitor devices - Chunhui Du; Hui Li; Ge Zhang; Rongtai Wan; Wanyi Zhang; Xuejiao Xu; Lu Zheng; Xukun Deng; Jingkun Xu; Baoyang Lu; Guangming Nie (Chemical Engineering Journal, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Survey of mosquito species in intensive pig farms in Hunan province, China - Yu Zhuo; Le-Yan Li; Yu Zhang; Xue-Ling Zhang; Jin-Hui Liu; Yuan-Ping Deng; Guo-Hua Liu (Tropical Animal Health and Production, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Influence of arbuscular mycorrhizal fungi on root foraging and competitive ability depends on soil phosphorus distribution: evidence from two pairs of invasive and native plants - Na-Na Yao; Ao Liu; Xiao-Jing Wang; Hao-Hui Deng; Sheng-Qi Fan; Hai-Jie Zhang; Hui-Xuan Liao; Shao-Lin Peng; Bao-Ming Chen (Applied Soil Ecology, 2024)

Assessment of soil-groundwater nitrogen cycling processes in the agricultural region through flux model, stable isotope - Yuandong Deng; Xueyan Ye; Jing Feng; Hui Guo; Xinqiang Du (Journal of Hydrology, 2024)

Constructing highly active vanadyl species for efficient selective catalytic reduction of NO - Chunxi Lin; Zhihua Lian; Weidong Huang; Qiang Wang; Hui Zhang; XiaoFeng Liu; Feng Deng; Xiaoyan Shi; Wenpo Shan; Hong He (Journal of Environmental Chemical Engineering, 2024)

Stability of tryptophan-containing LOs in flaxseed oil and their response towards γ-tocopherol - Wan-zhen Li; Zi-liang Song; Jun-le Li; Jia-hui Yu; Du-jian Deng; Xiao-qing Cai; Martin J.T. Reaney; Zi-zhe Cai; Yong Wang (Food Chemistry, 2024)

Cytogenetic identification and molecular mapping for the wheat-Thinopyrum ponticum introgression line with resistance to Fusarium head blight - Xiaoying Yang; Xiaofang Cheng; Guangyi Wang; Siyuan Song; Xu Ding; Hui Xiong; Changyou Wang; Jixin Zhao; Tingdong Li; Pingchuan Deng; Xinlun Liu; Chunhuan Chen; et al. (Theoretical and Applied Genetics, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Teacher-student guided knowledge distillation for unsupervised convolutional neural network-based speckle tracking in ultrasound strain elastography - Tianqiang Xiang; Yan Li; Hui Deng; Chao Tian; Bo Peng; Jingfeng Jiang (Medical & Biological Engineering & Computing, 2024)

Electrochemical activation of peroxymonosulfate facilitated by a stainless-steel scrubber cathode: Transition from non-radical to radical pathway mediated by iron leaching - Danni Deng; Zhi Liu; Shiwei Xie; Hui Hong; Ze Liu (Journal of Water Process Engineering, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

AP-1 and SP1 trans-activate the expression of hepatic CYP1A1 and CYP2A6 in the bioactivation of AFB1 in chicken - Jiang Deng; Jia-Cheng Yang; Yue Feng; Ze-Jing Xu; Kamil Kuča; Meng Liu; Lv-Hui Sun (Science China Life Sciences, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Picea pungens exhibits greatest tolerance to short-time thermal stress compared to Picea abies, and Picea omorika - Fangqun Ouyang; Meng Sun; Xia Cui; Mulualem Tigabu; Hui Zhang; Junyu Deng; Junhui Wang; Yu Wei; Ran He (New Forests, 2024)

Rhizophagus Irregularis regulates flavonoids metabolism in paper mulberry roots under cadmium stress - Shuiqing Deng; Lan Pan; Tong Ke; Jingwei Liang; Rongjing Zhang; Hui Chen; Ming Tang; Wentao Hu (Mycorrhiza, 2024)

Plastome structure, phylogeny and evolution of plastid genes in Reevesia (Helicteroideae, Malvaceae) - Li-Yang Geng; Tian-Yi Jiang; Xin Chen; Qiang Li; Jian-Hui Ma; Wen-Xiang Hou; Chen-Qian Tang; Qin Wang; Yun-Fei Deng (Journal of Plant Research, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Characterisation of flavour profiles and microbial communities of fermented peppers with different fermentation years by combining flavouromics and metagenomics - Miao Liu; Na Deng; Xiaoyi Hou; Bo Zhang; Hui Li; Jianhui Wang (Food Chemistry, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

What’s the typical issues influencing operation performance of HVACs in super high-rise buildings? Field tests and optimization analysis - Wenbo Qiang; Jiewen Deng; Chenwei Peng; Zhanhao Liao; Xiaoliang Tang; Zhongyi Yu; Qingpeng Wei; Xinhua Xu; Hecheng Yang; Hui Zhang (Energy and Buildings, 2024)

Forecasting and early warning of shield tunnelling-induced ground collapse in rock-soil interface mixed ground using multivariate data fusion and Catastrophe Theory - Long-Chuan Deng; Wei Zhang; Lu Deng; Ye-Hui Shi; Jian-Jun Zi; Xu He; Hong-Hu Zhu (Engineering Geology, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Retraction Note: Identification of biomarkers of hepatocellular carcinoma gene prognosis based on the immune-related lncRNA signature of transcriptome data - Andi Ma; Yukai Sun; Racheal O. Ogbodu; Ling Xiao; Haibin Deng; Hui Zhou (Functional & Integrative Genomics, 2024)

Retraction Note: ZFAS1 Promotes Colorectal Cancer Metastasis Through Modulating miR-34b/SOX4 Targeting - Hong Deng; Mingming Wang; Qin Xu; Hui Yao (Cell Biochemistry and Biophysics, 2024)

Response of garlic (Allium sativum L.) to the combined toxicity of microplastics and arsenic - Zhengguo Song; Zimin Chen; Youming Dong; Hui Deng; Minling Gao (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Direct hydrogenation of CO2 to liquid hydrocarbons over K/Fe-C catalysts: Effect of porous carbon matrix and K modification - Xixi Chen; Ruxing Gao; Qiang Wang; Kehao Hu; Fenfen Wang; Chao Deng; Lujing Xu; Chundong Zhang; Ki-Won Jun; Seok Ki Kim; Tiansheng Zhao; Hui Wan; et al. (Fuel, 2024)

Immunomodulatory melanin@Pt nanoparticle-reinforced adhesive hydrogels for healing diabetic oral ulcers - Erya Cai; Xiaoliang Qi; Yizuo Shi; Xinxin Ge; Yajing Xiang; Hangbin Xu; Ying Li; Yulong Lan; Jianliang Shen; Rongdang Hu; Hui Deng (Chemical Engineering Journal, 2024)

Double-Network structure chemically programmed DNA Cryogel: Enzyme immobilization platform with enhanced catalytic activity for portable biosensing - Jiaxuan Xiao; Hui Meng; Yumo Li; Yuhan Wang; Xiaofeng Yang; Xuesong Li; Nuanfei Zhu; Yibin Deng; Yanshen Li; Zhen Zhang (Chemical Engineering Journal, 2024)

Effects of the Indian summer monsoon on the cloud characteristics over the Eastern Tibetan Plateau: a simulation study - Kai Yang; Jinghua Chen; Xiaoqing Wu; Yan Yin; Tianliang Zhao; Chunsong Lu; Liping Deng; Hui Ding (Climate Dynamics, 2024)

Mixed plantations with N-fixing tree species maintain ecosystem C:N:P stoichiometry: Implication for sustainable production - Xianyu Yao; Dafeng Hui; Shuo Xing; Qianchun Zhang; Jingwen Chen; Zihua Li; Yang Xu; Qi Deng (Soil Biology and Biochemistry, 2024)

Thermoluminescence dating of gypsum in loess deposits - Leibin Wang; Shimin Chen; Hui Zhao; Yuxin Fan; Aijun Sun; Qingsong Cai; Huizhen Deng; Jia Ai; Haiwei Zhang (Quaternary Geochronology, 2024)

Impact of microplastics on microbial-mediated soil sulfur transformations in flooded conditions - Minling Gao; Youming Dong; Hui Deng; Weiwen Qiu; Zhengguo Song (Journal of Hazardous Materials, 2024)

Improving arsenic and cadmium contaminated paddy soil health and rice quality with plant-animal-based modified biochar: A mechanistic study - Md Shafiqul Islam; Hui Deng; Youming Dong; Junhua Zhu; Minling Gao; Zhengguo Song (Journal of Cleaner Production, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

From Triassic metamorphism to Early Cretaceous anatexis in the Dabie orogen, central China: Constraints from in-situ U-Pb age and Hf and O isotopes of zircon from migmatites - Hengcong Lei; Haijin Xu; Hui Zhang; Liangpeng Deng; Dongsheng Hu; Yongkang Ye (Journal of Asian Earth Sciences, 2024)

Regulating electron-spin state enables enhanced electrocatalytic water splitting properties in bimetallic sulfides - Mengmeng Zhang; Shaohua Chang; Xu Chen; Yifang Zhang; Zhijia Zhang; Hui Xue; Yida Deng; Yong Jiang (Fuel, 2024)

Characterization and comparison of flavors in fresh and aged fermented peppers: Impact of different varieties - Miao Liu; Na Deng; Hui Li; Xiaoyi Hou; Bo Zhang; Jianhui Wang (Food Research International, 2024)

Characterization, antioxidant, and sausage preservation effects of ethanol extract from lotus seed peel powder - Na Deng; Yangping Liu; Yongjian Cai; Hui Li; Changzhu Li; Zhihong Xiao; Bo Zhang; Miao Liu; Fang Fang; Jianhui Wang (Food Control, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Swimming Performance in Large Yellow Croaker: Effects of Group Size, Test Protocol, and Recovery Time On Critical Swimming Speed - Junjia Zeng; Wei Liu; Yacheng Deng; Pengxin Jiang; Zhijun Wang; Yanhong Ou; Hongtao Lu; Yuanjingxi Hui; Hongli Xu; Peng Xu (Marine Biotechnology, 2024)

Spatiotemporal Variation of Ecosystem Services Value and its Response to Land Use Change in the Yangtze River Basin, China - Hongfei Yang; Hui Zhou; Siqi Deng; Xin Zhou; Shunan Nie (International Journal of Environmental Research, 2024)

Geomagnetic activity affects animal myocardial ischemia/reperfusion injury: an experimental-simulated study - Weiyu Chang; Xinli Chen; Yuan Yang; Yanglin Deng; Liang Dong; Hui Wu (International Journal of Biometeorology, 2024)
Numerous studies have shown that geomagnetic activity (GMA) contributes to the development and escalation of cardiovascular disease (CVD), as well as increased morbidity and mortality. However, the underlying molecular mechanisms and approaches for understanding GMA remain unclear. This study aimed to investigate the impact of GMA on oxidative stress and inflammatory responses. Myocardial ischemia/reperfusion injury (MI/RI) rat models were created under various geomagnetic field conditions. The range of cardiac function, markers of myocardial injury, inflammatory factors, and the TLR4/NF-κB signaling pathway were measured after the 24-h period. The findings showed that weak GMA significantly improved cardiac function in the MI/RI rat model and reduced the size of myocardial infarction and creatine kinase (CK) and lactic dehydrogenase (LDH) levels. Additionally, weak GMA enhanced superoxide dismutase (SOD) activity and decreased malondialdehyde (MDA) content. Furthermore, weak GMA significantly reduced the levels of the myocardial inflammatory cytokines interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). Conversely, the effects observed under severe GMA conditions were opposite to those observed under weak GMA. Western blot and qPCR analysis demonstrated that weak GMA led to a significant downregulation of TLR4, TRAF6, NF-κB, TNF-α, and MCP-1 in the MI/RI rat models. In contrast to weak GMA, severe GMA increased TLR4, TRAF6, NF-κB, and TNF-α expression. This study suggested that weak GMA had a limiting effect on MI/RI rat models, whereas severe GMA exacerbated injury in MI/RI rats. These effects were associated with oxidative stress and inflammatory responses and might potentially involve the TLR4/NF-κB signaling pathway.

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Meroterpenoids from the marine-derived fungus Aspergillus terreus GZU-31-1 exerts anti-liver fibrosis effects by targeting the Nrf2 signaling in vitro - Hui Cui; Yuqian Tang; Chunfang Yang; Huimei Deng; Lei Chen; Xueying Fan; Liping Zhu; Yena Liu; Zhongxiang Zhao; Tao Su (Phytochemistry, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Simultaneous suppression of As mobilization and N2O emission from NH4+/As-rich paddy soils by combined nitrate and birnessite amendment - Feng Wang; Jing Zhang; Jiehua Hu; Honghui Wang; Yanqiong Zeng; Yanhong Wang; Peng Huang; Huanhuan Deng; Randy A. Dahlgren; Hui Gao; Zheng Chen (Journal of Hazardous Materials, 2024)

Improving antibiotic removal and anaerobic digestion performance of discarded cefradine pellets through thermo-alkaline pretreatment - Yongsen Shi; Boyuan Pang; Yanyan Jia; Haoting Quan; Ning Zhang; Qiujin Deng; Yujian Yan; Fahui Ji; Lianpeng Sun; Hui Lu (Journal of Hazardous Materials, 2024)

Influence mechanism of K on cellulose pyrolysis by stepwise isothermal method in-situ DRIFTS method - Deng Zhao; Haoyuan Feng; Yu Wang; Fei Wang; Huashan Wang; Hua Liu; Hui Liu (Fuel, 2024)

High-entropy zeolitic imidazolate framework for efficient oxidative desulfurization of diesel fuel: Towards complete sulfur removal and valuable sulfone production - Yuzhi Liu; Chang Deng; Peiwen Wu; Hui Liu; Feng Liu; Ruoyu Liu; Wenshuai Zhu; Chunming Xu (Fuel, 2024)

Responses of grape yield and quality, soil physicochemical and microbial properties to different planting years - Qingjie Li; Okbagaber Andom; Yanli Li; Chongyang Cheng; Hui Deng; Lei Sun; Zhaojun Li (European Journal of Soil Biology, 2024)

Mechanisms of low cadmium accumulation in crops: A comprehensive overview from rhizosphere soil to edible parts - Lihong Lin; Xinyue Wu; Xingying Deng; Zheng Lin; Chunguang Liu; Jiexiang Zhang; Tao He; Yunqiang Yi; Hui Liu; Yifan Wang; Weimin Sun; Zhimin Xu (Environmental Research, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Legacy and emerging per- and polyfluoroalkyl substances in the Shuidong bay of South China: Occurrence, partitioning behavior, and ecological risks - Hui Chen; Jingyuan Jiang; Junyi Tang; Lijia Xu; Weihua Deng; Kuangmin Ye; Danna Zeng; Yuchi Luo (Chemosphere, 2024)

Crop plant automatic detecting based on in-field images by lightweight DFU-Net model - Hui Shi; Dongyuan Shi; Shengjie Wang; Wei Li; Haojun Wen; Hongtao Deng (Computers and Electronics in Agriculture, 2024)

Weakened casual feedback loops following intensive restoration efforts and climate changes in a large shallow freshwater lake - Hui Fu; Yili Ge; Guojun Cai; Jianmin Deng; Huanyao Liu; Aiping Wu; Youzhi Li; Wei Li; Guixiang Yuan; Erik Jeppesen (Science of The Total Environment, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Dimerized sesquiterpenoid [4 + 2] adducts with ferroptosis-promoting activity from Inula britannica Linn - Cong Guo; Hui-Jun Geng; Wen-Ji Wang; Yan-Xiang Liu; Lu Deng; Jun-Mian Tian; Jin-Ming Gao; Jiang-Jiang Tang (Phytochemistry, 2024)

Heat stress enhances the occurrence of erythromycin resistance of Enterococcus isolates in mice feces - Lingxian Yi; Rui Xu; Xiaowu Yuan; Zining Ren; Huihui Song; Huamin Lai; Zhihua Sun; Hui Deng; Bo Yang; Daojin Yu (Journal of Thermal Biology, 2024)

Quantitative determination of wheat moisture content based on microwave detection technique combined with multivariate data analysis - Xue Bai; Lihua Ni; Jihong Deng; Xiang Zhao; Leijun Xu; Hui Jiang (Journal of Stored Products Research, 2024)

A colorimetric and phosphorescent dual-mode nanosensing platform for the sensitive detection of tobramycin in dairy products - Songlin Liu; Mina Wang; Hui Deng; Xin Deng; Ying Xiong; Qian Wen; Wang Li; Jiali Ren; Xiangjin Fu; Yanni Chen (Food Bioscience, 2024)

Flavonoids isolated from Bauhinia brachycarpa Wall and their chemotaxonomic significance - Xing-Ping Zhang; Hui-Juan Chen; Hong Deng; Cong-Xi Gao; Xiao-Xue Jiang; Kou Wang (Biochemical Systematics and Ecology, 2024)

Specific metabolic and cellular mechanisms of the vegetative desiccation tolerance in resurrection plants for adaptation to extreme dryness - Jie Liu; Yuanyuan Wang; Xiuxiu Chen; Ling Tang; Yang Yang; Zhaolin Yang; Runze Sun; Petko Mladenov; Xiaohua Wang; Xiaoqiang Liu; Songsong Jin; Hui Li; et al. (Planta, 2024)

Odorant-Binding and Chemosensory Proteins in Fig Wasps: Evolutionary Insights From Comparative Studies - Hui Yu; Xiaojue Nong; Weicheng Huang; Chantarasuwan Bhanumas; Xiaoxia Deng; Yamei Ding; Wanzhen Liu (Journal of Molecular Evolution, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

A comprehensive review of food gels: formation mechanisms, functions, applications, and challenges - Bin Liu; Haixia Yang; Chenhui Zhu; Jianbo Xiao; Hui Cao; Jesus Simal-Gandara; Yujin Li; Daidi Fan; Jianjun Deng (Critical Reviews in Food Science and Nutrition, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Corrigendum to “Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus” [Aquaculture 578(15): 740130, 2024] - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Increased invasion of submerged macrophytes makes native species more susceptible to eutrophication in freshwater ecosystems - Qiutong Peng; Bingbing Huo; Hui Yang; Zhiyan Xu; Hongzhi Mao; Shiwen Yang; Yuitai Dai; Zhongqiang Li; Xuwei Deng (Science of The Total Environment, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Integrated microbiota and multi-omics analysis reveal the differential responses of earthworm to conventional and biodegradable microplastics in soil under biogas slurry irrigation - Yuanyuan Zhao; Huiting Jia; Hui Deng; Chengjun Ge; Wenzhe Xing; Huamei Yu; Jiatong Li (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

TMT-based quantitative proteomics analysis of Sprague-Dawley rats liver reveals Triphenyltin induced liver damage and lipid metabolism disorders - Xijuan Ren; Penghui Mao; Zhi Li; Mingqing Qian; Xinxin Deng; Hui Liu; Li Wang (Pesticide Biochemistry and Physiology, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Damage identification of long-span bridges based on the correlation of monitored global dynamic responses in high dimensional space - Fan Deng; Shiyin Wei; Yang Xu; Hui Li (Engineering Structures, 2024)

FAM21 interacts with Ku to promote the localization of WASH to DNA double strand break sites - Tao Wang; Ai-Xue Zheng; Ping Li; Tuo Tang; Lu-Ping Zhang; Yu Hong; Xian Hong; Zhi-Hui Deng (DNA Repair, 2024)

Constructing a cross-field scenario system to aware systemic risk: national security as an example - Qing Deng; Mengjiao Yao; Hui Zhang; Feng Yu; Lida Huang; Yaping Ma (Natural Hazards, 2024)

Characterization of the Microbial Community Structures, Soil Chemical Properties, and Enzyme Activity of Stellera chamaejasme (Thymelaeaceae) and Its Associated Forages in Alpine Grassland of Northwestern China - Hui Jin; Jinan Cheng; Haoyue Liu; Xiaoyan Yang; Lu Dai; Xiancheng Huang; Zuhua Yan; Deng Min; Xinxin Xu; Bo Qin (Current Microbiology, 2024)

Spatial-temporal differentiation and influencing factors of rural settlements in mountainous areas: an example of Liangshan Yi Autonomous Prefecture, Southwestern China - Yumeng Wang; Qingchun Deng; Haiqing Yang; Hui Liu; Feng Yang; Yakai Zhao (Journal of Mountain Science, 2024)

Application of QSAR models for acute toxicity of tetrazole compounds administrated orally and intraperitoneally in rat and mouse - Zhiyong Liu; Junhong Gao; Cunzhi Li; Lihong Xu; Xiaoqiang Lv; Hui Deng; Yongchao Gao; Hong Wang; Huan Li; Zhigang Wang (Toxicology, 2023)

Soil acidification suppresses phosphorus supply through enhancing organomineral association - Yuanliu Hu; Ji Chen; Dafeng Hui; Jianling Li; Xianyu Yao; Deqiang Zhang; Qi Deng (Science of The Total Environment, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Different types of meteorological drought and their impact on agriculture in Central China - Huaiwei Sun; Xunlai Sun; Jianing Chen; Xiaoya Deng; Yong Yang; Hui Qin; Fulong Chen; Wenxin Zhang (Journal of Hydrology, 2023)

Differences in fat digestion from milk of different Species: In vitro gastrointestinal digestion model for infants - Biao Liu; Ye-hui Liang; Yang-Zheng He; Wenhui Ye; Ze-Yuan Deng; Jing Li; Shuntang Guo (Food Research International, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Covalently bridge metals to biomass carbon for sensing DA and FA with high specificity and sensitivity - Lei Li; Yuanyuan Xu; Zhiyu Chen; Jieyu Zhang; Xuanyu Xiao; Hui Deng; Yujie Zhou; Guoyuan Li; Xuefeng Hu; Yunbing Wang (Chemical Engineering Journal, 2023)

Translocation of gut microbes to epididymal white adipose tissue drives lipid metabolism disorder under heat stress - Zhang-Chao Deng; Jia-Cheng Yang; Yu-Xuan Huang; Ling Zhao; Jinshui Zheng; Qing-Biao Xu; Leluo Guan; Lv-Hui Sun (Science China Life Sciences, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Predicting 1-, 3-, 5-, and 8-year all-cause mortality in a community-dwelling older adult cohort: relevance for predictive, preventive, and personalized medicine - Yequn Chen; Xiulian Deng; Dong Lin; Peixuan Yang; Shiwan Wu; Xidong Wang; Hui Zhou; Ximin Chen; Xiaochun Wang; Weichai Wu; Kaibing Ke; Wenjia Huang; et al. (EPMA Journal, 2023)
Background Population aging is a global public health issue involving increased prevalence of age-related diseases, and concomitant burden on medical resources and the economy. Ninety-two diseases have been identified as age-related, accounting for 51.3% of the global adult disease burden. The economic cost per capita for older people over 60 years is 10 times that of the younger population. From the aspects of predictive, preventive, and personalized medicine (PPPM), developing a risk-prediction model can help identify individuals at high risk for all-cause mortality and provide an opportunity for targeted prevention through personalized intervention at an early stage. However, there is still a lack of predictive models to help community-dwelling older adults do well in healthcare. Objectives This study aims to develop an accurate 1-, 3-, 5-, and 8-year all-cause mortality risk-prediction model by using clinical multidimensional variables, and investigate risk factors for 1-, 3-, 5-, and 8-year all-cause mortality in community-dwelling older adults to guide primary prevention. Methods This is a two-center cohort study. Inclusion criteria: (1) community-dwelling adult, (2) resided in the districts of Chaonan or Haojiang for more than 6 months in the past 12 months, and (3) completed a health examination. Exclusion criteria: (1) age less than 60 years, (2) more than 30 incomplete variables, (3) no signed informed consent. The primary outcome of the study was all-cause mortality obtained from face-to-face interviews, telephone interviews, and the medical death database from 2012 to 2021. Finally, we enrolled 5085 community-dwelling adults, 60 years and older, who underwent routine health screening in the Chaonan and Haojiang districts, southern China, from 2012 to 2021. Of them, 3091 participants from Chaonan were recruited as the primary training and internal validation study cohort, while 1994 participants from Haojiang were recruited as the external validation cohort. A total of 95 clinical multidimensional variables, including demographics, lifestyle behaviors, symptoms, medical history, family history, physical examination, laboratory tests, and electrocardiogram (ECG) data were collected to identify candidate risk factors and characteristics. Risk factors were identified using least absolute shrinkage and selection operator (LASSO) models and multivariable Cox proportional hazards regression analysis. A nomogram predictive model for 1-, 3-, 5- and 8-year all-cause mortality was constructed. The accuracy and calibration of the nomogram prediction model were assessed using the concordance index (C-index), integrated Brier score (IBS), receiver operating characteristic (ROC), and calibration curves. The clinical validity of the model was assessed using decision curve analysis (DCA). Results Nine independent risk factors for 1-, 3-, 5-, and 8-year all-cause mortality were identified, including increased age, male, alcohol status, higher daily liquor consumption, history of cancer, elevated fasting glucose, lower hemoglobin, higher heart rate, and the occurrence of heart block. The acquisition of risk factor criteria is low cost, easily obtained, convenient for clinical application, and provides new insights and targets for the development of personalized prevention and interventions for high-risk individuals. The areas under the curve (AUC) of the nomogram model were 0.767, 0.776, and 0.806, and the C-indexes were 0.765, 0.775, and 0.797, in the training, internal validation, and external validation sets, respectively. The IBS was less than 0.25, which indicates good calibration. Calibration and decision curves showed that the predicted probabilities were in good agreement with the actual probabilities and had good clinical predictive value for PPPM. Conclusion The personalized risk prediction model can identify individuals at high risk of all-cause mortality, help offer primary care to prevent all-cause mortality, and provide personalized medical treatment for these high-risk individuals from the PPPM perspective. Strict control of daily liquor consumption, lowering fasting glucose, raising hemoglobin, controlling heart rate, and treatment of heart block could be beneficial for improving survival in elderly populations.

Spatial correlation and coupling between industrial enterprise agglomeration and water pollutant discharge - Yazhu Wang; Yawen Deng; Xuejun Duan; Hui Zou; Lingqing Wang (Chemosphere, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Fine-grained sustainability assessment: County sustainable development in China from 2000 to 2017 - Hui Xu; Huai Deng; Dawei Zhang (Journal of Cleaner Production, 2023)

Olfactory sensor combined with chemometrics analysis to determine fatty acid in stored wheat - Hui Jiang; Jihong Deng; Quansheng Chen (Food Control, 2023)

Investigating the potential of structurally defective UiO-66 for Sb (V) removal from tailing wastewater - Mingming Peng; Deng You; Zhennan Jin; Chenquan Ni; Hui Shi; Jiachuang Shao; Xuanyu Shi; Lei Zhou; Penghui Shao; Liming Yang; Xubiao Luo (Environmental Research, 2023)

High-performance nitrogen-doped porous carbon electrode materials for capacitive deionization of Industrial salt-contaminated wastewater - Chunyu Chen; An Liu; Chi Fei; Bin Hui; Yingying Li; Deng Guan; Dianchun Ju (Desalination, 2023)

High-Capacity and High-Rate sodium storage of CoS2/NiS2@C anode material enabled by interfacial C-S covalent bond and Mott–Schottky heterojunction - Hui Zheng; Maojun Pei; Ruoxue Qiu; Dakai Ma; Shuqi Deng; Xuechao Jiao; Kaili Wang; Yinze Zuo; Wei Yan; Yao Liu; Jiujun Zhang (Chemical Engineering Journal, 2023)

Interface engineering of hollow CsPbBr3/Co3O4 p-n heterojunction with rich oxygen vacancy for highly enhanced photocatalytic CO2 reduction - Xiuzheng Deng; Qian Liang; Jingshan Fan; Xiong Yan; Honglin Si; Hui Huang; Zhongyu Li; Zhenhui Kang (Chemical Engineering Journal, 2023)

DjFARP Contributes to the Regeneration and Maintenance of the Brain through Activation of DjRac1 in Dugesia japonica - Qian Song; Huazhi Geng; Hui Zhen; Hongjin Liu; Hongkuan Deng; Zuoqing Yuan; Jianyong Zhang; Zhonghong Cao; Qiuxiang Pang; Bosheng Zhao (Molecular Neurobiology, 2023)

Plants are the drivers of geographic variation of floral odours in brood site pollination mutualisms: A case study of Ficus hirta - Xiaoxia Deng; Bruno Buatois; Yan-Qiong Peng; Hui Yu; Yufen Cheng; Xuejun Ge; Magali Proffit; Finn Kjellberg (Acta Oecologica, 2023)

In vivo characterization of the superior fitness of classical swine fever virus genotype 2.1 to genotype 3.4 - Hsin-Meng Liu; Ming-Chung Deng; Yu-Liang Huang; Kuo-Jung Tsai; Hui-Wen Chang; Chia-Yi Chang (Veterinary Microbiology, 2023)

Microbubbles drag reduction characteristics of underwater vehicle during pitching movement - Weixue Xia; Wuchao Song; Cong Wang; Wenbin Yi; Qingchang Meng; Hui Deng (Ocean Engineering, 2023)

Genome analysis of Tepidibacter sp. SWIR-1, an anaerobic endospore-forming bacterium isolated from a deep-sea hydrothermal vent - Xue-Gong Li; Jie Dai; Wei-Jia Zhang; Ai-Jun Jiang; Deng-Hui Li; Long-Fei Wu (Marine Genomics, 2023)

Reactive migration mechanism of Fe2+ and As3+ during groundwater discharge into river water: Insight from sand column experiments - Xiyu Deng; Yao Huang; Ziwei Guo; Shengjun Mao; Shuang Li; Lei Tong; Minjing Li; Hui Liu (Journal of Hydrology, 2023)

Differences between reductive defluorination of perfluorooctanoic acid by chlorination, bromination, and iodization in the vacuum-ultraviolet/sulfite process - Changlan Hou; Jiaqin Deng; Shanhong Li; Hui Li; Yin Zhou; Yunbo Zhai (Journal of Hazardous Materials, 2023)

Integrated microbiome and multi-omics analysis reveal the molecular mechanisms of Eisenia fetida in response to biochar-derived dissolved and particulate matters - Huiting Jia; Yuanyuan Zhao; Hui Deng; Huamei Yu; Chengjun Ge; Jiatong Li (Journal of Hazardous Materials, 2023)

Effect of clay fraction on the mechanical properties and microstructural characteristics of waste rock fine-based brick - Sheng Zhang; Yunzhi Tan; Yongfeng Deng; Huajun Ming; Hui Li; Jun Wu (Journal of Cleaner Production, 2023)

Strategic nitrogen defect engineering for optimizing the photocatalytic performance of polymerized carbon nitride: Identification, synthesis, and mechanism - Zhangkai Chen; Meifang Li; Xinjiang Hu; Yuan Yuan; Hui Wang; Jiaqin Deng; Xiaodong Ji; Guoyu Li; Yuan Ouyang; Ni Liu (Journal of Environmental Chemical Engineering, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Quantitative effect of lithologic-geomorphic coupling on gully distribution at the regional scale: An example of the Dry Valleys (SW China) - Ziquan Zuo; Yuli He; Jun Luo; Lei Wang; Qingchun Deng; Hui Liu; Ying Zhao; Bin Zhang (Geomorphology, 2023)

Determination of multiple mycotoxins in chili powder using cold-induced liquid–liquid extraction and Fe3O4@MWCNTs-NH2 coupled with UPLC-Q-TOF/MS - Fenglan Zhou; Huiling Deng; Israel Emiezi Agarry; Jiang Hu; Donghui Xu; Hui Feng; Jianquan Kan; Tian Cai; Kewei Chen (Food Chemistry, 2023)

The effects of selenium on the growth and bone development in the weaned rats - Hongan Li; Linlin Jia; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Bioscience, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

The effectiveness of acoustic treatments in general hospital wards in China - Zhixiao Deng; Hui Xie; Jian Kang (Building and Environment, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

Evaluating the application of branched tetraether proxies in surface soils along the altitudinal transect at Mount Dabie, China - Li- Huan Deng; Feng-Hui Zou; Huan Yang; Feng Li (Arabian Journal of Geosciences, 2023)

Alsobacter ponti sp. nov., a novel denitrification and sulfate reduction bacterium isolated from Pearl River sediment - Qi-Qi Deng; Xiao-Qing Luo; Shan-Hui Li; Jia-Ling Li; Pan-Deng Wang; Yang Yuan; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Investigation on bubble load characteristics of near-field underwater explosion - Zhichao Lai; Shuo Deng; Jian Qin; Hui Chi; Xiangyao Meng; Xiaoqiang Yang; Ruiyuan Huang (Ocean Engineering, 2023)

Lipopolysaccharide accelerates tryptophan degradation in the ovary and the derivative kynurenine disturbs hormone biosynthesis and reproductive performance - Jie Shen; Weimin Zhao; Juanru Cheng; Jinhua Cheng; Lei Zhao; Chaohui Dai; Yanfeng Fu; Bixia Li; Zhe Chen; Deshun Shi; Hui Li; Yanfei Deng (Journal of Hazardous Materials, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Quantification of the nonlinear interaction among the tide, surge and river in Pearl River Estuary - Shikun Hu; Bingjun Liu; Maochuan Hu; Xuan Yu; Zhihong Deng; Hui Zeng; Mingzhu Zhang; Dan Li (Estuarine, Coastal and Shelf Science, 2023)

Microbial iron reduction activating sodium percarbonate for improving the dewaterability of iron-rich sludge - Lianpeng Sun; Chuanhan Chen; Siru Zhou; Weifang Yuan; Hui Lu; Hao Wang; Xinzhe Zhu; Huanzhong Deng; Xiao-yan Li; Lin Lin; Ruo-hong Li (Chemical Engineering Journal, 2023)

Influence of Rice Straw Biochar Application on Soil Nutrient Dynamics and Rice Productivity Under Different Irrigation Regimes - Le Chen; Lin Guo; Xueyun Deng; Xiaohua Pan; Xiaobing Xie; Xueming Tan; Ping Liao; Qiangqiang Xiong; Qigen Dai; Hui Gao; Haiyan Wei; Yongjun Zeng; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Comparative tests on the failure characteristics and mechanisms of slopes with curved surfaces - Shuwei Sun; Jiabing Hu; An Deng; Xianfu Xu; Hui Ding (Bulletin of Engineering Geology and the Environment, 2023)

A new insight of cadmium-induced cellular evidence of autophagic-associated spermiophagy during spermatogenesis - Waseem Ali; Kai Deng; Jian Sun; Yonggang Ma; Zongping Liu; Hui Zou (Environmental Science and Pollution Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Short-chain fatty acid producers in compost tea as affected by brewing time and aeration condition - Xiaoxing Wang; Qihang Wei; Quansheng Zhao; Xiayan Liu; Hui Deng; Zhaojun Li (Journal of Soils and Sediments, 2023)

Regulation of Water Masses to Hypoxia Zones in the Changjiang Estuary - Xingxing Yang; Haimei Fan; Hui Zhang; Sisi Chen; Ying Yang; Huanhong Ji; Xiaoshan Jiang; Bangping Deng; Junhe Jia (Journal of Ocean University of China, 2023)

Removal effect of typical pollutants from stormwater runoff in ecological ditches - Hui Luo; Jing Yang; Bao-Jie He; Wenhao Zhang; Mingyu Yang; Shiyu Deng; Yuhang Zuo (Environmental Science and Pollution Research, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

An improved vacuum-steam pulsed blanching machine design and garlic scape blanching verified experiment - Jing-Shou Zhang; Xian-Jun Chen; Sara Zielinska; Parag Prakash Sutar; Suo-Bin Li; Li-Zhen Deng; Hui Wang; Yu-Hang Chen; Hong-Wei Xiao (Innovative Food Science & Emerging Technologies, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

Short-term effects of asymmetric day and night warming on soil N2O, CO2 and CH4 emissions: A field experiment with an invasive and native plant - Xue Han; Na-Na Yao; Xiao-Jing Wang; Hao-Hui Deng; Hui-Xuan Liao; Sheng-Qi Fan; Bao-Ming Chen (Applied Soil Ecology, 2023)

Emission profiles, source identifications, and health risk of polycyclic aromatic hydrocarbons (PAHs) in a road tunnel located in Xi’an, China - Jiayao Liu; Shunxi Deng; Hui Tong; Yan Yang; Abula Tuheti (Environmental Science and Pollution Research, 2023)

Triassic granites in the West Qinling Orogen, China: implications for the Early Mesozoic tectonic evolution of the Paleo-Tethys ocean - Feng-Hui Zou; Cai-Lai Wu; Dong Gao; Li-Huan Deng; Yuan-Hong Gao (International Geology Review, 2023)

Lower limits of petrophysical parameters for effective reservoirs in ultradeep carbonate gas reservoirs: A case study from the Deng IV Member, Gaoshiti-Moxi Area, Sichuan Basin, SW China - Lu Wang; Yifan Zhang; Ruilan Luo; Rui Zou; Hui Deng; Run Zou; Liang Huang; Yisheng Liu (Journal of Hydrology, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Magnetic biochar promotes the risk of mobile genetic elements propagation in sludge anaerobic digestion - Yanru Zhang; Yinping Xiang; Rui Xu; Jing Huang; Jiaqin Deng; Xuan Zhang; Zijian Wu; Zhongliang Huang; Zhaohui Yang; Jingliang Xu; Wenlong Xiong; Hui Li (Journal of Environmental Management, 2023)

Dietary supplementation with casein/cyanidin-3-O-glucoside nanoparticles alters the gut microbiota in high-fat fed C57BL/6 mice - Qiyan Lyu; Hongting Deng; Shunxin Wang; Hesham El-Seedi; Hui Cao; Lei Chen; Hui Teng (Food Chemistry, 2023)

A comparative study on the taste quality of Mytilus coruscus under different shucking treatments - Shichen Zhu; Lin Zhu; Zhigang Ke; Hui Chen; Yadan Zheng; Peng Yang; Xingwei Xiang; Xiaomin Zhou; Youding Jin; Shanggui Deng; Xuxia Zhou; Yuting Ding; et al. (Food Chemistry, 2023)

Callose wall and sporoderm characteristics during the anther development stage of Dendrobium officinale - Wei Deng; Mei Zhen Lin; Hui Qiao Tian (Flora, 2023)

Enzyme-responsive microneedle patch for bacterial infection and accelerated healing of diabetic wounds - Shizhou Wu; Boquan Qin; Xiaofang Tang; Ting Cui; Shijiu Yin; Hongxian Dong; Yunjie Liu; Shu Deng; Hui Zhang; Guoying Feng; Huiqi Xie; Lei Lei (Chemical Engineering Journal, 2023)

Flavins enhance the hydroxyl radical production from FeCO3 oxygenation for organic pollutant degradation - Rong Chen; Hui Liu; Na Zhang; Yao Huang; Xiyu Deng; Menggui Jin (Chemical Geology, 2023)

Arbuscular Mycorrhizal Fungi Alter the Interaction Effects Between Bacillus and Rhizobium on Root Morphological Traits of Medicago ruthenica L. - Lu Yu; Hui Zhang; Wantong Zhang; Bing Han; Huakun Zhou; Xinming Lu; Yanfang Deng; Kesi Liu; Xinqing Shao (Journal of Soil Science and Plant Nutrition, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Correction to: Identification of biomarkers of hepatocellular carcinoma gene prognosis based on the immune‑related lncRNA signature of transcriptome data - Andi Ma; Yukai Sun; Racheal O. Ogbodu; Ling Xiao; Haibin Deng; Hui Zhou (Functional & Integrative Genomics, 2023)

RETRACTED ARTICLE: Identification of biomarkers of hepatocellular carcinoma gene prognosis based on the immune-related lncRNA signature of transcriptome data - Andi Ma; Yukai Sun; Racheal O. Ogbodu; Ling Xiao; Haibin Deng; Hui Zhou (Functional & Integrative Genomics, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Microbial community evolution and functional trade-offs of biofilm in odor treatment biofilters - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Guan-Yu Jiang; Meng-Fei Han; Ji-Guang Deng; Hsing-Cheng Hsi (Water Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Soil aggregate stability and its response to overland runoff–sediment transport in karst peak–cluster depressions - Jinyue Wang; Hui Wei; Juan Huang; Tieguang He; Yusong Deng (Journal of Hydrology, 2023)

Arc bead ignition of a cellulose fuel bed derived from experimental and simulated data - Hui-Fei Lyu; Cai-Ping Wang; Jun Deng; Wei-Feng Wang; Yang Li; Chi-Min Shu (Fuel, 2023)

Accurate prediction of the eating and cooking quality of rice using artificial neural networks and the texture properties of cooked rice - Fei Deng; Hui Lu; Yujie Yuan; Hong Chen; Qiuping Li; Li Wang; Youfeng Tao; Wei Zhou; Hong Cheng; Yong Chen; Xiaolong Lei; Guiyong Li; et al. (Food Chemistry, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Development and evolution of deep-seated toppling landslide by rapid river downcutting - Guoxiang Tu; Hui Deng; Ming Li (Bulletin of Engineering Geology and the Environment, 2023)

The coexistence of two related fig wasp species sharing the same host fig species across a broad geographical area - Xiaoxia Deng; Yaolin Liao; Wanzhen Liu; Hui Yu (Acta Oecologica, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Interactions of H2O and O2 with char during gasification in mixed atmosphere analyzed by isotope tracer method and in-situ DRIFTS - Deng Zhao; Shiqin Shu; Jianlong Zhao; Yongxiang Liang; Huashan Wang; Hui Liu; Lina Li; Daolei Wang (Fuel, 2023)

Alpha-class glutathione S-transferases involved in the detoxification of aflatoxin B1 in ducklings - Yu Zhang; Ke-Xin Cao; Qin-Jian Niu; Jiang Deng; Ling Zhao; Mahmoud Mohamed Khalil; Niel Alexander Karrow; Kamil Kuča; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Research on systematic analysis and optimization method for chillers based on model predictive control: A case study - Jiewen Deng; Wenbo Qiang; Chenwei Peng; Qingpeng Wei; Hui Zhang (Energy and Buildings, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Effects of temperature, relative humidity, and illumination on the entomological parameters of Aedes albopictus: an experimental study - Xiaoshuang Cai; Jianguo Zhao; Hui Deng; Jianpeng Xiao; Tao Liu; Weilin Zeng; Xing Li; Jianxiong Hu; Cunrui Huang; Guanghu Zhu; Wenjun Ma (International Journal of Biometeorology, 2023)

Effects of sand sedimentation and wind erosion around sand barrier: Numerical simulation and wind tunnel test studies - Kai Zhang; Hai-long Zhang; Yu-hui Deng; Jian-jun Qu; Zheng-hui Wang; Sheng Li (Journal of Mountain Science, 2023)

Microfluidic Generation of Near-Infrared Photothermal Vitexin/ICG Liposome with Amplified Photodynamic Therapy - Xia Cao; Qi Liu; Michael Adu-Frimpong; Wenwan Shi; Kai liu; Tianwen Deng; Hui Yuan; Xuedi Weng; Yihong Gao; Qingtong Yu; Wenwen Deng; Jiangnan Yu; et al. (AAPS PharmSciTech, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Evaluation of production capacity for rice-rapeseed cropping system in China - Jiada Huang; Xinyuan Cao; Jie Kuai; Hui Cheng; Qingsong Zuo; Hai Du; Shaobing Peng; Jianliang Huang; Nanyan Deng (Field Crops Research, 2023)

Highly efficient bacteria-infected diabetic wound healing employing a melanin-reinforced biopolymer hydrogel - Yajing Xiang; Xiaoliang Qi; Erya Cai; Chaofan Zhang; Jiajia Wang; Yulong Lan; Hui Deng; Jianliang Shen; Rongdang Hu (Chemical Engineering Journal, 2023)

Improved soil composition promotes nutrient recovery during vegetation restoration in karst peak-cluster depressions - Hui Wei; Yusong Deng; Liwen Lin; Jinyue Wang; Juan Huang (CATENA, 2023)

SecReT6 update: a comprehensive resource of bacterial Type VI Secretion Systems - Jianfeng Zhang; Jiahao Guan; Meng Wang; Gang Li; Marko Djordjevic; Cui Tai; Hui Wang; Zixin Deng; Zhaoyan Chen; Hong-Yu Ou (Science China Life Sciences, 2023)

Risk Assessment and Source Analysis of Atmospheric Heavy Metals Exposure in Spring of Tianjin, China - Yi Wang; Fang Li; Yang Liu; Xiaojuan Deng; Hui Yu; Jingpeng Li; Tao Xue (Aerosol Science and Engineering, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Killing three birds with one stone: Multi-stage metabolic regulation mediated by clinically usable berberine liposome to overcome photodynamic immunotherapy resistance - Chunjuan Zheng; Wenjuan Luo; Yu Liu; Jiashe Chen; Hui Deng; Zaigang Zhou; Jianliang Shen (Chemical Engineering Journal, 2023)

Lithiophilic and conductive framework of 2D MoN nanosheets enabling planar lithium plating for dendrite-free and minimum-volume-change lithium metal anodes - De Gao; Shuzhen Deng; Xiaogang Li; Yingxi Zhang; Tuan Lv; Yang He; Weijian Mao; Hui Yang; Jingwei Zhang; Paul K. Chu; Kaifu Huo (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Selection and electrochemical-sensor application of an DNA-aptamer for methyl parathion detection - Wenfei Guo; Changchun Hu; Shuo Li; Dan Wei; Jie Zhou; Xueying Liu; Hui Chen; Song Li; Yan Deng (Analytica Chimica Acta, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

Short-term morphological evolution of an ephemeral gully in the Dry-hot Valley of Southwest China - Lei Wang; Jilin Zheng; Bin Zhang; Wu Li; Jun Luo; Zhengping Du; Qingchun Deng; Hui Liu (Soil and Tillage Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Low symmetric sub-wavelength array enhanced lensless polarization-sensitivity photodetector of germanium selenium - Ziqi Zhou; Tao Shen; Pan Wang; Quanlin Guo; Qinghe Wang; Chenjun Ma; Kaiyao Xin; Kai Zhao; Yali Yu; Biao Qin; Yue-Yang Liu; Juehan Yang; et al. (Science Bulletin, 2023)

Protolith origin of eclogites from the North Qaidam UHP metamorphic Belt, NW China: Implications for the breakup of the Rodinia supercontinent - Xiao-Dong Wang; Lin Ding; Deng Zeng; Ya-Hui Yue; Ling-Ping Yang; Zhe-Jun Wang; Lu-An Xiao; Chao Wang (Precambrian Research, 2023)

An ultrasensitive lateral flow immunoassay platform for foodborne biotoxins and pathogenic bacteria based on carbon-dots embedded mesoporous silicon nanoparticles fluorescent reporter probes - Yuhui Wang; Chen Deng; Sihua Qian; Hui Li; Pan Fu; Hualan Zhou; Jianping Zheng (Food Chemistry, 2023)

Residential greenness and risk of incident dementia: A prospective study of 375,342 participants - He-Ying Hu; Ya-Hui Ma; Yue-Ting Deng; Ya-Nan Ou; Wei Cheng; Jian-Feng Feng; Lan Tan; Jin-Tai Yu (Environmental Research, 2023)

Influence of microplastics on microbial anaerobic detoxification of chlorophenols - Zhaochao Deng; Ning Zhang; Lijia Jiang; Hui Liu; Songtao Hu; Dongdong Zhang; Bairu Chen; Qing Liu; Yuxia Sun; Jiawang Chen; Chunfang Zhang (Environmental Pollution, 2023)

Can heat pump heat storage system perform better for space heating in China’s primary schools? A field test and simulation analysis - Jiewen Deng; Chenwei Peng; Wenbo Qiang; Qingpeng Wei; Hui Zhang (Energy and Buildings, 2023)

Constructing the o-FCMP adsorbent as a redox-reactor to implement in situ regeneration of binding sites for selective capture of precious metals - Xin Sheng; Xuan Ding; Congcong Liu; Hui Shi; Penghui Shao; Liming Yang; Deng You; Mingming Peng; Xubiao Luo; Shenglian Luo (Chemical Engineering Journal, 2023)

Tuning the isoelectric point of zinc molybdate nanomaterials to enhance the biohydrogen production of rice straws - Yuheng Zhou; Xiaohui Wang; Xubo Huang; Hui Deng; Yuntao Hu; Linfang Lu (Chemical Engineering Journal, 2023)

Excellent energy storage and mechanical performance in hetero-structure BaTiO3-based relaxors - Liang Chen; Feng Li; Botao Gao; Chang Zhou; Jie Wu; Shiqing Deng; Hui Liu; He Qi; Jun Chen (Chemical Engineering Journal, 2023)

Reversible cross-linked phosphorylate binder for recyclable lithium-sulfur batteries - Hui Wang; Guangzhao Zhang; Yukun Chen; Peitao Zheng; Huan Yi; Yonghong Deng; Yu Yang; Chaoyang Wang (Chemical Engineering Journal, 2023)

Valence-switchable and biocatalytic vanadium-based MXene nanoplatform with photothermal-enhanced dual enzyme-like activities for anti-infective therapy - Xiaoshuai Sun; Xiaojun He; Yue Zhu; Enoch Obeng; Bairui Zeng; Hui Deng; Jianliang Shen; Rongdang Hu (Chemical Engineering Journal, 2023)

Enzymatic biotransformation of Rb3 from the leaves of Panax notoginseng to ginsenoside rd by a recombinant β-xylosidase from Thermoascus aurantiacus - Hui Zhang; Hongxi Zhu; Xiuyuan Luo; Yuanzhen Deng; Wei Zhang; Shubo Li; Jingjuan Liang; Zongwen Pang (World Journal of Microbiology and Biotechnology, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Rice straw biochar reduces Cd accumulation and promotes Cu accumulation in rice: irrigation regime is the driving factor - Le Chen; Lin Guo; Ping Liao; Qiangqiang Xiong; Xueyun Deng; Hui Gao; Haiyan Wei; Qigen Dai; Xiaohua Pan; Yongjun Zeng; Hongcheng Zhang (Journal of Soils and Sediments, 2023)

A quantitative study of the influence of soil organic carbon and pore characteristics on the stability of aggregates of the karst peak-cluster depression area in Southwest China - Hui Wei; Yusong Deng; Juan Huang; Ling He; Qiuyue Tang; Yan Xiao (Journal of Soils and Sediments, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Diverse variations in middle and high latitudes of the Northern Hemisphere spring phenology sensitivity to diurnal temperature during 1982–2015 - Guorong Deng; Hongyan Zhang; Jianjun Zhao; Xiaoyi Guo; Ehsan Biniyaz; Hang Zhao; Dan Guo; Rihan Wu; Hui Li (International Journal of Climatology, 2022)
Recent studies have revealed that the influence of diurnal temperature on spring phenology is asymmetric, and the faster night‐time warming in the Northern Hemisphere (NH) has a complex impact on spring phenology. Our understanding from the sensitivity of the start of the growing season (SOS) to daytime (S T _daytime) and night‐time temperatures (S T _night‐time) has urgently needs to be improved. In this study, the SOS sensitivity to diurnal temperature in the middle and high latitudes of the NH (>30°N) from 1982 to 2015 is estimated. The results indicate that although SOS showed stronger sensitivity to daytime than night‐time temperature in most parts of the study areas, the influence of daytime temperature on SOS is decreasing, while the influence of night‐time temperature on SOS is increasing. The variations in S T _daytime and S T _night‐time along the latitude gradient were significantly correlated with the warming rate of the preseason diurnal temperature ( p T _night‐time was higher than S T _daytime at other latitudes due to topography and rapid night‐time warming. On the altitude gradient, the SOS was more sensitive to daytime temperature in areas below 800 and 2,000–4,000 m. S T _night‐time exceeded S T _daytime at other altitudes owing to night‐time warming relief of the severe restrictions on phenological processes and the reduction in frost risk. To reach a comprehensive characterization of the interaction between vegetation and climate systems, the current study suggests more investigation on the response of SOS to diurnal temperature on large scales.

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Neuroprotective Effect of Sonic Hedgehog Mediated PI3K/AKT Pathway in Amyotrophic Lateral Sclerosis Model Mice - Yan Qi; Chen Yang; Hui Zhao; Zhanjin Deng; Jin Xu; Weijing Liang; Zhitang Sun; John Dirk Vestergaard Nieland (Molecular Neurobiology, 2022)
The Sonic Hedgehog (SHH) signaling pathway is related to the progression of various tumors and nervous system diseases. Still, its specific role in neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS), remains studied. This research investigates the role of SHH and PI3K/AKT signaling pathway proteins on ALS development in a SOD1-G93A transgenic mouse model. After injection of SHH and PI3K/AKT signaling pathway inhibitors or agonists in hSOD1-G93A (9 weeks of age) transgenic mice, we studied skeletal muscle pathology using immunohistochemical staining and Western blot methods. In addition, recorded data on rotation time, weight, and survival were analyzed for these mice. Our study showed that the expression of SHH, Gli-1 and p-AKT in ALS mice decreased with the progression of the disease. The expression of p-AKT changed together with Gli-1 while injecting PI3K/AKT signaling pathway inhibitor or agonist; SHH and Gli-1 protein expression remained unchanged; p-AKT protein expression significantly decreased while injecting PI3K/AKT signaling pathway inhibitor. These results indicate that SHH has a regulatory effect on PI3K/AKT signaling pathway. In behavioral experiments, we found that the survival time of hSOD1-G93A mice was prolonged by injection of SHH agonist while shortened by injection of SHH inhibitor. In conclusion, we confirmed that the SHH pathway played a neuroprotective role in ALS by mediating PI3K/AKT signaling pathway.

Hydrofacies simulation based on transition probability geostatistics using electrical resistivity tomography and borehole data - Lei Ma; Hui Deng; Yongshuai Yan; Yaping Deng; Weidong Zhao; Xiaohui Tan; Jiazhong Qian (Hydrogeology Journal, 2022)

Dephenolization pyrolysis fluid improved physicochemical properties and microbial community structure of saline-alkali soils - Shuai Wang; Hanyu Chang; Zhenfei Dong; Yansen Ren; Tianle Tan; Hui Deng (Environmental Science and Pollution Research, 2022)

Comparison of ascorbate metabolism in fruits of two jujube species with differences in ascorbic acid content - Yang Wang; Guoying Song; Dong Liang; Hui Xia; Huifen Zhang; Xian Luo; Qunxian Deng (Horticulture, Environment, and Biotechnology, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Determination of extractable and non-extractable florfenicol residues as florfenicol amine in eggs by UPLC-MS/MS - Xia Li; Yu Zhang; Qifan Sun; Min Ding; Zengmei Li; Hui Yue; Ligang Deng; Lu Chen (Food Additives & Contaminants: Part A, 2022)

WASHC1 interacts with MCM2-7 complex to promote cell survival under replication stress - Yu Hong; He Sun; Xian Hong; Cai-Ping Yang; Daniel D. Billadeau; Tao Wang; Zhi-Hui Deng (Molecular Biology Reports, 2022)

CircRNA.0007127 triggers apoptosis through the miR-513a-5p/CASP8 axis in K-562 cells - Xiajing Li; Yiyu Zhang; Ning Wang; Zhaohu Yuan; Xiaojie Chen; Qicong Chen; Hui Deng; Xinxin Tong; Honglin Chen; Yuyou Duan; Yaming Wei (Journal of Zhejiang University-SCIENCE B, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Petrogenesis of Early-Middle Jurassic gabbros in southern Tibet with implications for crustal growth in the southern Lhasa subterrane - Liang Li; Hui Xie; Xinghai Lang; Xuhui Wang; Qing He; Yulin Deng; Fuwei Xie (International Geology Review, 2022)

Design, synthesis, and biological evaluation of novel 2-acetylphenol-rivastigmine hybrids as potential multifunctional agents for the treatment of Alzheimer’s disease - Cong Deng; Jing Mi; Yi Zhou; Xinjuan Li; Zhengwei Liu; Zhipei Sang; Hui Li (Medicinal Chemistry Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Mycorrhizal fungi alleviate acidification‐induced phosphorus limitation: Evidence from a decade‐long field experiment of simulated acid deposition in a tropical forest in south China - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying‐Ping Wang; Jianling Li; Jingwen Chen; Guoyin Chen; Yiren Zhu; Leiyi Zhang; Deqiang Zhang; Qi Deng (Global Change Biology, 2022)
South China has been experiencing very high rate of acid deposition and severe soil acidification in recent decades, which has been proposed to exacerbate the regional ecosystem phosphorus (P) limitation. We conducted a 10‐year field experiment of simulated acid deposition to examine how acidification impacts seasonal changes of different soil P fractions in a tropical forest with highly acidic soils in south China. As expected, acid addition significantly increased occluded P pool but reduced the other more labile P pools in the dry season. In the wet season, however, acid addition did not change microbial P, soluble P and labile organic P pools. Acid addition significantly increased exchangeable Al 3+ and Fe 3+ and the activation of Fe oxides in both seasons. Different from the decline of microbial abundance in the dry season, acid addition increased ectomycorrhizal fungi and its ratio to arbuscular mycorrhiza fungi in the wet season, which significantly stimulated phosphomonoesterase activities and likely promoted the dissolution of occluded P. Our results suggest that, even in already highly acidic soils, the acidification‐induced P limitation could be alleviated by stimulating ectomycorrhizal fungi and phosphomonoesterase activities. The differential responses and microbial controls of seasonal soil P transformation revealed here should be implemented into ecosystem biogeochemical model for predicting plant productivity under future acid deposition scenarios.

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Chaowei Zhou; Yan Li; Yan Zhou; Yu Zou; Dengyue Yuan; Xingxing Deng; Luo Lei; Jian Su; Chengke Zhu; Hua Ye; Hui Luo; Guangjun Lv; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus ( C. argus ), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus . In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus . A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Association between congenital heart defects and maternal manganese and iron concentrations: a case–control study in China - Meixian Wang; Yan Tian; Ping Yu; Nana Li; Ying Deng; Lu Li; Hong Kang; Dapeng Chen; Hui Wang; Zhen Liu; Juan Liang (Environmental Science and Pollution Research, 2022)
To investigate the correlation between maternal manganese and iron concentrations and the risk of CHD among their infant. A multi-center hospital-based case control study was conducted in China. There were 322 cases and 333 controls have been selected from pregnant women who received prenatal examinations. Correlations between CHDs and maternal manganese and iron concentrations were estimated by conditional logistic regression. Moreover, the interaction between manganese and iron on CHDs was analyzed. Compared with the controls, mothers whose hair manganese concentration was 3.01 μg/g or more were more likely to have a child with CHD than those with a lower concentration. The adjusted OR was 2.68 (95%CI = 1.44–4.99). The results suggested that mothers whose iron content was 52.95 μg/g or more had a significantly higher risk of having a child with CHD ( aOR = 2.87, 95%CI = 1.54–5.37). No interaction between maternal manganese and iron concentrations was observed in the multiplicative or additive model. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD ( OR = 7.02). Women with excessive manganese concentrations have a significantly increased risk of having offspring with CHDs. The high maternal iron status also correlates with CHDs. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD.

Genetic diversity analysis of forty-three insertion/deletion loci for forensic individual identification in Han Chinese from Beijing based on a novel panel - Congying Zhao; Jinlong Yang; Hui Xu; Shuyan Mei; Yating Fang; Qiong Lan; Yajun Deng; Bofeng Zhu (Journal of Zhejiang University-SCIENCE B, 2022)

Three-dimensional forward modeling and response characteristics analysis of foundation pit leakage electric-field considering electrokinetic effect - Chen Yu-Feng; Chen Hui; Deng Ju-Zhi; Liu Sui-Ming; Tang Wen-Wu; Wang Shuo (Applied Geophysics, 2022)

A Mathematical Modeling Method for an Analytical Solution of Ship Hydrodynamic Pressure Fields in Complex Restricted Waters - Hui Deng; Zhihong Zhang; Wenbin Yi; Weixue Xia (Journal of Marine Science and Engineering, 2022)
A ship advancing in restricted waters may cause a change in the surrounding velocity field, which in turn results in the hydrodynamic pressure field according to the variations in the ship speed. Accurate prediction of ship hydrodynamic pressure fields in restricted waters is therefore essential and important in the military and engineering fields. Based on the potential flow theory and the thin-ship assumption, dividing complex restricted waters with varying depths into the inner and outer domains with constant depths, a mathematical modeling method is developed and carried out for analyzing and solving the partial differential equations consisting of the governing equation with a dispersion effect, initial and boundary conditions, then the analytical solution of hydrodynamic pressure field caused by a ship advancing in complex restricted waters is obtained. The continuity of the analytical solution is confirmed and the correctness of the analytical solution is validated by simplifying to a simple water and comparing with available data. Moreover, the mathematical modeling method can be extended to study the hydrodynamic problems of ships in more complex waters.

High-quality genome assembly of Huazhan and Tianfeng, the parents of an elite rice hybrid Tian-you-hua-zhan - Hui Zhang; Yuexing Wang; Ce Deng; Sheng Zhao; Peng Zhang; Jie Feng; Wei Huang; Shujing Kang; Qian Qian; Guosheng Xiong; Yuxiao Chang (Science China Life Sciences, 2022)

MicroRNA-451a attenuates angiotensin II–induced cardiac fibrosis and inflammation by directly targeting T-box1 - Hao-Yuan Deng; Ze-Yin He; Zhi-Chao Dong; Yun-Long Zhang; Xiao Han; Hui-Hua Li (Journal of Physiology and Biochemistry, 2022)

Numerical Simulation of the Combined Slope Protection Effect of Living Stump and Bamboo Anchor - Yingbo Zhu; Hui Yang; Yong Liu; Xueliang Jiang; Riwen Deng; Li Huang; Peng Yin; Guojie Lai (Geotechnical and Geological Engineering, 2022)

Effect of freeze—thaw cycle on hydraulic conductivity of compacted clayey soil - Lei Guo; Qi-hao Yu; Na Yin; Dong-ming Zhang; Deng-ping Zhang; Xiu-ling Ren; Yan-hui You; Zhen-yu Zhang; Hui Bing; Shi-jie Chen (Journal of Mountain Science, 2022)

Experimental Research on Cumulative Damage Law of Microcrystalline Limestone under Fixed Equivalent Cyclic Blasting Load - Anrun Li; Hui Deng; Haojie Zhang (Arabian Journal of Geosciences, 2022)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Cyclometalated Ru(II) β-carboline complexes induce cell cycle arrest and apoptosis in human HeLa cervical cancer cells via suppressing ERK and Akt signaling - Jincan Chen; Yuanyuan Deng; Jie Wang; Suxiang Chen; Fa Peng; Xuerong He; Meijun Liu; Hui Luo; Jingjing Zhang; Lanmei Chen (JBIC Journal of Biological Inorganic Chemistry, 2021)

Gonadal antioxidant responses to seawater acidification and hypoxia in the marine mussel Mytilus coruscus - Guangen Xu; Hui Kong; Xueqing Chang; Sam Dupont; Hui Chen; Yuewen Deng; Menghong Hu; Youji Wang (Environmental Science and Pollution Research, 2021)

PEG‐modified subunit vaccine encoding dominant epitope to enhance immune response against spring viraemia of carp virus - Hui‐Xin Duan; Zhao Zhao; Ying‐Jie Jin; Zi‐Long Wang; Jie‐Fang Deng; Jie He; Bin Zhu (Journal of Fish Diseases, 2021)
Spring viraemia of carp (SVC) caused by spring viraemia of carp virus (SVCV) can infect almost all fish of cyprinids, which bring huge economic losses to aquaculture. Glycoprotein (G), as the most important antigenic determinant protein of SVCV, is widely considered as an effective method against SVCV. In our previous study, we found that G3 (131 aa) is the potential dominant antigen epitope that induces strong immune responses similar to G protein (510 aa). Here, in order to further improve the immune effect, we reported a subunit vaccine (PEG‐G3) constructed by PEG‐modified dominant epitope protein (G3). The results of serum antibody production, enzyme activities and immune‐related genes expression showed that PEG‐G3 induces significantly stronger immune protective responses against SVCV than G3. PEG modification significantly increased the serum antibody level of the vaccine, which increased significantly after immunization and reached the peak at 21 day post‐vaccination. T‐AOC and AKP activities in the lowest concentration group (5 μg) of PEG‐G3 were significantly higher than those in the highest concentration group (20 μg) of G3. In PEG‐G3 group, the expression of almost all genes increased at least 4 times compared with the control group. After 14‐day challenge, the RPS (relative percentage survival) of the highest concentration of PEG‐G3 group was 53.6%, while that of G3 group is 38.9%. Therefore, this work shows that PEG modification and dominant epitope screening may be effective methods to improve the immune protective effect of vaccines and to resist the infection of aquatic animal viral diseases.

Developing a two-step improved damage creep constitutive model based on soft rock saturation-loss cycle triaxial creep test - Anrun Li; Hui Deng; Haojie Zhang; Mingliang Jiang; Hanhan Liu; Yuyue Xiao; Jing Wen (Natural Hazards, 2021)

Effect of spatial scale on gully distribution in northeastern China - Houling Wang; Jun Luo; Wei Qin; Bin Zhang; Hui Liu; Qingchun Deng; Fachao Qin; Fuhua Xuan (Modeling Earth Systems and Environment, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Precipitation and nitrogen application stimulate soil nitrous oxide emission - Huiling Zhang; Qi Deng; Christopher W. Schadt; Melanie A. Mayes; Deqiang Zhang; Dafeng Hui (Nutrient Cycling in Agroecosystems, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

RETRACTED ARTICLE: ZFAS1 Promotes Colorectal Cancer Metastasis Through Modulating miR-34b/SOX4 Targeting - Hong Deng; Mingming Wang; Qin Xu; Hui Yao (Cell Biochemistry and Biophysics, 2021)

Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community - Hui Li; Shan Yang; Mikhail V. Semenov; Fei Yao; Ji Ye; Rencang Bu; Ruiao Ma; Junjie Lin; Irina Kurganova; Xugao Wang; Ye Deng; Irina Kravchenko; et al. (Global Change Biology, 2021)
Temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q 10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q 10 , SOM quality, and soil microorganisms. We examined the Q 10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate mixed forest ecosystems in parallel with SOM quality and bioavailability, microbial taxonomic composition, and functional genes responsible for organic carbon decomposition. Within this temperature gradient of 7.0°C, the Q 10 values increased with MAT, but decreased with SOM bioavailability. The Q 10 values increased with the prevalence of K‐strategy of soil microbial community, which was characterized by: (i) high ratios of oligotrophic to copiotrophic taxa, (ii) ectomycorrhizal to saprotrophic fungi, (iii) functional genes responsible for degradation of recalcitrant to that of labile C, and (iv) low average 16S rRNA operon copy number. Because the recalcitrant organic matter was mainly utilized by the K‐strategists, these findings independently support the carbon quality‐temperature theory from the perspective of microbial taxonomic composition and functions. A year‐long incubation experiment was performed to determine the response of labile and recalcitrant C pools to warming based on the two‐pool model. The decomposition of recalcitrant SOM was more sensitive to increased temperature in southern warm regions, which might attribute to the dominance of K‐selected microbial communities. It implies that climate warming would mobilize the larger recalcitrant pools in warm regions, exacerbating the positive feedback between increased MAT and CO 2 efflux. This is the first attempt to link temperature sensitivity of SOM decomposition with microbial eco‐strategies by incorporating the genetic information and disentangling the complex relationship between Q 10 and soil microorganisms.

Phylogeny and taxonomy of two new Alternaria (Ascomycota: Pleosporaceae) species in section Gypsophilae from China - Lin He; Hong Cheng; Aye Aye Htun; Hui Ge; Zhen Zhou Xia; Jian Wei Guo; Jian Xin Deng; Tao Du (Mycological Progress, 2021)

Morphology and composition of particles emitted from conventional and alternative fuel vehicles - Zhenzhen Lu; Shunxi Deng; Xi Liu; Lihui Huang; Ruixu Zhang; Hui Song; Guanghua Li (Environmental Science and Pollution Research, 2021)

Emission characteristics and ozone formation potentials of gaseous pollutants from in-use methanol-, CNG- and gasoline-fueled vehicles - Zhenzhen Lu; Shunxi Deng; Chanjuan Gao; Guanghua Li; Hui Song; Jianghao Li (Environmental Monitoring and Assessment, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Progress of Studies on Circulation Dynamics in the East China Sea: The Kuroshio Exchanges With the Shelf Currents - Zhiqiang Liu; Jianping Gan; Jianyu Hu; Hui Wu; Zhongya Cai; Yongfei Deng (Frontiers in Marine Science, 2021)
This paper reviews recent advances in the circulation dynamics of the Kuroshio and its interaction with shelf currents in the East China Sea (ECS). The annually averaged Kuroshio volume transport varies between 19 and 24 Sv, based on different observations, but there is no consensus on which season its volume transport peaks. The Kuroshio is intensified over the central slope of the ECS from that off the northeast of Taiwan. The total Kuroshio intrusion into the ECS shelf is estimated to be 1.3–1.4 Sv, deduced from the observed volume transport of exchange flow in the Taiwan and Tsushima Straits, based on the assumption of volume conversation over the shelf. However, the uncertainty regarding this estimation remains due to the absence of sufficient observations and understanding of the Kuroshio dynamics. The Kuroshio intrusions over the shelf off the northeast of Taiwan and southwest of Kyushu are stimulated by planetary or topographic β -effect associated with the alongshore variations in the ECS slope topography and altered by variations in the Kuroshio intensity, shear stress, and baroclinicity. Multilayered exchanges between the Kuroshio and shelf currents were found between 100- and 200-m isobaths along the central ECS slope. The spatial variations in these exchanges are governed by cross-isobath transport by geostrophy, whereas bottom Ekman transport may play a predominant role in altering the integrated exchange flow along the slope. Although the intrusion is greatly modulated along the path of the Kuroshio in the ECS by variable slope topography, there are few observations on the spatial variations of these exchange flows. The characteristics and variations in the circulation and hydrographic properties of waters between 100- and 200-m isobaths significantly determine the general ECS circulation, about which consensus has still not been attained.

Advances on Coastal and Estuarine Circulations Around the Changjiang Estuary in the Recent Decades (2000–2020) - Zhiqiang Liu; Jianping Gan; Hui Wu; Jianyu Hu; Zhongya Cai; Yongfei Deng (Frontiers in Marine Science, 2021)
Advances on the circulation in the Changjiang Estuary and adjacent East China Sea (ECS) and Yellow Sea (YS) coastal waters in the recent decades (2000–2020) are synthesized in this review. The circulation over the complicated bathymetry in the region is locally driven by winds, tides, as well as riverine discharge, and is remotely influenced by shelf currents between the 50 and 100-m isobaths through the cross-shelf exchanges. The interchange of the momentum and the freshwater pathway inside the Changjiang Estuary are jointly determined by tides and seasonally varying discharge and winds over the shelf. The buoyant waters are trapped inside the bulge that forms and expands over the shelf to the west of the 30-m isobath in the vicinity of Hangzhou Bay and the Changjiang Estuary. These buoyant waters are exported offshore by the shelf current, tidal mixing, and variations of wind patterns, forming the Changjiang River plume, which shows notable seasonality due to the reversal of both winds and shelf currents in the ECS and YS. Extensive spatial irregularities in the form of freshwater patches are present along its pathway to the Tsushima Strait in summer and to the Taiwan Strait in winter, respectively. Tides and the bathymetry irregularity have recently been found to play critical roles in determining the cross-shelf exchanges of water mass and momentum along the pathway of the ECS coastal current, and along this pathway, a year-round upslope intrusion of shelf waters appears in both summer and winter. Tides also play an important role in altering the expansion of the Changjiang River plume, cross-shelf extrusion of waters, and variation in the Yellow Sea Coastal Current over the shallow Subei Shoal.

The reproductive regulation of LPXRFa and its receptor in the hypothalamo-pituitary-gonadal axis of the spotted scat (Scatophagus argus) - Yi Zhai; Si-Ping Deng; Jian-Ye Liu; Dong-Neng Jiang; Yang Huang; Chun-Hua Zhu; Guang-Li Li; Ming-Hui Li (Fish Physiology and Biochemistry, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

EDTAD-modified cassava stalks loaded with Fe3O4: highly efficient removal of Pb2+ and Zn2+ from aqueous solution - Caiyan Kang; Qiuyan Li; Hui Yi; Hua Deng; Weiming Mo; Mianwu Meng; Siyu Huang (Environmental Science and Pollution Research, 2021)

Effects of lithium resource exploitation on surface water at Jiajika mine, China - Juan-Qin Gao; Yang Yu; Deng-Hong Wang; Wei Wang; Cheng-Hui Wang; Hong-Zhang Dai; Xue-Feng Hao; Kuang Cen (Environmental Monitoring and Assessment, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

A Pooled Study of Angiotensin-Converting Enzyme Insertion/Deletion Gene Polymorphism in Relation to Risk, Pathology and Prognosis of Childhood Immunoglobulin A Vasculitis Nephritis - Gao Hui; Zhang Cheng; Hua Ran; Wang Ziwei; Deng Fang (Biochemical Genetics, 2021)

MmbR , a master transcription regulator that controls fatty acid β‐oxidation genes in Mycolicibacterium smegmatis - Hui Xu; Zhi Su; Weihui Li; Yimin Deng; Zheng‐Guo He (Environmental Microbiology, 2021)
Summary An unusually high lipid content and a complex lipid profile are the most distinctive features of the mycobacterial cell envelope. However, our understanding of the regulatory mechanism underlying mycobacterial lipid metabolism is limited, and the major regulators responsible for lipid homeostasis remain to be characterized. Here, we identified MmbR as a novel master regulator that is essential for maintaining lipid homeostasis in Mycolicibacterium smegmatis . We found that MmbR controls fatty acid β‐oxidation and modulates biofilm formation in Mycolicibacterium smegmatis . Although MmbR possesses the properties of nucleoid‐associated proteins, it acts as a TetR‐like transcription factor, directly regulating and intensively repressing the expression of a group of core genes involved in fatty acid β‐oxidation. Furthermore, both long‐chain acyl‐Coenzyme A and fatty acids appear to regulate the signal molecules modulated by MmbR. The deletion of mmbR led to a significant reduction in intracellular fatty acid content and a decrease in the relative lipid composition of the biofilm. The lack of mmbR led to morphological changes in the mycobacterial colony, defects in biofilm formation and enhanced sensitivity to anti‐tuberculosis drugs. Our study is the first to establish a link between the transcriptional regulation of fatty acid β‐oxidation genes and lipid homeostasis in mycobacteria.

Fatigue Characteristic of Designed T-Type Specimen under Two-Step Repeating Variable Amplitude Load with Low-Amplitude Load below the Fatigue Limit - Jin Gan; Di Sun; Hui Deng; Zhou Wang; Xiaoli Wang; Li Yao; Weiguo Wu (Journal of Marine Science and Engineering, 2021)
In order to investigate the non-linear fatigue cumulative damage of joints in ocean structural parts, one type of low carbon steel Q345D was employed to prepare designed T-type specimens, and a series of fatigue experiments were carried out on the specimens under two-step repeating variable amplitude loading condition. The chosen high cyclic loads were larger than the constant amplitude fatigue limit (CAFL) and the chosen low cyclic loads were below the CAFL. Firstly, the S-N curve of designed T-type specimen was obtained via different constant amplitude fatigue tests. Then, a series of two-step repeating variable load were carried out on designed T-type specimens with the aim of calculating the cumulative damage of specimen under the variable fatigue load. The discussions about non-linear fatigue cumulative damage of designed T-type specimens and the interaction effect between the high and low amplitude loadings on the fatigue life were carried out, and some meaningful conclusions were obtained according to the series of fatigue tests. The results show that fatigue cumulative damage of designed T-type specimens calculated based on Miner’s rule ranges from 0.513 to 1.756. Under the same cycle ratio, the cumulative damage increases with the increase of high cyclic stress, and at the same stress ratio, the cumulative damage increases linearly with the increase of cycle ratio. Based on the non-linear damage evaluation method, it is found that the load interaction effect between high and low stress loads exhibits different damage or strengthening effects with the change of stress ratio and cycle ratio.

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Identifying a Carotenoid Cleavage Dioxygenase (CCD4) Gene Controlling Yellow/White Fruit Flesh Color of “Piqiutao” (White Fruit Flesh) and Its Mutant (Yellow Fruit Flesh) - Lu Wen; Yongqing Wang; Qunxian Deng; Min Hong; Si Shi; Shanshan He; Yan Huang; Hui Zhang; Cuiping Pan; Zhiwu Yang; Zhuoheng Chi; Yunmiao Yang (Plant Molecular Biology Reporter, 2020)
To better understand the fruit flesh coloration mechanism of peach ( Prunus persica ), the composition and accumulation of carotenoids were compared, the expression profile of key genes involved in carotenoid biosynthetic and catabolic pathways was performed, and the differentially expressed genes were identified using “Piqiutao” (white fruit flesh) and its mutant yellow “Piqiutao” at different fruit development stages. The results showed that the total carotenoid content in yellow “Piqiutao” was remarkably higher than that of “Piqiutao,” and the accumulation of β-cryptoxanthin, α-carotene, and β-carotene was significantly different, which was most likely caused by the differential expression of CCD4 . Therefore, CCD4 may be an essential gene that causes the yellow fruit flesh of yellow “Piqiutao.” However, the coding region sequence of CCD4 was entirely identical, and the intron was inserted by a retrotransposon in “Piqiutao” and its mutant, indicating that the expression difference was not caused by the sequence mutation and retrotransposon insertion.

Grafting Alleviates Cadmium Toxicity and Reduces Its Absorption by Tomato - Yongdong Xie; Huaqiang Tan; Guochao Sun; Huanxiu Li; Dong Liang; Hui Xia; Xun Wang; Ming’an Liao; Honghong Deng; Jin Wang; Yi Tang (Journal of Soil Science and Plant Nutrition, 2020)

Self-adaptively inpainting gaps between electrical image pads according to the image fabric - Zhao-hui Zhang; Jing Deng; Hua-yong Chen; Hong-guo Yu (Applied Geophysics, 2020)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Massilia aquatica sp. nov., Isolated from a Subtropical Stream in China - Hui-Bin Lu; Tong-Chu Deng; Mei-Ying Xu (Current Microbiology, 2020)

Evaluation of the production-living-ecology space function suitability of Pingshan County in the Taihang mountainous area, China - Shu-hui Yu; Wei Deng; You-xin Xu; Xia Zhang; Hao-lin Xiang (Journal of Mountain Science, 2020)

Depletion of florfenicol and florfenicol amine in eggs of laying hens and growing pullets after oral administration - Xia Li; Lu Chen; Hui Yue; Hua Feng; Enmin Xu; Xiuli Wei; Xiaoli Han; Ligang Deng; Zengmei Li (Food Additives & Contaminants: Part A, 2020)

Experimentally Induced Sepsis Causes Extensive Hypomyelination in the Prefrontal Cortex and Hippocampus in Neonatal Rats - Peixian Huang; Xuan Chen; Xiaoli Hu; Qiuping Zhou; Lanfen Lin; Shuqi Jiang; Hui Fu; Yajie Xiong; Hongke Zeng; Ming Fang; Chunbo Chen; Yiyu Deng (NeuroMolecular Medicine, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Deep-Seated Large-Scale Toppling Failure: A Case Study of the Lancang Slope in Southwest China - Guoxiang Tu; Hui Deng; Qi Shang; Yin Zhang; Xinping Luo (Rock Mechanics and Rock Engineering, 2020)

The role of HINT1 in methamphetamine-induced behavioral sensitization - Peng Liu; Gang Lei; Zheng Chu; Li-sha Deng; Liu Yang; Jun-liang He; Yong-hui Dang (Psychopharmacology, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Formation and evolution of a successive landslide dam by the erosion of river: a case study of the Gendakan landslide dam on the Lancang River, China - Guoxiang Tu; Hui Deng (Bulletin of Engineering Geology and the Environment, 2020)

Global response patterns of plant photosynthesis to nitrogen addition: A meta‐analysis - Xingyun Liang; Tong Zhang; Xiankai Lu; David S. Ellsworth; Hormoz BassiriRad; Chengming You; Dong Wang; Pengcheng He; Qi Deng; Hui Liu; Jiangming Mo; Qing Ye (Global Change Biology, 2020)
A mechanistic understanding of plant photosynthetic response is needed to reliably predict changes in terrestrial carbon (C) gain under conditions of chronically elevated atmospheric nitrogen (N) deposition. Here, using 2,683 observations from 240 journal articles, we conducted a global meta‐analysis to reveal effects of N addition on 14 photosynthesis‐related traits and affecting moderators. We found that across 320 terrestrial plant species, leaf N was enhanced comparably on mass basis ( N mass , +18.4%) and area basis ( N area , +14.3%), with no changes in specific leaf area or leaf mass per area. Total leaf area (TLA) was increased significantly, as indicated by the increases in total leaf biomass (+46.5%), leaf area per plant (+29.7%), and leaf area index (LAI, +24.4%). To a lesser extent than for TLA, N addition significantly enhanced leaf photosynthetic rate per area ( A area , +12.6%), stomatal conductance ( g s , +7.5%), and transpiration rate ( E , +10.5%). The responses of A area were positively related with that of g s , with no changes in instantaneous water‐use efficiency and only slight increases in long‐term water‐use efficiency (+2.5%) inferred from 13 C composition. The responses of traits depended on biological, experimental, and environmental moderators. As experimental duration and N load increased, the responses of LAI and A area diminished while that of E increased significantly. The observed patterns of increases in both TLA and E indicate that N deposition will increase the amount of water used by plants. Taken together, N deposition will enhance gross photosynthetic C gain of the terrestrial plants while increasing their water loss to the atmosphere, but the effects on C gain might diminish over time and that on plant water use would be amplified if N deposition persists.

A new diterpenoid alkaloid from Aconitum hemsleyanum - Zhi-Hui Luo; Yang Chen; Xin-Yi Sun; Hua Fan; Wei Li; Liang Deng; Tian-Peng Yin (Natural Product Research, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

Ribosome profiling analysis identified a KRAS-interacting microprotein that represses oncogenic signaling in hepatocellular carcinoma cells - Wenli Xu; Bing Deng; Penghui Lin; Chang Liu; Bin Li; Qiaojuan Huang; Hui Zhou; Jianhua Yang; Lianghu Qu (Science China Life Sciences, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Retraction Note to: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2020)

Responses of soil moisture to regional climate change over the Three Rivers Source Region on the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Zhaoguo Li; Yaqiong Lyv; Huajin Lei; Lin Zhao; Shengnan Zhao; Jun Ge; Hui Jing (International Journal of Climatology, 2020)
In this study, soil moisture data from two reanalysis datasets (ERA‐Interim, ERA5), a satellite soil moisture product from the European Space Agency (ESA) and three assimilation datasets from the Global Land Data Assimilation System (GLDAS), that is, GLADS‐NOAH025, GLADS‐NOAH10, and GLDAS‐CLM were compared with the observed soil moisture data in Maqu and Maduo stations over the Three Rivers Source Region (TRSR) on the Tibetan Plateau in China. Comparative statistical parameters between the soil moisture observations and the products, including the root mean square error, correlation coefficient ( R ), and standard deviation ratio were calculated to evaluate the products in different seasons. It was found that most products overestimated the soil moisture values, among which GLADS‐NOAH025 had relatively good consistency with the observations in the surface soil layer (0–10 cm), whereas GLDAS‐CLM agreed well with the observations in the 10–40 cm layer. Both ERA5 and ERA‐interim soil moisture overestimated soil moisture at all levels. The responses of soil moisture to regional climate change over the TRSR were also investigated by using the GLDAS‐NOAH025 soil moisture product, the ESA soil moisture product, and the observations during the nonfreezing period. The results show that the trends of soil moisture are consistent with the precipitation changes in the main central part of the TRSR. A significant positive correlation was found between soil moisture and precipitation in most regions of the TRSR, which indicates that soil moisture increases with the increase of precipitation, except in the northwest TRSR, where the variation of soil moisture was possibly influenced by both the precipitation changes and the increase of evapotranspiration.

Laboratory Investigation on Shear Behaviors of Bolt–Grout Interface Subjected to Constant Normal Stiffness - Chuanqing Zhang; Guojian Cui; Liang Deng; Hui Zhou; Jingjing Lu; Feng Dai (Rock Mechanics and Rock Engineering, 2020)

Effects of reciprocal hybridization on cadmium accumulation in F1 hybrids of two Solanum photeinocarpum ecotypes - Lijin Lin; Caifang Wu; Jin Wang; Ming’an Liao; Daiyu Yang; Honghong Deng; Xiulan Lv; Hui Xia; Dong Liang; Qunxian Deng (Environmental Science and Pollution Research, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Variation of rill cross-sections with gravel and aggregating soil in the Dry-Hot Valley (SW China) - Nana Wang; Lin Ding; Gangcai Liu; Qingchun Deng; Hui Liu; Jie Wang; Wei Lv; Jun Luo; Ziyin Du; Bin Zhang (Modeling Earth Systems and Environment, 2019)

Effects of mining speed on the developmental features of mining-induced ground fissures - Hui Liu; Kazhong Deng; Xiaojun Zhu; Chunlu Jiang (Bulletin of Engineering Geology and the Environment, 2019)

Micro-failure Analysis of Direct and Flat Loading Brazilian Tensile Tests - Yan-Sheng Wang; Jian-Hui Deng; Lin-Rui Li; Zheng-Hu Zhang (Rock Mechanics and Rock Engineering, 2019)

RETRACTED ARTICLE: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2019)

Accumulation and Depuration of Nonylphenol and Its Effect on the Expressions of Vitellogenin and Vitellogenin Receptor in Freshwater Prawn Macrobrachium rosenbergii - Hui Guo; Luan-luan Chen; Guang-li Li; Si-ping Deng; Chun-hua Zhu (Bulletin of Environmental Contamination and Toxicology, 2019)

An indole diterpenoid isolated from the fungus Drechmeria sp. and its antimicrobial activity - Jia-Hao Liang; Xiao-Kui Huo; Zhong-Bin Cheng; Cheng-Peng Sun; Jian-Chao Zhao; Xiao-Hui Kang; Tian-Yuan Zhang; Zhong-Jian Chen; Tian-Mei Yang; Ying-Ying Wu; Xiao-Peng Deng; Yi-Xuan Zhang (Natural Product Research, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Effect of locally accumulated crushed stone soil on the infiltration of intense rainfall: a case study on the reactivation of an old deep landslide deposit - Guoxiang Tu; Da Huang; Runqiu Huang; Hui Deng (Bulletin of Engineering Geology and the Environment, 2019)

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Magnetotelluric extremum boundary inversion based on different stabilizers and its application in a high radioactive waste repository site selection - Xian-Yang Huang; Ju-Zhi Deng; Xiao Chen; Xian-Xiang Wang; Hui Chen; Hui Yu (Applied Geophysics, 2019)

Correction to: Expression and Function of Zinc-α2-Glycoprotein - Xin Wei; Xi Liu; Changhong Tan; Lijuan Mo; Hui Wang; Xi Peng; Fen Deng; Lifen Chen (Neuroscience Bulletin, 2019)

Effects of intercropping with floricultural accumulator plants on cadmium accumulation in grapevine - Hongqiang Chen; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Qunxian Deng; Xun Wang; Xiulan Lv; Wei Ren (Environmental Science and Pollution Research, 2019)

Skipping of an exon with a nonsense mutation in the DMD gene is induced by the conversion of a splicing enhancer to a splicing silencer - Yanrong Zhu; Huiting Deng; Xiangfa Chen; Hui Li; Cheng Yang; Shuo Li; Xiaoying Pan; Siqi Tian; Shuxin Feng; Xiaoyue Tan; Masafumi Matsuo; Zhujun Zhang (Human Genetics, 2019)

Expression and Function of Zinc-α2-Glycoprotein - Xin Wei; Xi Liu; Changhong Tan; Lijuan Mo; Hui Wang; Xi Peng; Fen Deng; Lifeng Chen (Neuroscience Bulletin, 2019)

Three forms of cocaine- and amphetamine-regulated transcript may be involved in food intake regulation in gibel carp (Carassius auratus gibelio) - Chaowei Zhou; Luo Lei; Xingxing Deng; Dengyue Yuan; Chengke Zhu; Hua Ye; Hui Luo; Chi Zhang; Jianshe Zhou; Minmin Yang; Jian Wang; Benhe Zeng; et al. (Fish Physiology and Biochemistry, 2019)

Altitudinal variation in body size in Bufo minshanicus supports Bergmann’s rule - Tong Lei Yu; Dong Li Wang; Michael Busam; Yao Hui Deng (Evolutionary Ecology, 2019)

Phosphate adsorption from wastewater using ZnAl-LDO-loaded modified banana straw biochar - Yan-Hong Jiang; An-Yu Li; Hua Deng; Cheng-Hui Ye; Yi Li (Environmental Science and Pollution Research, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Soil microbiome mediated nutrients decline during forest degradation process - Yangying Liu; Shang Wang; Zhujun Wang; Zhaojing Zhang; Huayu Qin; Ziyan Wei; Kai Feng; Shuzhen Li; Yueni Wu; Huaqun Yin; Hui Li; Ye Deng (Soil Ecology Letters, 2019)

Multiple parapatric pollinators have radiated across a continental fig tree displaying clinal genetic variation - Hui Yu; Enwei Tian; Linna Zheng; Xiaoxia Deng; Yufen Cheng; Lianfu Chen; Wei Wu; Wattana Tanming; Dayong Zhang; Stephen G. Compton; Finn Kjellberg (Molecular Ecology, 2019)
The ways that plant‐feeding insects have diversified are central to our understanding of terrestrial ecosystems. Obligate nursery pollination mutualisms provide highly relevant model systems of how plants and their insect associates have diversified and the over 800 species of fig trees ( Ficus ) allow comparative studies. Fig trees can have one or more pollinating fig wasp species (Agaonidae) that breed within their figs, but factors influencing their number remain to be established. In some widely distributed fig trees, the plants form populations isolated by large swathes of sea, and the different populations are pollinated by different wasp species. Other Ficus species with continuous distributions may present genetic signatures of isolation by distance, suggesting more limited pollinator dispersal, which may also facilitate pollinator speciation. We tested the hypothesis that Ficus hirta , a species for which preliminary data showed genetic isolation by distance, would support numerous pollinator species across its range. Our results show that across its range F. hirta displays clinal genetic variation and is pollinated by nine parapatric species of Valisia . This is the highest number of pollinators reported to date for any Ficus species, and it is the first demonstration of the occurrence of parapatric pollinator species on a fig host displaying continuous genetic structure. Future comparative studies across Ficus species should be able to establish the plant traits that have driven the evolution of pollinator dispersal behaviour, pollinator speciation and host plant spatial genetic structure.

Pterostilbene, an active component of the dragon’s blood extract, acts as an antidepressant in adult rats - Liang Yang; Yuanyuan Ran; Zhenzhen Quan; Ran Wang; Qinghu Yang; Qiutian Jia; Heao Zhang; Yanhui Li; Yiheng Peng; JianHua Liang; Hui Wang; Hiroshi Nakanishi; et al. (Psychopharmacology, 2019)

Deletion of the Type IV Secretion System Effector VceA Promotes Autophagy and Inhibits Apoptosis in Brucella-Infected Human Trophoblast Cells - Jing Zhang; Min Li; Zhiqiang Li; Jingxue Shi; Yu Zhang; Xingmei Deng; Liangbo Liu; Zhen Wang; Yayin Qi; Hui Zhang (Current Microbiology, 2019)

Reactivation of a huge ancient landslide by surface water infiltration - Guo-xiang Tu; Da Huang; Hui Deng (Journal of Mountain Science, 2019)

Durability classification of red beds rocks in central Yunnan based on particle size distribution and slaking procedure - Jun-jie Zhu; Hui Deng (Journal of Mountain Science, 2019)

cAMP/PKA signalling pathway regulates redox homeostasis essential for Sporisorium scitamineum mating/filamentation and virulence - Changqing Chang; Enping Cai; Yi Zhen Deng; Dan Mei; Shanxu Qiu; Baoshan Chen; Lian‐Hui Zhang; Zide Jiang (Environmental Microbiology, 2019)
Summary The fungal pathogen Sporisorium scitamineum causes sugarcane smut disease. The formation and growth of dikaryotic hypha after sexual mating is critical for S. scitamineum pathogenicity, however regulation of S. scitimineum mating has not been studied in detail. We identified and characterized the core components of the conserved cAMP/PKA pathway in S. scitamineum by reverse genetics. Our results showed that cAMP/PKA signalling pathway is essential for proper mating and filamentation, and thus critical for S. scitamineum virulence. We further demonstrated that an elevated intracellular ROS (reactive oxygen species) level promotes S. scitamineum mating‐filamentation, via transcriptional regulation of ROS catabolic enzymes, and is under regulation of the cAMP/PKA signalling pathway. Furthermore, we found that fungal cAMP/PKA signalling pathway is also involved in regulation of host ROS response. Overall, our work displayed a positive role of elevated intracellular ROS in fungal differentiation and virulence.

Integrative genomic analysis predicts novel functional enhancer-SNPs for bone mineral density - Chuan Qiu; Hui Shen; Xiaoying Fu; Chao Xu; Qing Tian; Hongwen Deng (Human Genetics, 2019)

A thiopyran derivative with low murine toxicity with therapeutic potential on lung cancer acting through a NF-κB mediated apoptosis-to-pyroptosis switch - Liping Chen; Bixia Weng; Huimin Li; Haonan Wang; Qian Li; Xiaoyan Wei; Hui Deng; Sicen Wang; Chengxi Jiang; Renyu Lin; Jianzhang Wu (Apoptosis, 2019)

Phthalate esters in bottled drinking water and their human exposure in Beijing, China - Hui Li; Chunmei Li; Lihui An; Chao Deng; Hang Su; Lufang Wang; Zejun Jiang; Jie Zhou; Jing Wang; Chenghui Zhang; Fen Jin (Food Additives & Contaminants Part B-Surveillance, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Physiological and anatomical response of foliar silicon application to Dendrocalamus brandisii plantlet leaves under chilling - Hui Zhan; Li-ya Zhang; Lin Deng; Zhao-hui Niu; Mao-biao Li; Chang-ming Wang; Shuguang Wang (Acta Physiologiae Plantarum, 2018)

The morphological characteristics of gully systems and watersheds in Dry-Hot Valley, SW China - Zhen Xu; Fachao Qin; Bin Zhang; Qingchun Deng; Hui Liu; Jie Jin; Liangtao Shi (Acta Geochimica, 2018)

Fatigue damage evolution of coal under cyclic loading - Yong-Jie Yang; Lu-Yi Xing; Hui-Qiang Duan; Lei Deng; Yan-Chao Xue (Arabian Journal of Geosciences, 2018)

An Experimental Investigation of the Failure Mechanisms of Jointed and Intact Marble under Compression Based on Quantitative Analysis of Acoustic Emission Waveforms - Zheng-Hu Zhang; Jian-Hui Deng; Jian-Bo Zhu; Lin-Rui Li (Rock Mechanics and Rock Engineering, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Role of the Golgi Apparatus in the Blood-Brain Barrier: Golgi Protection May Be a Targeted Therapy for Neurological Diseases - Shuwen Deng; Hui Liu; Ke Qiu; Hong You; Qiang Lei; Wei Lu (Molecular Neurobiology, 2018)

Effect of overexpression of LPAAT and GPD1 on lipid synthesis and composition in green microalga Chlamydomonas reinhardtii - Chaogang Wang; Yi Li; Jun Lu; Xu Deng; Hui Li; Zhangli Hu (Journal of Applied Phycology, 2018)

Unexpected fungal communities in the Rehai thermal springs of Tengchong influenced by abiotic factors - Kai-Hui Liu; Xiao-Wei Ding; Nimaichand Salam; Bo Zhang; Xiao-Fei Tang; Baiwan Deng; Wen-Jun Li (Extremophiles, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

Inferring causal relationships between phenotypes using summary statistics from genome-wide association studies - Xiang-He Meng; Hui Shen; Xiang-Ding Chen; Hong-Mei Xiao; Hong-Wen Deng (Human Genetics, 2018)

Soil microbial beta-diversity is linked with compositional variation in aboveground plant biomass in a semi-arid grassland - Hui Li; Zhuwen Xu; Qingyun Yan; Shan Yang; Joy D. Van Nostrand; Zhirui Wang; Zhili He; Jizhong Zhou; Yong Jiang; Ye Deng (Plant and Soil, 2018)

Correction to: Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbing Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbin Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

Improved detection of genetic loci in estimated glomerular filtration rate and type 2 diabetes using a pleiotropic cFDR method - Hui-Min Liu; Jing-Yang He; Qiang Zhang; Wan-Qiang Lv; Xin Xia; Chang-Qing Sun; Wei-Dong Zhang; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

The Polyclonal Antibodies Induced by VBP3 Complex Peptide Targeting Angiogenesis and Tumor Suppression - Yanrui Deng; Hui Liang; Lei Pan; Ruiqiang Weng; Ligang Zhang; Zhitao Wan; Xuejun Lao; Qing Zhang; Likuan Xiong; Ning Deng (International Journal of Peptide Research and Therapeutics, 2017)

Responses of switchgrass soil respiration and its components to precipitation gradient in a mesocosm study - Chih-Li Yu; Dafeng Hui; Qi Deng; E. Kudjo Dzantor; Philip A. Fay; Weijun Shen; Yiqi Luo (Plant and Soil, 2017)

Phylogenetic analysis of Plectosphaerella species based on multi-locus DNA sequences and description of P. sinensis sp. nov. - Lei Su; Hui Deng; Yong-Chun Niu (Mycological Progress, 2017)

Spatial distribution and dynamics of carbon storage in natural Larix gmelinii forest in Daxing’anling mountains of Inner Mongolia, northeastern China - Sheng-wang Meng; Qi-jing Liu; Quan-quan Jia; Hui-xia Zhuang; Ying Qi; Cheng-xue Lu; Liu-bao Deng (Journal of Mountain Science, 2017)

Molecular analysis and biochemical characteristics of degenerated strains of Cordyceps militaris - Shu-Jing Sun; Chang-Huan Deng; Liao-Yuan Zhang; Kai-Hui Hu (Archives of Microbiology, 2017)

The microbially mediated soil organic carbon loss under degenerative succession in an alpine meadow - Yuguang Zhang; Xiao Liu; Jing Cong; Hui Lu; Yuyu Sheng; Xiulei Wang; Diqiang Li; Xueduan Liu; Huaqun Yin; Jizhong Zhou; Ye Deng (Molecular Ecology, 2017)
Land‐cover change has long been recognized as having marked effect on the amount of soil organic carbon ( SOC ). However, the microbially mediated processes and mechanisms on SOC are still unclear. In this study, the soil samples in a degenerative succession from alpine meadow to alpine steppe meadow in the Qinghai–Tibetan Plateau were analysed using high‐throughput technologies, including Illumina sequencing and geochip functional gene arrays. The soil microbial community structure and diversity were significantly ( p p SOC and nutrients medicated by changing soil microbial community structure and their functional potentials for carbon decomposition.

The Diagnostic Value of (1 → 3)-Beta-d-glucans and Galactomannan Assays in Children Suffering from Bacteremia in Pediatric Intensive Care Unit - Fang Zheng; Yelian Gu; Hui Zha; Jun Deng; Zhiquan Zhang (Mycopathologia, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

The complete mitochondrial genome of the monophagous moth Protegira songi (Lepidoptera: Noctuidae) - Guo Xiao-Hui; Cheng Ming-Yang; Hou Ya-Feng; Deng Tuan-Tuan; Zhao Sha; Yu Hai-Li; Xing Lian-Xi (Conservation Genetics Resources, 2017)

Responses of terrestrial ecosystem phosphorus cycling to nitrogen addition: A meta‐analysis - Qi Deng; Dafeng Hui; Sam Dennis; K. Chandra Reddy (Global Ecology and Biogeography, 2017)
Aim Anthropogenic additions of nitrogen (N) are expected to drive terrestrial ecosystems toward greater phosphorus (P) limitation. However, a comprehensive understanding of how an ecosystem's P cycle responds to external N inputs remains elusive, making model predictions of the anthropogenic P limitation and its impacts largely uncertain. Location Global. Time period 1986‐2015. Major taxa studied Terrestrial ecosystems. Methods We conducted a meta‐analysis including 288 independent study sites from 192 articles to evaluate global patterns and controls of 10 variables associated with ecosystem P cycling under N addition. Results Overall, N addition increased biomass in plants (+34%) and litter (+15%) as well as plant P content (+17%), while decreasing P concentrations in plants and litter (−8% and −11%, respectively). N addition did not change soil labile P or microbial P, but enhanced phosphatase activity (+24%). The effects of N addition on the litter P pool and soil total P remained unclear due to significant publication biases. The response of P cycling to N addition in tropical forests was different from that in other ecosystem types. N addition did not change plant biomass or phosphatase activity in tropical forests but significantly reduced plant P and soil labile P concentrations. The shift in plant P concentration under N addition was negatively correlated with the N application rate or total N load. N‐induced change in soil labile P was strongly regulated by soil pH value at the control sites, with a significant decrease of 14% only in acidic soils (pH Main conclusions Our results suggest that as anthropogenic N enhancement continues in the future it could induce P limitation in terrestrial ecosystems while accelerating P cycling, particularly in tropical forests. A quantitative framework generated on the basis of this meta‐analysis is useful for our understanding of ecosystem P cycling with N addition, and for incorporating the anthropogenic P limitation into ecosystem models used to analyse effects of future climate change.

Two new coumarins from the bark of Streblus indicus (Bur.) Corner - Ruijie He; Shengping Deng; Hui Nie; Yan Huang; Buming Liu; Ruiyun Yang; Shuai Huang; Dexiong Zhou; Huangcan Chen; Jun Li; Yanjun Zhang (Natural Product Research, 2017)

Using stable hydrogen and oxygen isotopes to study water movement in soil-plant-atmosphere continuum at Poyang Lake wetland, China - Xiang Zhang; Yang Xiao; Hui Wan; Zhimin Deng; Guoyan Pan; Jun Xia (Wetlands Ecology and Management, 2017)

Molecular cloning and characterization of S-adenosylmethionine decarboxylase gene in rubber tree (Hevea brasiliensis) - Manman Zhao; Hui Liu; Zhi Deng; Jiangshu Chen; Hong Yang; Huiping Li; Zhihui Xia; Dejun Li (Physiology and Molecular Biology of Plants, 2017)

Diagnostic Values and Limitations of (1,3)-β-d-Glucans and Galactomannan Assays for Invasive Fungal Infection in Patients Admitted to Pediatric Intensive Care Unit - Fang Zheng; Hui Zha; Dandan Yang; Jun Deng; Zhiquan Zhang (Mycopathologia, 2017)

miR-200a controls hepatic stellate cell activation and fibrosis via SIRT1/Notch1 signal pathway - Jing-Jing Yang; Hui Tao; Li-Ping Liu; Wei Hu; Zi-Yu Deng; Jun Li (Inflammation Research, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Tourism sectorization opportunity spectrum model and space partition of tourism urbanization area: a case of the Mayangxi ecotourism area, Fujian province, China - Hui Tao; Jia-ming Liu; Yu Deng; Ao Du (Journal of Mountain Science, 2017)

Three-dimensional forward modeling of DC resistivity using the aggregation-based algebraic multigrid method - Hui Chen; Ju-Zhi Deng; Min Yin; Chang-Chun Yin; Wen-Wu Tang (Applied Geophysics, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Molecular characterization of HOXC8 gene and methylation status analysis of its exon 1 associated with the length of cashmere fiber in Liaoning cashmere goat - Wen L. Bai; Jiao J. Wang; Rong H. Yin; Yun L. Dang; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang; Hui L. Xue (Genetica, 2017)

Activated carbon adsorptive removal of azo dye and peroxydisulfate regeneration: from a batch study to continuous column operation - Jing Li; Yue Du; Bin Deng; Kangmeng Zhu; Hui Zhang (Environmental Science and Pollution Research, 2017)

A Sfp-type phosphopantetheinyl transferase ZmsO is essential for zeamines production and the virulence of Dickeya zeae - Yingying Cheng; Lisheng Liao; Changqing Chang; Jianuan Zhou; Yinyue Deng; Lian-Hui Zhang (European Journal of Plant Pathology, 2016)

A new crowdsourcing model to assess disaster using microblog data in typhoon Haiyan - Qing Deng; Yi Liu; Hui Zhang; Xiaolong Deng; Yefeng Ma (Natural Hazards, 2016)

The PI3K/Akt/mTOR pathway regulates the replicative senescence of human VSMCs - Pan Tan; Yan-Jiao Wang; Shuang Li; Yi Wang; Je-Yu He; Yi-Yin Chen; Hui-Qian Deng; Wu Huang; Jun-Kun Zhan; You-Shuo Liu (Molecular and Cellular Biochemistry, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Petrography and geochemistry of the Paleogene sandstones from the Ningnan Basin, NW China: implications for provenance, weathering and tectonic setting - Yan Zhao; Chiyang Liu; Dongdong Zhang; Hui Deng; Xiaochen Zhao (Arabian Journal of Geosciences, 2016)

Performance of a pilot-scale wet electrostatic precipitator for the control of sulfuric acid mist - Jiayu Huang; Hongmei Wang; Yingjie Shi; Fan Zhang; Xiaoqing Dang; Hui Zhang; Yun Shu; Shuang Deng; Yu Liu (Environmental Science and Pollution Research, 2016)

First report of human salivirus/klassevirus in respiratory specimens of a child with fatal adenovirus infection - Na Pei; Jiaosheng Zhang; Jinmin Ma; Liqiang Li; Meng Li; Jiandong Li; Yisuo Sun; Jingkai Ji; Hui Jiang; Yong Hou; Fengping Xu; Haorong Lu; et al. (Virus Genes, 2016)

Experimental Study of High-Temperature Fracture Propagation in Anthracite and Destruction of Mudstone from Coalfield Using High-Resolution Microfocus X-ray Computed Tomography - Yang Xiao; Jun-Hui Lu; Cai-Ping Wang; Jun Deng (Rock Mechanics and Rock Engineering, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Long-Term Dietary Alpha-Linolenic Acid Supplement Alleviates Cognitive Impairment Correlate with Activating Hippocampal CREB Signaling in Natural Aging Rats - Hui Gao; Peipei Yan; Shun Zhang; Hao Huang; Fenghong Huang; Taoping Sun; Qianchun Deng; Qingde Huang; Sijing Chen; Keqiang Ye; Jiqu Xu; Liegang Liu (Molecular Neurobiology, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Estimating crop chlorophyll content with hyperspectral vegetation indices and the hybrid inversion method - Liang Liang; Zhihao Qin; Shuhe Zhao; Liping Di; Chao Zhang; Meixia Deng; Hui Lin; Lianpeng Zhang; Lijuan Wang; Zhixiao Liu (International Journal of Remote Sensing, 2016)

PPARGC1B gene is associated with Kashin-Beck disease in Han Chinese - Yan Wen; Jingcan Hao; Xiao Xiao; Wenyu Wang; Xiong Guo; Weimin Lin; Tielin Yang; Xiaogang Liu; Hui Shen; Lijun Tan; Xiangding Chen; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Noncoding RNA as regulators of cardiac fibrosis: current insight and the road ahead - Hui Tao; Jing-Jing Yang; Wei Hu; Kai-Hu Shi; Zi-Yu Deng; Jun Li (Pflügers Archiv - European Journal of Physiology, 2016)

A new thalloid liverwort: Pallaviciniites sandaolingensis sp. nov. from the Middle Jurassic of Turpan–Hami Basin, NW China - Rui-Yun Li; Xue-lian Wang; Jing-Wei Chen; Sheng-Hui Deng; Zi-Xi Wang; Jun-Ling Dong; Bai-Nian Sun (PalZ, 2016)

Special HMW-GSs and their genes of Triticum turgidum subsp. dicoccoides accession D141 and the potential utilization in common wheat - Xiao-Hui Guo; Ji-Liang Hu; Bi-Hua Wu; Zhen-Zhen Wang; Dong Wang; Deng-Cai Liu; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

A research update on the potential roles of aquaporin 4 in neuroinflammation - Yu-Long Lan; Deng-Yang Fang; Jie Zhao; Tong-Hui Ma; Shao Li (Acta Neurologica Belgica, 2016)

Efficacy of a Fructus mume Extract Combination with Stable Chlorine in Preventing Bacterial Contamination in Frozen Mackerel ( Scomber japonicus ) Fillets - Bin Zhang; Hui-min Lin; Yan Tang; Shang-gui Deng (Journal of Aquatic Food Product Technology, 2016)

Effects of Mudstone Particle Content on Shear Strength of a Crushed Sandstone–Mudstone Particle Mixture - Jun-Jie Wang; Zhen-Feng Qiu; Wen-Jie Deng; Hui-Ping Zhang (Marine Georesources & Geotechnology, 2016)

Phialemoniopsis endophytica sp. nov., a new species of endophytic fungi from Luffa cylindrica in Henan, China - Lei Su; Hui Deng; Yong-Chun Niu (Mycological Progress, 2016)

Diffusible signal factor family signals provide a fitness advantage to Xanthomonas campestris pv. campestris in interspecies competition - Yinyue Deng; Jien Wu; Wenfang Yin; Peng Li; Jianuan Zhou; Shaohua Chen; Fei He; Jun Cai; Lian‐Hui Zhang (Environmental Microbiology, 2016)
Summary Diffusible signal factor (DSF) represents a new class of widely conserved quorum sensing signals, which regulates various biological functions through intra‐ or interspecies signaling. The previous studies identified that there is an antagonistic interaction between Xanthomonas and Bacillus species bacteria in natural ecosystem, but the detailed molecular mechanism of interspecies competition is not clear. This study showed that Xanthomonas campestris pv. campestris ( Xcc ) interfered with morphological transition and sporulation of Bacillus thuringiensis in mixed cultures, whereas abrogation of the DSF synthase RpfF reduced the interference. DSF inhibited B. thuringiensis cell division and sporulation through modulation of ftsZ , which encodes an important cell division protein in bacterial cells. In addition, RpfF is essential for production of six DSF‐family signals in Xcc , which employ the same signaling pathways to regulate biological functions in Xcc and play similar effects on reduction of cell division, sporulation and antibiotic resistance of B. thuringiensis . Furthermore, abrogation of RpfF decreased the competitive capability of Xcc against B. thuringiensis on the surface of Chinese cabbage leaves. Our findings provide new insights into the role of DSF‐family signals in interspecies competition and depict molecular mechanisms with which Xcc competes with B. thuringiensis .

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Climate–growth relationship stability of Picea crassifolia on an elevation gradient, Qilian Mountain, Northwest China - Jing-pin Lei; Xiao-hui Feng; Zheng Shi; Deng-zhong Bai; Wen-fa Xiao (Journal of Mountain Science, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Klf10 regulates odontoblast differentiation and mineralization via promoting expression of dentin matrix protein 1 and dentin sialophosphoprotein genes - Zhuo Chen; Wentong Li; Han Wang; Chunyan Wan; Daoshu Luo; Shuli Deng; Hui Chen; Shuo Chen (Cell and Tissue Research, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Exome sequencing identified FGF12 as a novel candidate gene for Kashin-Beck disease - Feng Zhang; Lanlan Dai; Weimin Lin; Wenyu Wang; Xuanzhu Liu; Jianguo Zhang; Tielin Yang; Xiaogang Liu; Hui Shen; Xiangding Chen; Lijun Tan; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Study of the relationship between variants near CCNL1/LEKR1 and in ADCY5 with low birth weight in a Chinese population - Xuejin Fan; Qi Peng; Yanhua Chen; Zeke Ma; Xiaoguang He; Biying Deng; Hui Huang; Juan Zeng; Chuyun Cheng; Shaoji Liu; Xiaomei Lu (Genes & Genomics, 2015)

Distributive directions of gully system in Yuanmou Dry-hot Valley - Hongli Mu; Qingchun Deng; Bin Zhang; Fachao Qin; Mingliang Luo; Hui Liu; Shoujiang Liu (Arabian Journal of Geosciences, 2015)

Down‐regulation of tissue N:P ratios in terrestrial plants by elevated CO 2 - Qi Deng; Dafeng Hui; Yiqi Luo; James Elser; Ying-Ping Wang; Irakli Loladze; Quanfa Zhang; Sam Dennis (Ecology, 2015)
Increasing atmospheric CO 2 concentrations generally alter element stoichiometry in plants. However, a comprehensive evaluation of the elevated CO 2 impact on plant nitrogen : phosphorus (N:P) ratios and the underlying mechanism has not been conducted. We synthesized the results from 112 previously published studies using meta‐analysis to evaluate the effects of elevated CO 2 on the N:P ratio of terrestrial plants and to explore the underlying mechanism based on plant growth and soil P dynamics. Our results show that terrestrial plants grown under elevated CO 2 had lower N:P ratios in both above‐ and belowground biomass across different ecosystem types. The response ratio for plant N:P was negatively correlated with the response ratio for plant growth in croplands and grasslands, and showed a stronger relationship for P than for N. In addition, the CO 2 ‐induced down‐regulation of plant N:P was accompanied by 19.3% and 4.2% increases in soil phosphatase activity and labile P, respectively, and a 10.1% decrease in total soil P. Our results show that down‐regulation of plant N:P under elevated CO 2 corresponds with accelerated soil P cycling. These findings should be useful for better understanding of terrestrial plant stoichiometry in response to elevated CO 2 and of the underlying mechanisms affecting nutrient dynamics under climate change.

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

NMR-Based Metabolic Profiling Reveals Neurochemical Alterations in the Brain of Rats Treated with Sorafenib - Changman Du; Xue Shao; Ruiming Zhu; Yan Li; Qian Zhao; Dengqi Fu; Hui Gu; Jueying Kong; Li Luo; Hailei Long; Pengchi Deng; Huijuan Wang; et al. (Neurotoxicity Research, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Next-generation sequencing, assembly, and comparative analyses of the latex transcriptomes from two elite Hevea brasiliensis varieties - Dejun Li; Lili Hao; Hui Liu; Manman Zhao; Zhi Deng; Yu Li; Rizhong Zeng; Weimin Tian (Tree Genetics & Genomes, 2015)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Circulating MicroRNA Let-7d in Attention-Deficit/Hyperactivity Disorder - Li Hui Wu; Min Peng; Mei Yu; Qian Lei Zhao; Chao Li; Yu Tong Jin; Yong Jiang; Zhong Yi Chen; Nian Hui Deng; Hui Sun; Xing Zhong Wu (NeuroMolecular Medicine, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Amanita cinereovelata, a new species of Amanita section Lepidella from Bangladesh - Md. Iqbal Hosen; Tai-Hui Li; Wang-Qiu Deng (Mycological Progress, 2015)

Marasmius albopurpureus, a new species of section Globulares from Baili Island, China - Chao-Qun Wang; Tai-Hui Li; Hao Huang; Ye-Wei Xia; Chun-Ying Deng; Wang-Qiu Deng (Mycological Progress, 2015)

Non-isothermal kinetic analysis of thermal decomposition of the Ca-bentonite from Santai, China - Xiang-hui Zhang; Chuan He; Ling Wang; Zhong-quan Li; Miao Deng; Jing Liu; Hong-kui Li; Qian Feng (Mineralogy and Petrology, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Cognitive Improvement Induced by Environment Enrichment in Chronic Cerebral Hypoperfusion Rats: a Result of Upregulated Endogenous Neuroprotection? - Ying Yang; Junjian Zhang; Li Xiong; Min Deng; Jing Wang; Jiawei Xin; Hui Liu (Journal of Molecular Neuroscience, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Construction and characterization of VL–VH tail-parallel genetically engineered antibodies against staphylococcal enterotoxins - Xianzhi He; Lei Zhang; Pengchong Liu; Li Liu; Hui Deng; Jinhai Huang (Immunologic Research, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Urban metabolism based on emergy and slack based model: A case study of Beijing, China - Tao Song; Jianming Cai; Hui Xu; Yu Deng; Fangqu Niu; Zhenshan Yang; Shanshan Du (Chinese Geographical Science, 2015)

Cloning and respond of a cold shock domain protein (CnCSDP) gene to cold stress in noble scallop Chlamys nobilis (Bivalve: Pectinidae) - Ya-Jun Wang; Huai-Ping Zheng; Bo Zhang; He-Lu Liu; Hua-Juan Deng; Long-Hui Deng (Molecular Biology Reports, 2014)

Spatial distribution and potential ecologic risk assessment of heavy metals in the sediments of the Nansi Lake in China - Xuezhi Cao; Yan Shao; Wenjing Deng; Hui Wang; Shiliang Wang (Environmental Monitoring and Assessment, 2014)

Zearalenone degradation by two Pseudomonas strains from soil - Hui Tan; Yanchun Hu; Jie He; Lei Wu; Fei Liao; Biao Luo; Yajun He; Zhicai Zuo; Zhihua Ren; Zhijun Zhong; Guangneng Peng; Junliang Deng (Mycotoxin Research, 2014)

Molecular cloning of α-amanitin and characterization of its expression pattern in different parts and development stages of Amanita exitialis fruitbody - Peng Li; Wang-qiu Deng; Tai-hui Li (Mycological Progress, 2014)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a novel COL4A5 mutation in a Chinese family with X-linked Alport syndrome using exome sequencing - Yi Guo; Jinzhong Yuan; Hui Liang; Jingjing Xiao; Hongbo Xu; Lamei Yuan; Kai Gao; Bin Wu; Yongchang Tang; Xiaorong Li; Hao Deng (Molecular Biology Reports, 2014)

Genome-wide copy number variation study and gene expression analysis identify ABI3BP as a susceptibility gene for Kashin–Beck disease - Feng Zhang; Xiong Guo; Yinping Zhang; Yan Wen; Weizhuo Wang; Sen Wang; Tielin Yang; Hui Shen; Xiangding Chen; Qing Tian; Lijun Tan; Hong-Wen Deng (Human Genetics, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Compaction behaviour and particle crushing of a crushed sandstone particle mixture - Jun-Jie Wang; Hui-Ping Zhang; Ming-Wei Liu; Di-Ping Deng (European Journal of Environmental and Civil Engineering, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

A new species of Amanita section Lepidella from South China - Wang-Qiu Deng; Tai-Hui Li; Peng Li; Zhu L. Yang (Mycological Progress, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

The Chilli Veinal Mottle Virus Regulates Expression of the Tobacco Mosaic Virus Resistance Gene N and Jasmonic Acid/Ethylene Signaling Is Essential for Systemic Resistance Against Chilli Veinal Mottle Virus in Tobacco - Feng Zhu; De-Hui Xi; Xing-Guang Deng; Xing-Ji Peng; He Tang; Ying-Juan Chen; Wei Jian; Hong Feng; Hong-Hui Lin (Plant Molecular Biology Reporter, 2014)

Genetic analysis of the ATP1B4 gene in Chinese Han patients with Parkinson’s disease - Kai Gao; Zhi Song; Hui Liang; Wen Zheng; Xiong Deng; Yi Yuan; Yongxiang Zhao; Hao Deng (Molecular Biology Reports, 2014)

Isolation, Expression, and Characterization of Blue Light Receptor AUREOCHROME Gene From Saccharina japonica (Laminariales, Phaeophyceae) - Yunyan Deng; Jianting Yao; Gang Fu; Hui Guo; Delin Duan (Marine Biotechnology, 2014)

Involvement of the nuclear factor-κB pathway in the adhesion of neutrophils to renal tubular cells after injury induced by neonatal postasphyxial serum - Tao Xiong; Wenbin Dong; Hui Fu; Qingping Li; Cunliang Deng; Xiaoping Lei; Lin Guo (Molecular and Cellular Biochemistry, 2014)

Sphingosine Kinase-1 Activation Causes Acquired Resistance Against Sunitinib in Renal Cell Carcinoma Cells - Hui Gao; Lichun Deng (Cell Biochemistry and Biophysics, 2014)

Two new species, Pythium agreste and P. wuhanense, based on morphological characteristics and DNA sequence data - Yan-Yan Long; Xin Sun; Ji-Guang Wei; Xiang Sun; Ji-Jing Wei; Hui Deng; Liang-Dong Guo (Mycological Progress, 2014)

A trehalose-6-phosphate synthase gene from Saccharina japonica (Laminariales, Phaeophyceae) - Yunyan Deng; Xiuliang Wang; Hui Guo; Delin Duan (Molecular Biology Reports, 2014)

Characterization and cross-species amplification of 11 polymorphic microsatellite loci in Liobagrus marginatoides - Xiang-Yang Jia; Ying-Wen Li; Deng-Qiang Wang; Hui-Wu Tian; Bin Tu; Da-Qing Chen (Conservation Genetics Resources, 2013)

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

Genetic Analysis of the Leucine-Rich Repeat and lg Domain Containing Nogo Receptor-Interacting Protein 1 Gene in Essential Tremor - Hui Liang; Zhi Song; Xiong Deng; Hongbo Xu; Anding Zhu; Wen Zheng; Yongxiang Zhao; Hao Deng (Journal of Molecular Neuroscience, 2013)

Perfluorooctane sulfonate (PFOS) distribution and effect factors in the water and sediment of the Yellow River Estuary, China - Shiliang Wang; Hui Wang; Wenjing Deng (Environmental Monitoring and Assessment, 2013)

Permeability and sedimentation characteristics of pleistocene fluvio-glacial deposits in the Dadu river valley, Southwest China - Guo-xiang Tu; Run-qiu Huang; Hui Deng; Yan-rong Li (Journal of Mountain Science, 2013)

Isolation and characterization of twenty-six microsatellite loci for the tetraploid fish Dabry’s sturgeon (Acipenser dabryanus) - Shu-Huan Zhang; Hui Luo; Hao Du; Deng-Qiang Wang; Qi-Wei Wei (Conservation Genetics Resources, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Global identification of miRNAs and targets in Populus euphratica under salt stress - Bosheng Li; Hui Duan; Jigang Li; Xing Wang Deng; Weilun Yin; Xinli Xia (Plant Molecular Biology, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

Development of InDel markers for Brassica rapa based on whole-genome re-sequencing - Bo Liu; Yan Wang; Wen Zhai; Jie Deng; Hui Wang; Yang Cui; Feng Cheng; Xiaowu Wang; Jian Wu (Theoretical and Applied Genetics, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Occurrence and morphology of crayback-like stalagmites in the Painted Cave of Niah (Sarawak, Malaysia) - Dominique Dodge-Wan; Angela Hui Min Deng; Mohammad Fadhil Abbas (Carbonates and Evaporites, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Preparation and Characterization of Stable pH-Sensitive Vesicles Composed of α-Tocopherol Hemisuccinate - Huan Xu; Yi-Hui Deng; Kai-Qian Wang; Da-Wei Chen (AAPS PharmSciTech, 2012)

miR-210 activates notch signaling pathway in angiogenesis induced by cerebral ischemia - Yuan-Lei Lou; Fei Guo; Fen Liu; Fa-Liang Gao; Peng-Qi Zhang; Xin Niu; Shang-Chun Guo; Jun-Hui Yin; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2012)

Mapping of planation surfaces in the southwest region of Hubei Province, China—Using the DEM-derived painted relief model - Hui Li; Xuya Huang; Qinglu Deng; Timothy M. Kusky; Xiaobin Cai (Journal of Earth Science, 2012)

Biodegradation of 3,4-Dichloroaniline by a Novel Myroides odoratimimus Strain LWD09 with Moderate Salinity Tolerance - Tian Li; Xin-Ping Deng; Jin-Jun Wang; Hui Zhao; Lei Wang; Kun Qian (Water, Air, & Soil Pollution, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

A centrifuge simulated push–pull manoeuvre with subsequent reduced +Gz tolerance - Yan Xu; Bao-Hui Li; Li-Hui Zhang; Zhao Jin; Xiao-Yang Wei; Hong Wang; San-Yuan Wu; Hai-Xia Wang; Quan Wang; Gui-Ding Yan; Lue Deng; Xi-Chen Geng (European Journal of Applied Physiology, 2012)

Study on the spectral and Cu (II) binding characteristics of DOM leached from soils and lake sediments in the Hetao region - Xujing Guo; Jinyuan Jiang; Beidou Xi; Xiaosong He; Hui Zhang; Yu Deng (Environmental Science and Pollution Research, 2012)

Bivariate genome-wide association study suggests that the DARC gene influences lean body mass and age at menarche - Rong Hai; Lei Zhang; YuFang Pei; LanJuan Zhao; Shu Ran; YingYing Han; XueZhen Zhu; Hui Shen; Qing Tian; HongWen Deng (Science China Life Sciences, 2012)

Combined effects of a neutrophil elastase inhibitor (sivelestat sodium) and a free radical scavenger (edaravone) on lipopolysaccharide-induced acute lung injury in rats - Tao Yang; Junjie Zhang; Lulu Sun; Xiaoyan Zhu; Jinbao Li; Jiafeng Wang; Hui Chen; Rui Bao; Xiaoming Deng; Jiong Hou; Yujian Liu (Inflammation Research, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

A new lignan and other constituents from Zanthoxylum armatum DC. - Tao Guo; Hui Xie; Yun-Xia Deng; Sheng-Li Pan (Natural Product Research, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Effects of non-esterified fatty acids on the gluconeogenesis in bovine hepatocytes - Xinwei Li; Xiaobing Li; Ge Bai; Hui Chen; Qinghua Deng; Zhaoxi Liu; Liang Zhang; Guowen Liu; Zhe Wang (Molecular and Cellular Biochemistry, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Geological and geophysical conditions for potential natural gas hydrate resources in southern South China Sea waters - Hailing Liu; Yongjian Yao; Hui Deng (Journal of Earth Science, 2011)

Effects of dietary protein sources on feed intake, growth and plasma thyroid hormones levels of Japanese flounder (Paralichthys olivaceus) - Jun-Ming Deng; Kang-Sen Mai; Qing-Hui Ai; Wen-Bing Zhang; Wei Xu; Zhi-Guo Liufu (Aquaculture International, 2011)

Granaticins and their biosynthetic gene cluster from Streptomyces vietnamensis: evidence of horizontal gene transfer - Ming-Rong Deng; Jun Guo; Xiang Li; Chun-Hua Zhu; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2011)

Cloning and characterization of a maize SnRK2 protein kinase gene confers enhanced salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Hui-Yong Li; Ying-Hui Liu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell Reports, 2011)

Retinoic acid inducible gene-I and melanoma differentiation-associated gene 5 are induced but not essential for dengue virus induced type I interferon response - Cheng-Feng Qin; Hui Zhao; Zhong-Yu Liu; Tao Jiang; Yong-Qiang Deng; Xu-Dong Yu; Man Yu; E-De Qin (Molecular Biology Reports, 2011)

Transgenic sugarcane plants expressing high levels of modified cry1Ac provide effective control against stem borers in field trials - Li-Xing Weng; Hai-Hua Deng; Jin-Ling Xu; Qi Li; Yu-Qian Zhang; Zi-De Jiang; Qi-Wei Li; Jian-Wen Chen; Lian-Hui Zhang (Transgenic Research, 2011)

Detection of Staphylococcus aureus Carrying the Gene for Toxic Shock Syndrome Toxin 1 by Quantum-Dot-Probe Complexes - Dan Wang; Hui Chen; Hua Li; QiZhi He; XingHua Ding; Le Deng (Journal of Fluorescence, 2011)

Association of adiponectin gene polymorphisms with the risk of ischemic stroke in a Chinese Han population - Fang Liu; Zhiyi He; Shumin Deng; Hui Zhang; Nan Li; Jialiang Xu (Molecular Biology Reports, 2011)

Sustained Liver Targeting and Improved Antiproliferative Effect of Doxorubicin Liposomes Modified with Galactosylated Lipid and PEG-Lipid - Shaoning Wang; Hui Xu; Jinghua Xu; Ying Zhang; Yingchun Liu; Yi-hui Deng; Dawei Chen (AAPS PharmSciTech, 2010)

Effect of dietary protein reduction with synthetic amino acids supplementation on growth performance, digestibility, and body composition of juvenile Pacific white shrimp, Litopenaeus vannamei - Ming-Yan Huai; Yong-Jian Liu; Li-Xia Tian; Shi-Xi Deng; An-Long Xu; Wen Gao; Hui-Jun Yang (Aquaculture International, 2010)

Long-term effect of re-vegetation on the microbial community of a severely eroded soil in sub-tropical China - Huan Deng; Bin Zhang; Rui Yin; Hui-li Wang; Susan M. Mitchell; Bryan S. Griffiths; Timothy John Daniell (Plant and Soil, 2010)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Sequence-length variation of mtDNA HVS-I C-stretch in Chinese ethnic groups - Feng Chen; Yong-hui Dang; Chun-xia Yan; Yan-ling Liu; Ya-jun Deng; David J. R. Fulton; Teng Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Epigallocatechin-3-gallate induced primary cultures of rat hippocampal neurons death linked to calcium overload and oxidative stress - Shu-Ting Yin; Ming-Liang Tang; Hong-Min Deng; Tai-Ran Xing; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Fusarium solani, Tax-3, a new endophytic taxol-producing fungus from Taxus chinensis - Bai Wan Deng; Kai Hui Liu; Wen Qiang Chen; Xiao Wei Ding; Xiu Chao Xie (World Journal of Microbiology and Biotechnology, 2009)

A novel derivative of xanomeline improved memory function in aged mice - Yi-Hui Cui; Wen Si; Liang Yin; Shu-Ming An; Jing Jin; Shi-Ning Deng; Xiao-Hua Cao (Neuroscience Bulletin, 2008)

The cauliflower mosaic virus (CaMV) 35S promoter sequence alters the level and patterns of activity of adjacent tissue- and organ-specific gene promoters - Xuelian Zheng; Wei Deng; Keming Luo; Hui Duan; Yongqin Chen; Richard McAvoy; Shuiqing Song; Yan Pei; Yi Li (Plant Cell Reports, 2007)

The chemokine (C-C-motif) receptor 3 (CCR3) gene is linked and associated with age at menarche in Caucasian females - Fang Yang; Dong-hai Xiong; Yan Guo; Hui Shen; Peng Xiao; Feng Zhang; Hui Jiang; Robert R. Recker; Hong-wen Deng (Human Genetics, 2007)

A genome-wide linkage scan for quantitative trait loci underlying obesity related phenotypes in 434 Caucasian families - Lan-Juan Zhao; Peng Xiao; Yong-Jun Liu; Dong-Hai Xiong; Hui Shen; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2007)

In vitro regeneration and Agrobacterium-mediated genetic transformation of Euonymus alatus - Yongqin Chen; Litang Lu; Wei Deng; Xingyu Yang; Richard McAvoy; Degang Zhao; Yan Pei; Keming Luo; Hui Duan; William Smith; Chandra Thammina; Xuelian Zheng; et al. (Plant Cell Reports, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Land-cover density-based approach to urban land use mapping using high-resolution imagery - Xiu-ying Zhang; Xue-zhi Feng; Hui Deng (Chinese Geographical Science, 2005)

Mating system and DNA polymorphism of monokaryons with different mating type of Stropharia rugoso-annulata - Pei-Sheng Yan; Jia-Hui Jiang; Gui-Fang Li; Cong-Liang Deng (World Journal of Microbiology and Biotechnology, 2003)